Dental mesenchymal stem cells under inflammatory condition: A potential candidate for stem cell therapy - Shuqi Zhang; Jingjing Pan; Jinhong Lv; Yueli Lin; Ying Shi; Lin Cheng; Zesheng Li; M.M. Zhiqiang Chen (Tissue and Cell, 2027)

Bioaccumulation, oxidative stress, immune disruption, and metabolic alterations in Mytilus galloprovincialis exposed to nano-copper oxide - Yitong Gong; Yang Lin; Ziyan Lang; Jiawan Lv; Jing Sun; Liming Wang; Shujun Li; Weiang Zhang; Xiaoli Liu; Liping You (Marine Pollution Bulletin, 2026)

Bridging the domain gap: A transferable dynamic routing enhancer for robust aerial detection under adverse weather - Yu Wan; Jie Li; Liupeng Lin; Zhaowen Lv; Zaiyan Zhang; Qiangqiang Yuan; Huanfeng Shen (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Whole genome sequencing analysis and functional characterization of Lacticaseibacillus rhamnosus HP-B1083 - Da-Hu Zhang; Zhen-Dong Tian; Bao-Zhi Ge; Qian-Meng Qi; Jia-Lin Lv; Hang Wu; Shao-Yang Hou; Shu-Hang Zhang (Brazilian Journal of Microbiology, 2026)

Organic matter amendment regulates surface electrochemical properties of yellow soils: The major role of Alkyl C and O-Alkyl C - Xiaoshuai Song; Cheng Liang; Chenyang Liu; Lin Ning; Xiheng Lv; Wei Liu; Rena Yasin; Yunhang Luo; Jiangwen Li; Chenyang Xu; Wei Du; Wuquan Ding; et al. (Soil and Tillage Research, 2026)

Controlling nitrosamine accumulation in dry fermented sausages using Lacticaseibacillus rhamnosus H7: The role of physicochemical drivers and precursor depletion - Ying Yue; Ning Zhao; Bingrui Guo; Jing Lv; Xin Nie; Sufang Zhang; Yingxi Chen; Beiwei Zhu; Shengjie Li; Xinping Lin (Food Microbiology, 2026)

Distinct raindrop size distribution microphysical mechanisms of frontal and warm-sector heavy rainfall in Coastal Southeast China - Mingrui Guo; Wen Lin; Jingjing Lv; Chenglong Gong; Qing Duan; Jingxi Sun; Pengcheng Lin; Chunsong Lu; Yiqi Chen (Atmospheric Research, 2026)

FUT2-mediated α1,2-fucosylation in inflammatory bowel disease: mechanisms and translational potential - Jin Chen; Li Gan; Shuhong Zhang; Shengtao Liao; Lin Lv (Molecular Biology Reports, 2026)

Agmatine protects against MAFLD via decreasing RBM15/IGF2BP2-mediated m6A modification of SREBP1 - Guangkui Bu; Yu Li; Guangfu Lin; Lichun Han; Deyi Chen; Xiaoping Lv (Molecular Biology Reports, 2026)

Substituent-controlled phenoxy radicals drive cross-coupling transformation of tetracycline on δ-MnO2 - Yue Wang; Jingyi Lin; Yonghuan Zhao; Weiguang Lv; Bo Liang; Peihua Li; Kaisheng Zhang; Xing-jiu Huang (Water Research, 2026)

Variations in source-originated health risks of soil heavy metals in an open-pit mining area, northern China from 2014 to 2023 - Yamei Shao; Weibo Ma; Yicong Chen; Yujuan Lv; Nan Wang; Jie Lin; Yanli Lv; Haidong Li (Journal of Environmental Sciences, 2026)

Kinetic selectivity-driven propylene/propane separation in mixed matrix membranes with flexible-robust ELM-12 nanofiller - Xiaoqing Chang; Qin Shen; Liulin Lv; Wei Cui; Dongyang Li; Jing Wang; Yuqing Lin; Xiaoquan Feng; Yatao Zhang; Hideto Matsuyama (Desalination, 2026)

Interfacial charge redistribution at ZnSe/V2O5 heterojunction encapsulated in N, P-doped carbon enables high-performance wide-temperature Zn-air batteries - Mingjie Yi; Shuanghui Lv; Leqian Chu; Jingwen Zhang; Lijun Lin; Liangqi Gui; Jing Huang; Jiaheng Zhang (Chemical Engineering Journal, 2026)

Immobilizing MIL-9 in PVDF spheres for durable and efficient peroxymonosulfate activation toward antibiotic degradation - Xing-Lin Lv; Peng Wang; Xiang-Yu Li; Fei Wang; Zi-Yu Jia; Miao Chang; Xin Jiang; Zhao-Yi Liu; Xiao-Hong Yi; Anping Wang; Jiguang Deng; Chong-Chen Wang (Chemical Engineering Journal, 2026)

Non-covalent interactions between lignin and cellulase: From molecular mechanisms to precision regulation - Chengcheng Ye; Yuchen Han; Yanyi Tao; Lin Lv; Yu Long; Jianfeng Wu; Yongcan Jin; Wenjuan Wu (Bioresource Technology, 2026)

Piezoelectric-photocatalysis assisted chemical mechanical polishing: A cost-effective and efficient approach to atomic-scale processing of RS-SiC surfaces - Xingwang Xu; Jiayi Liu; Bin Lin; Tianyi Sui; Jinming Li; Bingrui Lv; Pengcheng Zhao; Hetian Hou; Cong Chen; Hualong Zhang; Yuhao Zhang; Jinhua Wei; et al. (Journal of Environmental Chemical Engineering, 2026)

Non-radical activation of peroxydisulfate by Fe-doped piggery digestate biochar for efficient sulfamethoxazole removal - Jiayi Li; Yunlong Wu; Qiqi Tang; Yuansheng Wang; Jiaqu Tan; Min Yu; Zhen Zhang; Zhixiao Lv; Yulong Zhang; Xueming Lin (Journal of Environmental Chemical Engineering, 2026)

Low-order polyimide-based COFs incorporated thermally rearranged mixed matrix membranes with enhanced H2/N2 and CO2/N2 separation performance - Yuanyuan Xu; Yunhua Lu; Pengwei Lv; Guoyong Xiao; Tonghua Wang; Lin Li (Journal of Environmental Chemical Engineering, 2026)

Treatment of nitrogen micro-polluted wastewater using a new type of biological folded non-aerated filter (BFNAF): Performance, microbial community and machine learning optimization - Jie Han; Youzhao Wang; Mingdong Chang; Xiaoyan Dang; Shumin He; Xiaodi Huang; Yongguang Ma; Zhipeng Wang; Yaonan Zhu; Junnan Liu; Jinxiang Wang; Lin Zhai; et al. (Journal of Environmental Chemical Engineering, 2026)

Chemical-free closed-loop conversion of nitrate into struvite fertilizer via exsolved high-entropy perovskite electrocatalyst - Li-Hui Yang; Yi-Heng Liu; Si-Hao Lv; Man-Ting Liao; Hui Lin; Wei Li; Cao Yang; An-Qi Wang; Hao-Yi Cheng (Journal of Environmental Chemical Engineering, 2026)

A-site magnesium regulation for defect-optimized perovskite oxides toward efficient and durable alkaline oxygen evolution - Xintong Lv; Kaitao Li; Chengjun Xie; Zijun Xu; Feifei Dong; Yufei Ma; Zhan Lin (Fuel, 2026)

Experimental investigation on MILD combustion characteristics of NH3/CH4 blended fuels in a swirl combustion chamber - Junjian Tian; Haobo Bi; Chuanwen Lv; Gaofeng Wang; Qizhao Lin (Fuel, 2026)

Gut microbiota-derived SCFAs mediate the intestinal anti-aging effect of structurally characterized Dendrobium officinale glucomannan via Treg immune regulation in mice - YingJie Dong; Yawen Sun; Minqiu Lin; Fan Liu; Jiayue Zhu; Bo Li; Guiyuan Lv; Suhong Chen (Food Research International, 2026)

Food-derived extracellular vesicles modulate ferroptosis: Implications for functional food development and healthy aging - Lin Zhang; Wangying Qiu; Mingrun Lu; Shuting Lan; Zuokai Lv; Haiyan Zhang; Yue Pang; Xingcan Zhang; Wenjing Xu; Haitao Wang; Jiahui Liu; Jiahui Ma; et al. (Food Research International, 2026)

Polygonatum kingianum polysaccharides ameliorate cognitive impairments in alcohol-exposed obese mice in a sex-specific manner by regulating the gut microbiome and metabolome - Jiayao Lv; Yizhe Qu; Qixin Yan; Ken Cheng; Qingyang Wu; Jiayi Zhang; Xinting Duan; Shanshan Han; Honglei Tian; Lin Shi (Food Research International, 2026)

Atomic-scale matrix partitioning of polar and antipolar motifs for high-density energy storage capacitors - Dingheng Lin; Bin Kong; Jinjun Liu; Jiarong Lv; Ya Yang; Wei Zhang; Sen Chen; Ning Liu; Zhongbin Pan (Chemical Engineering Journal, 2026)

Enabling fast Li+ transport in cellulose nanocrystals polymer electrolytes via grafting flexible acrylates for stable solid-state lithium metal batteries - Xinyan Lv; Shuting Liu; Lin Peng; Sheng Liu; Zhenkun Liu; Zuyun Chen; Xiaoyuan Yu (Carbohydrate Polymers, 2026)

Development of magnetic solid-phase extraction with magnetic graphene oxide composite nanospheres for sensitive determination of perfluoroalkyl substances in tea beverages - Xin-Li Song; Tong Sun; Ke-Chao Liao; Hui Lv; Pin-Pin Wang; Dong-Dong Wang; Yan Lu; Lin Li (Analytica Chimica Acta, 2026)

Nanozyme-loaded colorimetric gelatin methacryloyl microneedles for glucose detection in interstitial fluid - Shixian Lin; Ziqing Mao; Mengyao Miao; Wensheng Lin; Min Hu; Xinyan Shi; Ruxi Jin; Xiaoyu Lv; Ruijie Liang; Shijie Wang; Jingyan Li; Yupeng Xie; et al. (Analytica Chimica Acta, 2026)

A bioinspired membrane with structure-chemistry dual reinforcement for unconventional emulsion purification - Jie He; Xichi Xiang; Hongzhuo Xie; Haiying Lin; Qingge Feng; Guanjian He; Yujiang Fan; Chun Lv; Dongjun Li; Yuyu Pi; Yongjie Tuo; Gelimei Zhang; et al. (Chemical Engineering Journal, 2026)

Global Freshwater Resistomes Reveal Environmental Signatures Associated with the Burden of Drug-resistant Tuberculosis - Tong Li; Jiahui Lv; Yunye Tu; Li Cheng; Hongjun Xiao; Yanping Sun; Jia-xin Li; Mingkun Lv; Jingkai Yang; Guanghui Wang; Zexi Tang; Yajie Liu; et al. (Environmental Pollution, 2026)

Corrigendum to “TiO2/MIL-100(Fe) S-scheme heterojunction for efficient photocatalytic inactivation of Microcystis aeruginosa and microcystin degradation” [Chem. Eng. J. 524 (2025) 169033] - Jie Zhang; Na Lv; Mingcan Wu; Limeng Liu; Ling Fang; Mingyang Ma; Rosaiah Pitcheri; Shu Lin; Kezhen Qi (Chemical Engineering Journal, 2026)

Nanoconfined iron-based catalysts activate peroxymonosulfate via electron transfer and radical pathways for efficient bisphenol A removal - Mingyu Sun; Qingqing Hao; Jingxingyu Wu; Chenye Fu; Long Lin; Guochun Lv; Shihuai Deng; Xiaohui Lu; Jiali Peng (Journal of Hazardous Materials, 2026)

Facet-controlled Pt/CeO2 unlocks low-humidity HCHO oxidation via terminal hydroxyls - Juanjuan Gong; Ruicheng Wang; Yilong Lin; Hui Chen; Bihong Lv; Huawang Zhao; Huazhen Shen; Zhiwei Huang; Xiaomin Wu; Guohua Jing (Journal of Hazardous Materials, 2026)

Human-relevant co-exposure to 6:2 Cl-PFESA and PFHxS impairs sperm motility and blood-testis barrier integrity in male mice: Evaluation of combined effects - Lan Shi; Tianrui Gao; Zhipeng Zhu; Fan Yang; Bing Han; Jia Lv; Lin Tao; Yang Gao; Rong Hua; Huan Wu; Yichao Huang; Xiaojin He (Journal of Hazardous Materials, 2026)

The content, bio-accessibility and in vitro bioavailability of lead species in various seafood samples collected from Fujian, China - Siyi liu; Ying Peng; Yuting Yang; Wenchao Lv; Jingguang Li; FengFu Fu; Yue Lin (Journal of Hazardous Materials, 2026)

Microbial and Flavor-Related Metabolic Changes in Sour Meat Inoculated with Saccharomyces cerevisiae LXPSC1: An Integrated Multi-omics Study - Shimiao Wang; Siqi Zhang; Jing Lv; Xianhao Zhang; Yiyao Wang; Ying Shi; Yingxi Chen; Xinping Lin (Food Bioscience, 2026)

Fe2+ alters carbon and nitrogen metabolic networks in a composite microbial consortium: Metagenomic insights into the shift from denitrification to DNRA - Lin Zhang; Bowei Zhao; Xiao Zhang; Yuan Li; Haibo Li; Shuying Yuan; Haoxiang Ning; Bingcheng Lv; Le Li; Xiaojun Fan; Xiuping Yue (Environmental Research, 2026)

Fluid-like polarization rotation in interpenetrating diffuse phase boundary for dielectric capacitors - Ya Yang; Yawen Cui; Linqiong Xu; Jiarong Lv; Dingheng Lin; Bing Kong; Jinjun Liu; Ning Liu; Zhongbin Pan (Chemical Engineering Journal, 2026)

Molecular wedging strategy enables random-entangled polyimide binders for highly durable Si/C composite anodes - Junhao Xin; Zhiguang Zhang; Zixin Lv; Guojing Zhao; Lin Chen; Shuanyan Kang; Junfen Li; Nanwen Li (Chemical Engineering Journal, 2026)

Tea proteins, peptides, and amino acids: A whole-chain review of profile, functionalization, transformation, and valorisation - Zi-Hao Qiu; Qiu-Sheng Zhong; Gao-Zhong Yang; Yin Zhu; Yue Zhang; Qun-Hua Peng; Susanne Baldermann; Zhi Lin; Hai-Peng Lv; Jiang Shi (Trends in Food Science & Technology, 2026)

Retraction notice to “Scenario analysis on optimal farmed-fish-species composition in China: A tentative theoretical methodology to benefit wild-fishery stock, water conservation, economic and protein outputs under the context of climate change” [Sci. Total Environ. 806 (2022) 150600] - Guobao Song; Xinyue Zhao; Lin Lv; Qi Yuan; Yongchi Ma; Laura Batlle Bayer; Dan Zhang; Pere Fullana-i-Palmer (Science of The Total Environment, 2026)

AGR2-high cells drive a FOXM1-mediated pro-malignancy program in non-functional pancreatic neuroendocrine tumors (NF-PanNETs) and informatively predict patient outcomes - Junya Peng; Rui Jiang; Jiajuan Tu; Wanli Liu; Lu Ping; Ruikang Dun; Wenyu Zhang; Hao Chen; Yihong Shi; Xu Pan; Panpan Jia; Mengjie Li; et al. (Science Bulletin, 2026)

Active dynamic heterogeneous ensemble learning-based nose optimization for impact load reduction during water entry - Mengsen Zhao; Junhao Xiao; Hao Lin; Kaihong Huang; Hui Peng; Yunxiao Lv (Ocean Engineering, 2026)

Synthetic microbial community shields wheat from cadmium: Coordinating host metabolic reprogramming and rhizosphere microenvironment regulation - Huangxin Chen; Lin Kong; Yaoyuan Zhang; Guiyin Wang; Xin Qi; Changlian Xu; Zhanbiao Yang; Zhang Cheng; Guochun Lv; Junzhuo Cai; Lilin Wang; Yongxia Jia; et al. (Journal of Hazardous Materials, 2026)

Highly synergistic degradation of fluoroquinolones driven by redox dual channel mechanism in Fe(Ⅲ)-mediated thermally activated persulfate system - Lingzhi Shen; Yongpeng Zhang; Yuxing Xian; Zihong Xu; Zihao Guo; Yixun Zheng; Yue Yang; Zili Lin; Kun Yao; Zheng Hu; Yanli Wang; Zhenjun Xiao; et al. (Journal of Hazardous Materials, 2026)

Exploring the endogenous and exogenous key aroma-active components in three aroma types of black teas from different cultivars - Weixuan Li; Zhouling Zhong; Han Yan; Longyu Guo; Ge Chen; Zhi Lin; Haipeng Lv; Yue Zhang; Yin Zhu (Food Research International, 2026)

Insights into the molecular basis of umami in premium green teas via integrated metabolomics, peptidomics, and in silico molecular docking - Jiaqi Yang; Shitao Fang; Qi Zhou; Yizhi Wang; Kangni Yan; Peng Qunhua; Lin Zhi; Wu Yan; Fu Jianyu; Mu Dan; Lv Haipeng; Shi Jiang (Food Chemistry, 2026)

Storm sequences reduce the wave attenuation capacity of salt marshes - Yuxi Ma; Wenzhen Zhao; Liming Xue; Bas Hofland; Lin Su; Lv Gong; Shiwei Lin; Zhan Hu; Xiuzhen Li; Tjeerd J. Bouma (Estuarine, Coastal and Shelf Science, 2026)

Halloysite surface-induced spin-state regulation and hydroxyl-assisted adsorption: A dual enhancement mechanism for PMS activation - Haiyi Lv; Sikai Zhao; Yan Li; Qiang Zhao; Xiaoyu Jiang; Hongshan Bi; Zhou Lin; Yanbai Shen (Chemical Engineering Journal, 2026)

Interatomic push-pull engineering in heterocyclic covalent organic frameworks for boosting photocatalytic hydrogen peroxide production - Wenjun Yang; Jialong Lv; Yuelin Chen; Weikang Peng; Shibin Zheng; Wei Lin; Jinhong Bi; Guocheng Huang (Chemical Engineering Journal, 2026)

Faecalibaculum rodentium- derived quinic acid- mediated Treg differentiation drives the attenuation intestinal inflammation by Agrimoniae Herba polysaccharides - Jiayan Hu; Yitong Yu; Zhibin Wang; Muyuan Wang; Yuxi Wang; Xiaowei Chen; Yuyue Liu; Mengyu Zheng; Chengtao Liang; Chenran Lv; Anqi Yang; Zhengdao Lin; et al. (Carbohydrate Polymers, 2026)

Ferritin Associates with Interspecific Variation in Iron Accumulation among Five Economically Important Bivalves: Sequence, Expression, and Functional Analyses - Jiachen Li; Ao Li; Zizheng Wei; Zhihua Lin; Liyuan Lv; Hanhan Yao; Yinghui Dong (Biological Trace Element Research, 2026)

Estuaries as fragmentation hotspots and transport regulators of microplastics - Yancheng Lv; Fei Jiang; Yihe Wang; Yuye Chen; Yan Yang; Jinyang Lin; Xiaoteng Shen; Qiqing Chen (Marine Pollution Bulletin, 2026)

Microbial mechanisms regulate soil carbon dynamics under nitrogen addition in mangrove wetlands of Dongzhai Harbor, Southern China - Cuiting Meng; Jingqiu Jiang; Shuguo Lv; Pengxia Liu; Guanghui Lin; Kun Lei; Xiaoguang Li (Marine Pollution Bulletin, 2026)

Quercetin attenuates cisplatin-induced muscle atrophy via Hippo/YAP1 signaling pathway - Jingchun Lv; Jianwei Lin; Xiaojing Chen; Qi Wu; Zhiyao Cao; Dapeng Jiang (Journal of Natural Medicines, 2026)

Subduction-controlled Late Triassic rifting along the northern margin of Gondwana - Si-Lin Sun; Jian-Jun Fan; Bo-Chuan Zhang; Jia-Wei Bai; Yang Wang; Jun-Pu Lv; Xin-Yu Hou (International Geology Review, 2026)

Ecological impacts of herbicide control in a protected coastal wetland of Chongming Island (Yangtze River Estuary, eastern China) assessed using macrobenthic indicators - Tian Zhu; Lin Yang; Hanzhong Liu; Shiyun Qiu; Qichen Jiang; Weiwei Lv; Yue Wang (Marine Pollution Bulletin, 2026)

AjIGF2 relieves Vibrio splendidus induced inflammation through metabolic reprogramming in Apostichopus japonicus - Qikai Lin; Chenghua Li; Lianlian Sun; Zhen Zhang; Si Zhu; Zhimeng Lv (Aquaculture, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

Influence of the C/N ratio on lactic acid production from food waste under high substrate concentration - Liang Song; Jing Wu; Yanghua Duan; Minghua Liu; Chunxiang Lin; Yifan Liu; Xiaoxia Ye; Yuancai Lv; Chenhang Cai; Jiayi Chen; Jianhui Huang; Zhixin Huang (Journal of Environmental Management, 2026)

Impacts of continuous ultra-low temperature freezing on the evolution of pore throat characteristics and coalbed methane production in bituminous coal - Lei Qin; Siheng Lin; Niandong Chen; Feilong Zhang; Zengning Huang; Han Wang; Shiyin Lv; Miao Mu (Journal of Applied Geophysics, 2026)

Westerly reorganization driven by orbital forcing: Late Miocene aridification in the Tarim Basin, Central Asia - Dong Wang; Qingqing Qiao; Chuang Xuan; Zhuangzhuang Lv; Sunyi Dong; Gangqiang Li; Long Ma; Yudong Chen; Zhanwei Lin; Zhongyin Gao (Global and Planetary Change, 2026)

Metabolomic and transcriptomic analyses reveal nutritional composition differences and underlying molecular mechanisms in Chimonobambusa utilis shoots with distinct sheath colors - Hanjiao Zhang; Saixue Hu; Wanqi Zhao; Zhuo Lv; Binao Zhou; Shuyan Lin (Food Bioscience, 2026)

Layered double hydroxide/Cu-luteolin nanoparticle-loaded hydrogel coating: Promoting healing of infected bone defects - Zitong Tian; Jian Yin; Yakun Mao; Hao Yang; Pengde Han; Lili Song; He Lin; Lei Xie; Xiao Huang; Kongpeng Lv; Yong Huang (Chemical Engineering Journal, 2026)

Scalable fabrication of ultrathin LiIn@Cu composite anodes via roll-to-roll dip coating for high-energy-density batteries - Qihang Zhang; Anli Wang; Yifei Chen; Zihan Lin; Changyi Dong; Qiang Lu; Jixian Lv; Weike Yu; Siming Yang; Xiaoqun Qi; Jia Li; Fei Shen; et al. (Chemical Engineering Journal, 2026)

Stage-dependent topographic controls on vegetation recovery and landscape-pattern evolution under contrasting restoration treatments in an abandoned mine from UAV multispectral time series - Lv Zhou; BoWen Shi; ZhiQiang Lin; Jie Zhang; Jun Lu; Fei Yang; Fan Jiang; Xiang Huang (CATENA, 2026)

Effects of faba beans ( Vicia faba L.) on the growth, amino and fatty acids compositions, flesh quality and oxidative stability of African catfish, Clarias gariepinus - Qingqing Li; Qifeng Lu; Huai Zhang; Li Lin; Huohong Lv; Xinyi Li (Journal of Fish Biology, 2026)
The African catfish, Clarias gariepinus , is a commercially vital fish that is cultured worldwide, but it often exhibits low‐quality flesh despite high production, which limits its market value. Consequently, there is increasing interest in identifying alternative feed ingredients that can improve flesh quality without severely compromising growth performance. Previous studies have shown that the inclusion of raw faba beans ( Vicia faba L.) in the diet can improve muscle quality in species like tilapia and grass carp by increasing muscle crisped, yet information on their effects in C. gariepinus remains limited. This study aimed to assess the impacts of 0% (Diet I, control group), 40% (Diet II), 50% (Diet III), 60% (Diet IV) and 70% (Diet V) dietary faba beans inclusion on growth performance, physiological parameters and muscle quality of C. gariepinus during 90 days of cultivation. Compared to the control group, C. gariepinus fed faba beans‐containing diets exhibited lower body weight, body weight gain rate (WGR) and specific growth rate (SGR), accompanied by a significant decline in glucose‐6‐phosphate dehydrogenase activity ( p C. gariepinus receiving faba bean‐supplemented diets exhibited a higher density of muscle fibres, broader gaps between fibres and reduced fibre diameter compared with the control group. Fish fed 50% and 60% faba bean diets exhibited significantly greater muscle hardness ( p p C. gariepinus ; however, inclusion levels must be carefully managed because of their adverse effects on growth.

Genome Analysis and Reproductive Observations Suggest Allotetraploidy and a Potential Reproduction–Metabolism Association in the Endangered Fish Neolissochilus heterostomus - Tiaoyi Xiao; Zhichao Wu; Dongfang Li; Beibei Qin; Shengguo Tang; Chengyi Lin; Kuayun Mao; Jinwu Yin; Zhihu Li; Hongquan Wang; Zhao Lv (Fishes, 2026)
Neolissochilus heterostomus, a cyprinid fish endemic to Yunnan Province, China, is highly valued for both ornamental and edible purposes, yet its wild populations are currently declining and classified as endangered. In this study, we present a chromosome-level genome assembly of N. heterostomus, utilizing the PacBio HiFi and Hi-C strategies. The assembled genome spans 1793.99 Mb and is anchored to 50 chromosomes, comprising a total of 50,203 genes. Genomic features and chromosomal karyotype data recorded in the present study are consistent with an allotetraploid origin for N. heterostomus. Comparative genomics shows that N. heterostomus shares a close phylogenetic relationship with another allotetraploid fish, the common carp Cyprinus carpio. In total, 4687 expanded and 1365 contracted gene families were identified in N. heterostomus. Further enrichment analyses indicated an overrepresentation of metabolism-related pathways among the expanded and positively selected gene families, whereas the contracted gene families were enriched in reproduction- and embryonic development-related pathways. Reproductive observations further indicate that N. heterostomus produces fewer eggs than other cyprinid species characterized by relatively long embryonic development periods (106.1 h; accumulated temperature: 2260.6 °C·h), including common carp, goldfish (Carassius auratus), grass carp (Ctenopharyngodon idella), pond loach (Misgurnus anguillicaudatus), and blunt snout bream (Megalobrama amblycephala). These findings suggest a potential association between metabolism-related genomic features and reproductive traits, although functional validation remains necessary. Overall, this study may offer insights into the polyploidization, metabolic, and reproductive traits of N. heterostomus, thereby providing genomic and biological resources that may support future studies relevant to the conservation and management of this endangered species.

A novel UAV-based fusion of spectral and textural features with canopy stratification for accurate estimation of vertical nitrogen distribution in cotton - Guldana Sarsen; Qiu-xiang Tang; Ya-bin Li; Long-long Bao; Yu-hang Xu; Guang-yun Sun; Jian-wen Wu; Yierxiati Abulaiti; Qing-qing Lv; Fubin Liang; Na Zhang; Ren-song Guo; et al. (Computers and Electronics in Agriculture, 2026)

Moderate net-chasing enhances stress resilience in freshwater prawns Macrobrachium rosenbergii: evidence from behavioral and physiological recovery - Jiangtao Li; Jiale Zhou; Licheng Zeng; Yingtong Ou; Zhongjie You; Zheng Xiao; Jianjun Guo; Li Lin; Xiaojing Lv (Aquaculture, 2026)

Building tailorable Kagome lattices with quantum-confined orbitals in periodic mirror twin boundaries - Ruo-Han Zhang; Jiang-Hui Pan; Ya-Xin Zhao; Chen-Yue Hao; Ke Lv; Mo-Han Zhang; Xiao-Ya Wang; Ya-Ning Ren; Ji Feng; Lin He (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

A stabilized single-sided nonlinear inverse finite element framework for large-deformation displacement field reconstruction - Shiyan Lv; Meng Zhang; Lin Ren; Zhaochun Zhang; Donghui Wang; Ding Chen; Xiaohui Zhang; Haibo Hu; Nan Li (Ocean Engineering, 2026)

Cooperative strengthening of active sites and charge transport for efficient visible-light photodegradation of tetracycline via N-doped copper phenylacetylide - Zheng Hu; Zihao Guo; Yixun Zheng; Yingyi Chen; Zili Lin; Zhenjun Xiao; Ping Chen; Wenying Lv; Guoguang Liu (Journal of Environmental Chemical Engineering, 2026)

Overlooked spectral matching-Enabled sulfoxide wastewater valorization and in situ pollutant elimination - Lingzhi Shen; Yue Yang; Yixun Zheng; Mengyang Niu; Zhiqing Lin; Zihong Xu; Yongpeng Zhang; Shan Yao; Yanli Wang; Kun Zhao; Zhenjun Xiao; Zili Lin; et al. (Journal of Cleaner Production, 2026)

Effect of liquid CO2 phase transition fracturing on gas expansion energy - Nian Si; Gaofeng Liu; Zhen Zhang; Zixu Zhang; Huan Liu; Runsheng Lv; Xiaoming Wang; Ping Chang; George Barakos; Jia Lin (Gas Science and Engineering, 2026)

A molecular study of synergistic inhibition of methane hydrate growth with glycine-based peptides and PVCap - Huiyun Mu; Yang Liu; Lin Ding; Wenlong Wang; Xiaofang Lv; Yisong Yu; Qianli Ma; Chuanshuo Wang; Xiaoyan Li; Shidong Zhou (Fuel, 2026)

Highly efficient detection of imidacloprid in agricultural samples based on ZIF-8-derived carbon particles-modulated fluorescence polarization immunoassay - Rui Sun; Pei Lv; Bingqing Shen; Qian Wu; Yuan Xue; Lin Chen; Weibin Li; Zhenjiang Liu (Food Chemistry, 2026)

Strong and liquid-free ion-conductive elastomer reinforced by chemically cross-linked cellulose network for strain sensors and triboelectric nanogenerators - Meilin Zhang; Zhongshen Cai; Yufan Lan; Zongming Lv; Rui Qian; Zhongsheng Shi; Lihua Fu; Baofeng Lin; Chuanhui Xu; Qunyang Li; Bai Huang (Chemical Engineering Journal, 2026)

Octopus-inspired photonic-electronic synergistic hydrogel tactile sensor for accurate and reliable health monitoring - Boqing Jia; Changxu Zhang; Yihe Zhao; Lan Yu; Yibo Lv; Gengyu Han; Xinyu Shi; Zhuorui Chen; Xuanting Lu; Jiaxiang Wang; Min Li; Guoxi Luo; et al. (Chemical Engineering Journal, 2026)

Depth-coupling pattern between forest soil microorganisms and carbon mineralization in southwestern China - Shuang Ding; Shengzhao Wei; Honghong Lin; Li Rong; Enwei Zhang; Xue Yang; Huanxu Lv; Xingwu Duan (CATENA, 2026)

Efficient DNA Extraction Coupled with Fluorescence Loop-Mediated Isothermal Amplification (LAMP) for On-Site Early Warning Detection of Vibrio parahaemolyticus - Fengyi Liu; Qilin Geng; Xue Sun; Jie Lin; Xuan Zhu; Danyang Wang; Xiao-Hua Zhang; Jingjie Hu; Shi Wang; Lisui Bao; Jia Lv (Marine Biotechnology, 2026)

Ginsenoside F1 ameliorates nonalcoholic fatty liver disease by activating the AMPK/PGC-1α pathway and autophagy - Wenjiao Xie; Yun Lv; Zhixian Zhou; Guihui Wang; Xu Zhang; Daiping Peng; Haiyan Yang; Juan Liao; Xin Sun; Wei Lin; Zhe Ding (In Vitro Cellular & Developmental Biology - Animal, 2026)

Optimization of pediatric dosing regimens for aztreonam and amoxicillin/clavulanate combination therapy against multidrug-resistant bacteria - Lili Wang; Mengyuan Wu; Lin Qu; Pengfei Wang; Ziwei Yu; Hua Deng; Frederico S. Martins; Jiayuan Zhang; Da Rong; Mingming Yu; Zhihua Lv; Sherwin K. B. Sy; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Ectomycorrhizal and saprotrophic fungi are linked to reduced pathogenic fungi across roots and rhizosphere soils of major afforestation species in northeastern China - Wen Guo; Xiangxia Yang; Yaping Liu; Xiaoding Lin; Le Chang; Yaru Wei; Mingming Xia; Minghao Lv; Kazuo Isobe (Soil Ecology Letters, 2026)

ZDHHC14-driven RUNX2 S-palmitoylation attenuates ferroptosis and enhances chemoresistance in ovarian cancer via the YAP1/GLS1 axis - Tao Li; Bin Lv; Hai Lin; Hong Zhang; Yingchun Wan (Apoptosis, 2026)

Integrated Diagnosis and Therapy Using Flexible Contact Electrodes: Low-Voltage Irreversible Electroporation and Quantitative Assessment of Therapeutic Efficacy - Yuchen Cheng; Bowang Cheng; Jingyu Li; Zhuoqun Li; Fulai Lin; Yuan Qi; Haorui Xue; Jiawei Wang; Jian Lv; Fenggang Ren; Weidong Ding (Annals of Biomedical Engineering, 2026)

Click Chemistry-Based Quantification of Extracellular Matrix Turnover for Drug Screening and Regenerative Medicine - Annie Porter; Songshan Fan; Ying Peng; Mengxi Lv; Yilu Zhou; Abdulaziz Alanazi; Lin Han; Liyun Wang; X. Lucas Lu (Annals of Biomedical Engineering, 2026)
Purpose To develop and validate a bioorthogonal labeling approach for quantifying ECM remodeling in living cell and tissue culture systems. Methods Strain-promoted azide-alkyne (SPAAC) reactions, or copper-free click chemistry, were used to fluorescently label newly synthesized glycan and protein matrix components. ECM synthesis and degradation was quantified in cartilage explants, human mesenchymal stem cells, and SKBR3 breast cancer cells under various external stimuli, including inflammation, mechanical stimulus, and drug treatment. Results The click chemistry method reliable quantified ECM turnover across platforms. It detected reduced glycan and protein synthesis after 24-hour inflammatory challenge and enabled longitudinal tracking of ECM degradation in cartilage explants. The technique demonstrated high sensitivity, measuring increased ECM deposition by ~ 10,000 human mesenchymal stem cells in 12-hour intervals and substrate stiffness-dependent synthesis by SKBR3 cells. Additionally, the approach supported osteoarthritis drug screening by identifying compounds that mitigated inflammation-induced ECM degradation. Conclusion Compared to traditional biochemical or histological assays, the click chemistry-based technique provides higher sensitivity, reduced sample requirements, and improved temporal resolution for quantifying ECM turnover. Its versatility enables broad application in tissue engineering, regenerative medicine, disease modeling, and high-throughput drug evaluation.

An Edge-Ready Lightweight Computer Vision Framework for On-Site Fish Disease Detection in Aquaculture Management - Jiawen Li; Weidong Zhang; Shengzhao Xiao; Xuanzhong Chen; Yuesheng Huang; Jujian Lv; Kaihan Lin; Xianglei Hu; Xianxian Zeng; Rongjun Chen (Fishes, 2026)
Efficient detection of fish diseases is essential for intelligent health monitoring and timely intervention in aquaculture. However, current computer vision models remain computationally intensive, hindering their deployment on resource-constrained edge devices in aquaculture applications. To this end, this study developed a lightweight detection framework based on an improved You Only Look Once (YOLO), aiming to achieve a favorable balance between detection accuracy and on-site inference efficiency. First, a Dual-Branch Feature-Preserving Downsampling (DFPD) module was proposed to enhance the extraction of valuable disease-related cues with minimal computational overhead. Subsequently, structured pruning was applied to compress the optimized baseline model. Four pruning techniques, including Slim, GroupTaylor, Layer-Adaptive Magnitude-Based Pruning (LAMP), and L1-based, were evaluated under the same conditions. The enhanced baseline model improved precision from 0.864 to 0.908 and mAP@0.5:0.95 from 0.613 to 0.632, while already reducing the Number of Parameters (Params) and Giga Floating-point Operations Per Second (GFLOPs) compared with the original YOLOv8n. Among the pruning techniques, L1-based produced the best overall trade-off, yielding a final model that maintained a F1-score of 0.860 while reducing Params and GFLOPs by 54.7% and 49.4%, respectively, relative to the original detector. Ablation studies further revealed that a moderate FLOPs reduction of approximately 41% to 47% was optimal for preserving diagnostic performance while enhancing compactness. Edge deployment tests on an RK3588S device verified the framework’s practical inference speed advantage. Therefore, this study offers a deployment-friendly computer vision solution for on-site fish disease detection in aquaculture management, particularly suited to real-world scenarios with limited computational resources.

Evaluating sustainable coastal management strategies following Spartina alterniflora eradication: Insights from typhoon-induced hydro-sedimentary responses - Lv Gong; Yang Hu; Yuanhao Song; Liangxun Pan; Lin Su; Xiaoyu Yu; Wenzhen Zhao; Ben Li; Xiuzhen Li (Ocean & Coastal Management, 2026)

Multi-time point transcriptomics and metabolomics reveals toxic responses of imidacloprid exposure in Aquatica leii (Coleoptera: Lampyridae) - Jiapeng Li; Jiani Lin; Chao Liu; Qimeng Wang; Wangxin Xia; Qian Zhao; He Lv; Chengquan Cao; Yiping Wang (Pesticide Biochemistry and Physiology, 2026)

Transcriptional activation of TcToll9 to exogenous bacteria in the larvae of Tribolium castaneum - Qiuying He; Shiyuan Li; Hui Lv; Ruixuan Lin; Xintong Wu; Jisheng Liu (Journal of Stored Products Research, 2026)

RDX as the sole nitrogen source affects the nitrogen metabolism in Rhodococcus sp. LMD - Songwei Hu; Mengdi Li; Yaya Huang; Yanchao Li; Songrui Zhang; Wenjia Li; Bing Lin; Jiaxin Zhengchen; Qi Lv; Xuanrui Shen; Huibin Zou; Fengbing Liang; et al. (Journal of Hazardous Materials, 2026)

Application of layered double hydroxides (LDHs) derived catalysts for selective catalytic reduction of NOx with NH3 - Tian-yu Lv; Zuo-lin Cui; Rui-tang Guo (Fuel, 2026)

Corrigendum to “Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis citrina Baroni)” [Food Chem. 506 (2026) 148147] - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Bridging accelerated cell-level degradation to module-relevant failure mechanisms in TOPCon solar cells and modules - Xinyuan Wu; Wei Wu; Weiguang Yang; Yan Zhang; Jiexi Fu; Xutao Wang; Jing Yuan; Jianjun Nie; Zhencong Qiao; Chao An; Feng Li; Lin Lv; et al. (Chemical Engineering Journal, 2026)

A novel double-layer composite material with excellent radiative cooling and thermal management for electronic devices - Haoxin Lv; Haixuan Liu; Jiahui Lin; Jintao Huang; Hanlin Xie; Xiaofeng Li; Yonggang Min; Xiang Lu (Chemical Engineering Journal, 2026)

Cloning, heterologous expression, and characterization of a metagenome-derived GH10 xylanase with salt and alkali tolerance from Xinjiang saline-alkali soil - Jing Gao; Hua-Lin Li; Mao-Song Li; Zong-Jin Shao; Zheng-Feng Yang; Chan-Jin Li; Zhi-Xin Zhang; Dan Zhu; Zhi-Hua Lv; Rong-Huan Song; Jian-Ling Li; Wei Hu; et al. (Antonie van Leeuwenhoek, 2026)

Vibrio sinaloensis NH-7 induces yellow-spot and rough-shell syndrome in Porphyra sensu lato (Bangiales, Rhodophyta) - Jiaxia Lv; Qiqin Liu; Xinwei Wang; Caihua Lin; Yangyin Mao; Xianming Tang; Juanjuan Chen; Haimin Chen; Rui Yang (Aquaculture, 2026)

Density-dependent effects of net-chasing training on aggression, stress, and metabolic load in the freshwater prawn Macrobrachium rosenbergii - Jiangtao Li; Jiale Zhou; Zhongjie You; Zheng Xiao; Licheng Zeng; Li Lin; Xiaojing Lv (Aquaculture, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Linking chemical profiles to sensory quality: Insights into color and taste formation in purple leaf tea infusions - Gaozhong Yang; Mengxue Zhou; Yanan Li; Paul A. Kilmartin; Zhi Lin; Jiang Shi; Haipeng Lv (Food Chemistry, 2026)

Adaptive dual-mode photoelectric eutectogel interface for closed-loop human-machine interaction - Xinpeng Lv; Kai Gong; Ze Li; Zhongyuan Lin; Hongqiu Wei; Jianhui Sun; Yongjun Liu; Peng Li (Chemical Engineering Journal, 2026)

Surface piezotronics in centrosymmetric silicon for ultra-sensitive strain sensing and mechanoelectronic transduction - Mingqiang Zhong; Shaopeng Wang; Tianli Meng; Ao Li; Jiale Lv; Ehud Gazit; Zhong Lin Wang; Rusen Yang (Chemical Engineering Journal, 2026)

Efficiency improvement of TOPCon half-cells and modules via laser-assisted edge isolation (LAEI) technology - Xukai Zhao; Zunke Liu; Biao Wu; Yi Liu; Xiaowei Liu; Hongping Jiang; Chaoyan Fang; Chen Lv; Yikun Liu; Shihua Chen; Wenli Yan; Wei Liu; et al. (Chemical Engineering Journal, 2026)

Nanoscale modulation engineered Au-In2O3-xFx nanorod bundles for highly sensitive, ultra-rapid responding/recovering TEA sensing platform based on LSPR oscillation effect - Zhidong Jin; Jinbo Zhao; Lin Liu; Zhihong Lv; Fei Liu; Shiqiang Li; Jiurong Liu; Lili Wu (Chemical Engineering Journal, 2026)

Integrated dynamic control and enzyme co-localization strategies enable high-efficiency stilbenoid biosynthesis - Guofu Zhao; Pengpai Li; Xinyao Ding; Jiugong Lv; Ying Yang; Lin Liu; Lihan Zi; Qiang Zhang; Liya Liang; Rongming Liu (Bioresource Technology, 2026)

Atmospheric CO₂ concentration gradients at the coastal region of the Yangtze River Delta: Patterns and drivers - Yi Lin; Honggang Lv; Kehan Chen; Peng Guo; Yifei Jiang; Lin Xiao; Tienan Zhao; Haiyan Wang; Yuanyuan Chen; Kunpeng Zang; Shuangxi Fang (Atmospheric Research, 2026)

Prey selection and foraging behavior of Eriocheir sinensis towards three freshwater mollusk species: Mechanisms and ecological implications - Yanming Sui; Aijia Lin; Weiwei Su; Weiyi Zou; Yiyun Zhang; Linlan Lv; Hucheng Jiang (Behavioural Processes, 2026)

Research progress on NSP4 protein of porcine reproductive and respiratory syndrome virus - Xiaolin Lan; Fang Liang; Gan Li; Yaqiong Ye; Feng Li; Chen Lv; Kexin Liu; Zhiyu Yang; Ruyu Sun; Keshan Zhang; Lin Wang; Huawei Li; et al. (Veterinary Research Communications, 2026)

Landslide susceptibility assessment based on Bayesian optimization and geographical similarity - Jiayu Yan; Shengwu Qin; Wendi Rao; Chaobiao Zhang; Jiangfeng Lv; Zhijun Lin; Feng Wan; Jiasheng Cao (Natural Hazards, 2026)

Global-to-regional variations in the effects of grassland management on soil carbon - Xi Lin; Shengwei Zhang; Alfredo Huete; Han Y.H. Chen; Hongbin Zhao; Qinsi He; Shengwei Lv; Qian Zhang; Xiaoduo Zhang; Xiaofeng Zhang (Agriculture, Ecosystems & Environment, 2026)

Rapid and Simple Detection of Enterocytozoon Bieneusi Using Lateral Flow Assay Based on Recombinase Polymerase Amplification or Nested PCR Combined with CRISPR–Cas12a - Yi-Yang Liu; Yue-Rong Lv; Jun-Tao Jia; Rong Zhang; Bo Yang; Shi-Yuan Xue; Hasi Bayaer; Alateng Bagen; Rui-Bin Chen; Siqin Tunala; Rui Wang; Yu-Lin Ding; et al. (Acta Parasitologica, 2026)

Multi-omics analysis investigates the effects of replacing fishmeal with intestinal mucosal protein on growth performance and intestinal health in hybrid sturgeon - Yuanfa He; Jun Wen; Hang Chen; Guangjun Lv; Yongjun Chen; Shimei Lin; Haiping Liu; Zhijian Wang; Hailong Ge (Aquaculture, 2026)

Application of ENU-mediated efficient mutagenesis in breeding of the big belly seahorse (Hippocampus abdominalis) - Xiao-lei Su; Chun-yu Hou; Lin Shi; Shi-chang Zhang; Cheng-de Fan; Jie-zhou Wang; Yi-cong Ma; Wu-hong Lv; Cong Liu; Guo-dong Zheng; Kai Wang (Aquaculture, 2026)

Size-dependent effects of polystyrene Nanoplastics on hepatic Immunometabolism and the gut-liver Axis in the Swamp Eel (Monopterus albus) - Mingming Han; Wenzong Zhou; Ji Liang; Aileen Tan Shau-Hwai; Zihan Zhou; Lin Cheng; Jiayuan Liao; Weiwei Huang; Qichen Jiang; Weiwei Lv (Aquaculture, 2026)

The overlooked role of nitrate in mediating electron transfer and enhancing reactive species generation in TiO2 photocatalytic water remediation - Zheng Hu; Jin Wu; Lingzhi Shen; Zili Lin; Zihong Xu; Zhenjun Xiao; Zheng Fang; Daguang Li; Ping Chen; Wenying Lv; Guoguang Liu (Process Safety and Environmental Protection, 2026)

The formation mechanism of self-assembly composite gels - Dingyang Lv; Fusheng Chen; Lijun Yin; Xi Yang; Xingfeng Guo; Fengyan Lin (Journal of Food Engineering, 2026)

NMR study on the changes of water content characteristics and pore structure evolution during melting of coal frozen with liquid nitrogen - Lei Qin; Hui Wang; Haifei Lin; Pengfei Liu; Shiyin Lv; Jiawei Li (Journal of Applied Geophysics, 2026)

Adaptive image zoom-in with bounding box transformation for UAV object detection - Tao Wang; Chenyu Lin; Chenwei Tang; Jizhe Zhou; Deng Xiong; Jianan Li; Jian Zhao; Jiancheng Lv (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Effects of vacuum steam pulsed blanching on bioactive compounds, quality attributes, enzyme activities, and microstructural properties of daylily (Hemerocallis lilioasphodelus L.) - Jun Zhang; Li-Zheng Deng; Wei-Peng Zhang; Ming-Qiang Xu; You-Sheng Shi; Shi-Han Yu; Jing-Shou Zhang; Fan Yang; Shu-Lin Liu; Wei-Qiao Lv; Hong-Wei Xiao (Food Chemistry, 2026)

Unraveling the aromatic essence of baked green tea using sensomics: insights from three representative cultivars - Yan Zhao; Chen-Yang Shao; Han Yan; Yue Zhang; Qun-Hua Peng; Zhi Lin; Xiao-Ting Zhai; Hai-Peng Lv; Yin Zhu (Food Chemistry, 2026)

Predicting heavy metal distribution coefficient in global soil via machine learning: The effect of mineral heterogeneity - Wenping Zuo; Huangling Gu; Qinpeng Liao; Jin Chao; Chongchong Qi; Junqin Liu; Yuancai Lv; Chen Tian; Zhang Lin (Environmental Research, 2026)

Rapid phosphorus adsorption: Polyaluminium chloride (PAC) modified glass pumice (MPAC-G) with exceptional regenerability for low-concentration aquaculture effluents - Junming Li; Jie Yang; Xiangying Wei; Xin Xu; Guifang Yang; Jianhui Huang; Xiuchun Lin; Yuancai Lv; Xiaomei Zhong; Zeyuan Zhao (Environmental Research, 2026)

Enhanced synergistic adsorption and peroxymonosulfate oxidation via interlayer-confined MgFe layered double hydroxide/porous biochar composite for water decontamination - Hongmin Zhang; Yifei Yang; Sirui Chen; Yujing Lin; Yongtao Lv; Huihui Zhang; Licheng Chen; Lei Wang; Xudong Wang (Chemical Engineering Journal, 2026)

A bio-based composite phase-change material composed of pineapple peel and polyethylene glycol for efficient thermal energy storage - Haixuan Liu; Haoxin Lv; Yongshuang Xiao; Jiahui Lin; Yonggang Min; Jintao Huang (Biomass and Bioenergy, 2026)

Assessing the Probiotic Properties and safety of Limosilactobacillus reuteri LP4 Isolated from Apis cerana Based on Whole Genome and Phenotype Analyses - Le Xu; Pingping Fang; Mingkui Lv; Shiyu Chen; Chen Liu; Sifan Wang; Jiqin Li; Kun Dong; Qiuye Lin; Zhenhui Cao (Probiotics and Antimicrobial Proteins, 2026)

Cigarette smoking combines with genetic variants to regulate FOXN3 and associate with bladder cancer risk - Yiwen Zheng; Youhan Wu; Jinyue Zhang; Chenfei Zhao; Tianqin Wang; Qunbo Wang; Qiang Lv; Chao Qin; Lin Yuan; Haiyan Chu; Mulong Du; Meilin Wang; et al. (Archives of Toxicology, 2026)

Spatially differentiated restoration strategies optimize multiple ecosystem functions in tidal marshes after Spartina eradication - Wenzhen Zhao; Shiwei Lin; Xiaolu Yan; Jingqiu Zhong; Lin Su; Shupu Wu; Lv Gong; Yang Hu; Xiuzhen Li (Ocean & Coastal Management, 2026)

The bioaccumulation characteristics and combined toxicity effects of aged microplastics with adsorbed Hg(II) in oysters - Lianghong Li; Chun Lv; Qijia Zhou; Qiaoguo Tan; Haiying Lin; Qingge Feng; Xiaohong Song; Xianghua Wu; Qiuyan Hu; Lixin Huang; Jie He; Guanjian He; et al. (Journal of Hazardous Materials, 2026)

Synergistic enhancement of bisphenol A photodegradation by BiOCl via nitrite-induced charge separation and reactive oxygen species generation: A dual role for nitrite in pollutant degradation and transformation - Zengkai Fu; Zili Lin; Junle Jian; Siling Zhang; Fengyuan Zhang; Yanfang Wang; Yunshuang He; Linsheng Liu; Yishun Wang; Hongda Zhan; Zheng Hu; Ping Chen; et al. (Journal of Environmental Chemical Engineering, 2026)

Towards High spatial resolution and fine-grained fidelity depth reconstruction of single-photon LiDAR with context-aware spatiotemporal modeling - Zhenyu Zhang; Yuan Li; Feihu Zhu; Yuechao Ma; Junying Lv; Qian Sun; Lin Li; Wuming Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Milk-derived small extracellular vesicles promote intestinal epithelial and immune development in suckling mice - Zenghui Xia; Yujia Luo; Peng Xue; Yingying Lin; Jian He; Yafei Zhang; Yao Lu; Xi Lv; Huiyuan Guo (Food Research International, 2026)

Lactoferrin-quercetin synergy: Mechanistic analysis and functional optimization of high internal phase emulsions for 3D food printing with bioactive delivery capabilities - Yanpei Huang; Conghui Lang; Kang Lin; Weijun Chen; Wenxue Chen; Qiuping Zhong; Jianfei Pei; Ying Lv; Rongrong He; Ming Zhang; Haiming Chen (Food Hydrocolloids, 2026)

Two birds with one stone: Constructing confined N-doped carbon catalysts to boost solar-driven interfacial water evaporation and peroxymonosulfate mediating antibiotic wastewater purification - Qi-E Zhang; Lin-Bo Deng; Hui-Qing Lv; Guo-Qing Zhao; Yan Pan; Jin Zou; Meng-Ting He; Xun-Kuan Ye; Jin-Gang Yu; Limin Lu (Environmental Research, 2026)

Efficient adsorption of U(VI) from seawater on tannin-immobilized conjugated micro-mesoporous poly(aniline)s - Xiaoying Lin; Bingqing Huang; Yifan Liu; Yuancai Lv; Chunxiang Lin; Jianhui Huang; Minghua Liu; Xiaoxia Ye; Jie Chen (Desalination, 2026)

Water vapor-mediated cellulose skeleton enhances liquid-free ion-conductive elastomers for flexible electronics - Zongming Lv; Hongping Li; Meilin Zhang; Yuanyuan Lao; Lihua Fu; Baofeng Lin; Chuanhui Xu; Bai Huang (Chemical Engineering Journal, 2026)

Synergistic TdT/CbAgo mediated protein-nucleic acid conversion for trace detection of neuron-derived exosomal Aβ42 - Chao Yan; Jiqing Liu; Siwen Lv; Caoyi Duan; Qingxi Wu; Yan Chen; Xiaoming Kong; Lin Huang (Chemical Engineering Journal, 2026)

Investigation of intramolecular split G-quadruplex-hemin systems and development of DNAzyme-based probes - Lu Lin; Mengmeng Lv; Jiangtao Ren; Jin Wang; Erkang Wang (Analytica Chimica Acta, 2026)

Comparative pharmacokinetics of sixteen components following oral administration of raw and processed Viticis Fructus in rats - Zijing Zhang; Kaili Zhang; Wenwen Li; Zhenguo Lv; Lu Chen; Jinyue Ma; Wenhan Lin; Yameng Zhu; Huizi Ouyang; Jun He (Natural Product Research, 2026)

Identification and transcriptomic analysis of a new pathogen, Photobacterium damselae SCXP, associated with sea cucumber skin ulceration syndrome - Linwei Yang; Shuming Liu; Hui Lv; Haiyun Wei; Tong Wu; Bilian Lou; Jingsong Yang; Qingmei Huang; Yuxin Shi; Tongxin Lin; Zhengwei Cui; Xinhua Chen; et al. (Aquaculture, 2026)

Dicyanoisophorone-based near-infrared fluorescent probe with a large Stokes shift for the detection and bioimaging of hydrazine - Hong-Cheng Xia; Yu-Hang Zhang; Li-Ming Lv; Di Han; Hong-Kun Yang; Hui-Juan Yan; Jie-Li Lv; Jun-Tang Lin; Ying-Ying Kong (Journal of Hazardous Materials, 2026)

Evaluating technical soil derived from lithium mica residue: Integrating soil quality and life cycle assessment for functional performance and environmental sustainability - Yanqi Li; Zi Guo; Xinyan Lv; Xin Liao; Guilan Duan; Liping Fang; Xiaoliang Li; Xiao Tan; Aijun Lin (Journal of Cleaner Production, 2026)

Experimental study of flame height and merging condition of jet fire arrays - Yujie Lin; Yuhang Chen; Guanlin Peng; Chen Kuang; Jiang Lv; Chang Qi; Anfeng Yu; Yi Liu (Fuel, 2026)

Enhancing pearl luster by targeted delivery of astaxanthin using submicron hollow ordered mesoporous silica to the mantle of pearl oysters - Yuan-shuai Fu; Xi-ke Li; Yue Lin; Yun-ao Li; Yong Zhao; Wei-hao Wu; He Wang; Xue-feng Lv; Yuan Zhang; Yong-heng Zhu; Zhi-yi Bai (Chemical Engineering Journal, 2026)

Bright and stable green-emitting quantum dots with universal surface modifiability for diagnostic probes - Ning Li; Dexia Zhou; Ya Liu; Ziming Zhou; Zhaobing Tang; Siqi Jia; Ruili Wu; Huaibin Shen; Yanbing Lv; Lin Song Li (Chemical Engineering Journal, 2026)

Three eagles with one arrow: Multimode and dynamic luminescence from single non-conjugated polymer system induced by aromatic β-diketone - Wei Lv; Jingwen Han; Fan Wu; Shuaiqi Wang; Meijuan Lin; Qidan Ling; Zhenghuan Lin (Chemical Engineering Journal, 2026)

A novel combined Enzymatic-Thermal hydrolysis process for mass reduction and resource recovery from waste activated sludge - Lin Li; Heyuan Lv; Lequn Qu; Xueqing Shi (Bioresource Technology, 2026)

Deciphering Ferroptosis-Related Astrocyte Subpopulations and Diagnostic Biomarkers in Parkinson’s Disease through RNA Transcriptomics - Zhongying Gong; Dan Guo; Yufeng Lin; Zhiwei Liu; Mengdi Lv; Xinxin Liu; Mingshuo Sun; Linlin Wang; Tianman Zhao; Zhiyun Wang; Xue Xue (Molecular Neurobiology, 2026)

Fluvoxamine Attenuates Blood–Brain Barrier Disruption in Drug-Resistance Epilepsy and inhibits Ferroptosis via the Sigma-1 Receptor-TAMM41 signaling in bEnd.3 cells - Lin Guo; Siyu Liu; Na Lv; Jianlun Ji; Xinting Lin; Ying Ke; Zhidong Liu; Congcong Sun; Yun Wang (Molecular Neurobiology, 2026)

One-pot fabrication of highly stable and luminescent InP quantum dots nanobeads through multifunctional polymer encapsulation for lateral flow immunoassay - Xinxin Chen; Qingbiao Zheng; Xiaoquan Li; Li Wang; Lifang Zhang; Yuxin Zhang; Lei Wang; Yanbing Lv; Lin Song Li; Ruili Wu (Analytica Chimica Acta, 2026)

Unraveling the Tectonic Evolution of the Eastern Jiangnan Orogen, South China: Constraints From Basalts of Trace Elements, Nd Isotope, and Geochronology - Jiandong Sun; Xuehui Zhang; Jinsong Lv; Haili Li; Shiru Lin (Island Arc, 2026)
The Jiangnan Orogen has long been recognized as an ideal location for Precambrian geologists to study Neoproterozoic tectonic movements. However, the paleogeographic location of the South China Craton within the Rodinia supercontinent and the associated geodynamic mechanisms remain contentious. This research presents results from Laser Ablation Inductively Coupled Plasma Mass Spectrometry (LA‐ICP‐MS) zircon U–Pb dating, whole‐rock geochemistry, and Nd isotopes of early Neoproterozoic Jinshan basalts from the Zhangcun Formation. The basalts, dated at approximately 844 Ma, display a tholeiitic affinity, characterized by high MgO (8.19–13.70 wt.%), moderate TiO 2 (0.89–1.40 wt.%), and positive ε Nd ( t ) values (+ 1.35 to +3.53). Normalized rare earth element (REE) patterns and primitive mantle‐normalized trace element distributions indicate a slight enrichment of light rare earth elements (LREE) and a significant enrichment of large ionic lithosphere elements (LILEs), comparable to E2 basalts from the East Scotia Ridge back‐arc basin. It is suggested that the Jinshan basalts originated from a slightly depleted asthenospheric mantle, combined with recycled slab melt. When integrated with existing regional data, these basalts from the eastern Jiangnan Orogen exhibit notable geochemical anomalies, including elevated LREE and incompatible element ratios, as well as lower ε Nd ( t ) values, in contrast to back‐arc basin basalts from the central Jiangnan Orogen. This study proposes that the observed geochemical disparities between the eastern and central Jiangnan Orogen are attributed to varying degrees of slab rollback within the Yangtze Block during the early Neoproterozoic. Furthermore, evidence from prolonged arc magmatism and extensional tectonics related to slab rollback supports the conclusion that the South China Craton is positioned at the periphery of the Rodinia supercontinent.

Numerical Simulations of Propulsion Performance of Hull–Propeller–Rudder–Coupled System with Propeller Boss Cap Fins (PBCFs) - Xiaoqing Tian; Haoliang Zhao; Jinliang Ma; Ming Lv; Hooi-Siang Kang; Junting Wang; Huachen Pan; Du Lin; Songkai Ren; Chizhong Wang (Journal of Marine Science and Engineering, 2025)
Ship propulsion performance is important for navigating. This study aims to enhance the propulsion performance of a 9500 DWT ship by integrating PBCFs into the hull–rudder–propeller–coupled system. A total of 27 PBCF models with different fin installation angles, radius ratio, and tilt angles are designed in the study. The computational fluid dynamics method is employed and a propeller open-water test is also performed to optimize the PBCF design, which is integrated into different coupled systems. The numerical results show that the PBCFs exhibit differential enhancements of propeller performance across system configurations with their efficiency changing from 4.05% to 2.87%. Moreover, the reliability of ship self-propulsion simulation is mutually validated through the combined BF (body force) and MRF (multi-reference frame) methods. Then, simulations were conducted using these two methods for the self-propulsion of a 9500 DWT ship at three different speeds. Finally, the results from using the MRF method show that the incorporation of PBCFs can reduce delivered power to propeller by 1.32% at different Fr.

Spatial structure of aquatic communities and dispersal pathway selection: an empirical study based on near-natural mountainous watershed - Yuke Duan; Zongwei Lin; Guohao Liu; Yuanyuan Lv; Yixia Wang; Tatenda Dalu; Naicheng Wu (Environmental Monitoring and Assessment, 2025)

Large-scale analysis of SARS-CoV-2 genomic data from sewage using eVarEPS reveals that amino acid mutations detected in sewage provide an early warning on population prevalence - Ziquan Lv; Chang Shu; Yulin Fu; Yinghui Li; Shisong Fang; Xiangjie Yao; Qinglan Sun; Kesheng Peng; Jian Lu; Guomei Fan; Dongmei Liu; Jinzhen Tang; et al. (Water Research, 2025)

Tunable surface potential nanomaterials for enhanced environmental nucleic acid extraction and surveillance - Jiahui Lv; Tong Li; Ying Liu; Bing Li; Peng Jia; Chuwei Ma; Hongjun Xiao; Guanghui Wang; Li Cheng; Jingkai Yang; Ziyi Xu; Xuan Tan; et al. (Water Research, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Safe sequestration of CO2-carbonated fly ash in coal mine goafs and geomechanical stability analysis of the sequestration formation - Lei Qin; Siheng Lin; Haifei Lin; Shugang Li; Hui Wang; Shiyin Lv (Process Safety and Environmental Protection, 2025)

Preparation of activated carbon/liquid paraffin/metakaolin composite geopolymer microspheres using acid leaching and its removal of ReO4−/TcO4− - Kaituo Wang; Qian Li; Teng Lv; Min Yi; Liu He; Xinpeng Wang; Lin Shao (Journal of Water Process Engineering, 2025)

Land use and economic development influenced the hotspots of groundwater storage gains and losses in mainland China in the past 20 years - Qian Zhang; Shengwei Lv; Shengwei Zhang; Ying Zhou; Xi Lin; Lin Yang; Shuai Wang; Ruishen Li (Journal of Hydrology, 2025)

Monitoring vegetation recovery in abandoned mining areas using Sentinel-2A and UAV data: Evidence from the Hengshanli mine - BoWen Shi; Lv Zhou; Fei Yang; Fan Jiang; Jie Zhang; Xiang Huang; WenGuang Wei; Lin Jiang (Journal of Environmental Management, 2025)

Obstacles and bottleneck breakthroughs affecting the development of hydroxyl radicals assisted chemical mechanical polishing - Xingwang Xu; Bin Lin; Haopeng Chen; Bingrui Lv; Jinming Li; Pengcheng Zhao; Jingguo Zhou; Junqing Jia; Tianyi Sui; Jieqiong Lin (Journal of Environmental Chemical Engineering, 2025)

Glacial-interglacial climate modulates sedimentary sulfur cycling in the Peruvian oxygen minimum zone: Mechanistic insights from pyrite multiple sulfur isotopes - Xiaoxiao Yu; Fang Qian; Xiaomin Lin; Longye Du; Jianghao Bai; Dawei Lv; Yanguang Liu; Gangjian Wei; Mang Lin (Geochimica et Cosmochimica Acta, 2025)

Effect of heavy-duty engines aftertreatment system on particle emission properties above 10 nm - Zuwei Zheng; Sheng Su; Tao Zhou; Tao Lv; Xuteng Zhao; He Lin (Fuel, 2025)

Effects of Hofmeister ions on gel properties and formation mechanism of soybean protein isolate-konjac glucomannan composite gel - Yingying Ma; Fusheng Chen; Dingyang Lv; Fengyan Lin; Shuchao Zhao (Food Research International, 2025)

Insights into anthocyanin stability and infusion color in purple leaf teas driven by co-pigment flavonoid interactions - Gaozhong Yang; Jiqiang Jin; Jufen Mei; Zhi Lin; Jiang Shi; Haipeng Lv (Food Chemistry, 2025)

Astaxanthin enhances broiler health via integrated regulation of antioxidant capacity, immune function, and gut microbiota - Xiao-Ming Gu; Ding-Cheng Ye; Jun-Wei Cheng; Zhi-Xin Lin; Hai-Xuan Lv; Zai-Xing Cai; Yun Yang; Chang-Kang Wang; Yu-Yun Gao; Ling Jin (Food Chemistry, 2025)

Insights into biochemical process and associated microbial mechanisms in the fermentation reactor of side-stream enhanced biological phosphorus removal processes - Lu Qin; Nicholas B. Tooker; Taotao Lv; Kailong Li; Lin Xie; Guangyu Li; Zijian Leo Wang; Annalisa Onnis-Hayden; Hongrui Ma; Dongqi Wang (Chemical Engineering Journal, 2025)

Engineering NK cell membrane-camouflaged copper-BODIPY nanoassembly to synergize dual-phototherapy and cuproptosis for enhanced antitumor immunity - Xuya Yu; Yushi Zhang; Zhuona Rong; Xueping Li; Lingpeng Luo; Lu Zhang; Liyu Sun; Yayue Liu; Wen Li; Lin Mei; Feng Lv; Xiaocong Pang; et al. (Chemical Engineering Journal, 2025)

Substrate-engineered Mo single-atom catalysts for enhanced PMS activation: Selective 1O2 generation toward efficient tetracycline degradation - Boping Xiong; Jingyi Lin; WeiGuang Lv; Boyu Wu; Yue Wang; Peihua Li; Zongyin Song; Kaisheng Zhang; Xingjiu Huang (Chemical Engineering Journal, 2025)

Influence of slope crest soil cracks on water dynamics and gully wall stability under varying rainfall patterns - Maojin Yang; Nanbo Cen; Bangning Zhou; Yihao Lv; Fangshi Jiang; Yanhe Huang; Jinshi Lin; Yue Zhang (CATENA, 2025)

Corrigendum to “Evaluation of bacteriostatic and antioxidant screening of secondary metabolites of endophytic fungi in Lanzhou lily” [Bioresour. Technol. Rep. 32 (2025) 102380] - Xinlan Wang; Bolu Sun; Ying Lv; Miao Zhou; Xuanxiu Da; Jiali Kang; Haiying He; Chenyu Qin; Quhuan Ma; Hongxia Shi; Lin Yang; Xiaofeng Shi (Bioresource Technology Reports, 2025)

Evaluation of bacteriostatic and antioxidant screening of secondary metabolites of endophytic fungi in Lanzhou lily - Xinlan Wang; Bolu Sun; Ying Lv; Miao Zhou; Xuanxiu Da; Jiali Kang; Haiying He; Chenyu Qin; Quhuan Ma; Hongxia Shi; Lin Yang; Xiaofeng Shi (Bioresource Technology Reports, 2025)

Evaluation of Feeding Effect of a New Artificial Diet on Chilo sacchariphagus and Chilo infuscatellus (Lepidoptera: Crambidae), Two Major Stalk Borers on Sugarcane in China - Ji-li Wei; Yong-lin Ma; Cheng-hua Huang; Feng-ying Wang; Qiao-xian Wei; Liu-feng Li; Ren-zhao Liao; Fu Lv; Xue-hong Pan; Xian-kun Shang (Sugar Tech, 2025)

Long Term Rice Cultivation in Saline-Alkaline Soil Improves Phosphorus Availability, Microbial activity, and Reduces P Mass Balance - Qilin Lv; Tairan Zhou; Xuepeng Zhou; Jingbiao Fan; Xueqin Ren; Lin Zhang; Shuwen Hu (Journal of Soil Science and Plant Nutrition, 2025)

Heterogeneity analysis and prognostic model construction of HPV negative oral squamous cell carcinoma T cells using ScRNA-seq and bulk-RNA analysis - Chunyan Li; Zengbo Lv; Chongxin Li; Shixuan Yang; Feineng Liu; Tengfei Zhang; Lin Wang; Wen Zhang; Ruoyu Deng; Guoyu Xu; Huan Luo; Yinhong Zhao; et al. (Functional & Integrative Genomics, 2025)

Histological studies on the ontogeny of the big-belly seahorse (Hippocampus abdominalis) - Yuanyuan Xue; Lu Tang; Chunhui Lv; Fang Wang; Xiaolei Su; Mingzhu Li; Yuping Hou; Jie Dong; Chengde Fan; Jiezhou Wang; Lin Shi; Qunhao Zhou; et al. (Fish Physiology and Biochemistry, 2025)

Fast Forward Modeling of Resistivity Method under Complex Topography Using Finite Element Method - Zhan Wang; Chang-Wei Li; Yu-Zeng Lv; Run-Lin Luo; Bo Cheng; Bo Li (Applied Geophysics, 2025)

Application of Interprofessional Sequential Simulation Teaching Mode in Standardized Training of Radiation Oncology Residents - Hai-Zhen Yi; Xiao guo Cai; Wei Lv; Jin-Jing Chen; Zhan Lin (Journal of Cancer Education, 2025)

Electrostatic spinning technology coupled with traditional pollution control processes: A review - Hanrun Lv; Xuechen Li; Mengjiao Wang; Ruyu Bai; Hongjin Li; Junlang Lao; Mengda Du; Jiaqi Shi; Hanfei Gao; Baorong Duan; Qingjian Zhang; Lin Liu; et al. (Science of The Total Environment, 2025)

Subfunctionalization, neofunctionalization, and nonfunctionalization of the four soybean phytochrome A genes - Lixin Ma; Ting Zhang; Sujun Ye; Wenmin Lin; Yinhua Lv; Wenmin Liu; Fanjiang Kong; Baohui Liu; Yang Tang; Xiaoya Lin (Plant Science, 2025)

Hypoglycemic cucurbitane-type triterpenoids from fruits of Citrullus colocynthis - Hua-Wei Lv; Yu Wan; Wen-Lin Fan; Meng-Di Zhu; Qiao-Liang Wang; Zhong-Bo Zhou; Chang-Chun Chen; Hong Wang; Xing-Nuo Li (Phytochemistry, 2025)

Multi-omics investigation unveils the role of Eurotium cristatum fermentation in potentiating thinned young apple pomace for colitis-induced liver disorders amelioration - Jiayao Lv; Yi Wang; Lanqi Zhou; Shiyi Zhang; Wei Song; Rui Dong; Tianqi Liu; Guoze Wang; Lin Shi (Food Research International, 2025)

Multifaceted characterization of lactoferrin and (−)-epigallocatechin-3-gallate (EGCG) interactions: development of the pickering emulsions for microencapsulated functional foods - Yanpei Huang; Kang Lin; Conghui Lang; Haiming Chen; Wenxue Chen; Qiuping Zhong; Jianfei Pei; Ying Lv; Rongrong He; Ming Zhang; Weijun Chen (Food Research International, 2025)

Key odorants driving aroma transformation during aging process in Liubao tea: A sensory and chemical perspective - Ying Yang; Ruijin Qiu; Qiushuang You; Wanjun Ma; Yuhui Zhang; Yan Zhao; Gaozhong Yang; Yue Zhang; Zhi Lin; Yin Zhu; Haipeng Lv (Food Chemistry, 2025)

Investigation of dietary supplementation with Tricholoma matsutake on immunoregulation: The underlying direct mechanism - Renzhi Lv; Yifei Wang; Qunyan Fan; Zhijie Bao; Songyi Lin (Food Bioscience, 2025)

Isolation of largemouth bass virus (LMBV) and dominant immunogenic epitope screening of the major capsid protein of LMBV - Jie Leng; Ling-Yun Lin; Yun-Yao Tu; Cheng-Ke Zhu; Qun Lu; Ming-Ji Lv; Tao He; Jian-Yong Hu; Zhao-Fang Han; Song Zhu (Fish & Shellfish Immunology, 2025)

Interface engineering of flower-like ZIF-67 derived CoSe2/g-C3N4 heterojunction for efficient immobilization of elemental mercury - Guanjian He; Yujiang Fan; Qiang Niu; Gelimei Zhang; Fenghui Wu; Dandan Chen; Chun Lv; Jie He; Haiying Lin; Minjie He (Chemical Engineering Journal, 2025)

Machine learning-enhanced microfluidic CircRNA detection platform for high-accuracy breast cancer diagnosis - Xinyu Zhang; Zixin Lin; Huanyu Zhou; Qitao Xie; Yuetao Zhang; Yongmei Chen; Zijie Li; Runlin Lv; Zhiqi Li; Rubing Xiong; Xiaman Chen; Yong Xia; et al. (Chemical Engineering Journal, 2025)

TiO₂/MIL-100(Fe) S-scheme heterojunction for efficient photocatalytic inactivation of Microcystis aeruginosa and microcystin degradation - Jie Zhang; Na Lv; Mingcan Wu; Limeng Liu; Ling Fang; Mingyang Ma; Rosaiah Pitcheri; Shu Lin; Kezhen Qi (Chemical Engineering Journal, 2025)

Synergistic spin state and geometry engineering by constructing MoFe diatomic sites to catalyze non-radical and sustained oxidation of water pollutants - Chaofa Chen; Minjia Yan; Yu Li; Feng Chen; Zhangrong Lou; Xingshuai Lv; Xi-Lin Wu (Chemical Engineering Journal, 2025)

Quantifying the contribution of different microenvironments to real-time PM2.5 exposure of rural and urban residents in southwest China - Pingshu Wang; Shaojun Lv; Nan Fu; Nan Lin; Ming Yang; Yunhang Jiang; Yuanchen Chen; Peng Zhang; Wei Du; Bo Pan (Building and Environment, 2025)

Predictors of mortality and progression from colonization to Stenotrophomonas maltophilia bloodstream infection in hematologic disorders: a single-center retrospective study - Hongchen Bi; Qingsong Lin; Qi Sun; Yanxia Lv; Zhiying Tian; Xue Fu; Qiushuang Yan; Yaqing Yu; Hongjing Yao; Fujun Sun; Yonghui Xia; Aiming Pang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

The impact of different Spartina alterniflora eradication strategies on the biological community - Lv Gong; Yuanhao Song; Wenzhen Zhao; Lin Su; Tianyou Li; Yang Hu; Ben Li; Xiuzhen Li (Marine Pollution Bulletin, 2025)

Bridging blue carbon and carbon markets: An interdisciplinary analysis of research and technology for climate mitigation - Nihed Benani; Pingjian Yang; Nicholas Miwornunyuie; Tao Wang; Dan Wu; Faming Wang; Jian lin Chen; Shuguo Lv; Guozhu Mao (Ocean & Coastal Management, 2025)

Association of urinary phthalate metabolites and polycystic ovary syndrome in women undergoing in vitro fertilization - Wenjie Zhou; Shuifang Lei; Hong Lv; Yangqian Jiang; Tianyu Sun; Yanjie Zhang; Hongxia Ma; Jie Wu; Yuan Lin (Reproductive Toxicology, 2025)

Spatio-temporal distribution characteristics and sources of organic carbon in a typical mariculture Bay: A case study of Sansha Bay, China - Xiaolong Lv; Lingyi Lei; Feipeng Wang; Rongmao Li; Cong Li; Hua Lin; Zhi Zhang; Jingli Mu (Marine Environmental Research, 2025)

Efficient utilization of low-grade ilmenite: An innovative approach integrating pre-oxidation with CH₄-H₂ direct reduction for titanium carbide production - Tingting Lv; Jianwei Song; Yunfei An; Tu Hu; Guo Lin; Baocheng Zhou (Journal of Environmental Chemical Engineering, 2025)

The synergistic performance and mechanism of coal dust suppression contributed by Bacillus pasteurii assisted with a potent indigenous Lysinibacilus MN-5 - Gang Zhou; Yixin Xu; Wenqi Shao; Xueqiang Lv; Yongguang Lan; Xianchao Jia; Jintuo Zhu; Guochao Yan; Jianmin Bai; Lin Li (Journal of Environmental Chemical Engineering, 2025)

Unexpected high prevalence of carbapenemase-producing bacteria and widely spread of blaNDM-1-positive Shewanella spp. in retail shrimp - Chao Yue; Xun Gao; Ludan Xiao; Litao Lu; Jiakuo Chen; Caiying Lin; Zhongpeng Cai; Guolong Gao; Luchao Lv; Jian-Hua Liu; Yi-Yun Liu (International Journal of Food Microbiology, 2025)

Effect of low-energy stirring temperature on the formation of oil-in-water emulsions stabilized by gelatin-arginine complexes - Jun Qi; Yu-cong Li; Hui-min Yan; Li-ting Zeng; Ao-jing Lv; Rui-ling Dong; Xue-qing Li; Zhou Lin; Le-le Shao; Lang Zhang; Guo-qing Duan; Chun-hui Zhang; et al. (Food Research International, 2025)

Phosphorus nutrition modulates DEHP uptake, translocation, and metabolism in tomato seedlings - Fuying Zhang; Chaoba Lin; Ruiqing Fan; Yajing Ma; Guohan Wu; Yujiao Song; Xutong Pang; Xuezhu Zhu; Baitao Lv (Environmental Pollution, 2025)

Target-tailored PAN membrane for synchronous removal of emulsions and trace Hg(II) from complex aqueous systems: performance and interfacial mechanism study - Jie He; Haiying Lin; Qingge Feng; Xianghua Wu; Jiatong Lv; Qiuyan Hu; Lixin Huang; Guanjian He; Yujiang Fan; Chun Lv (Chemical Engineering Journal, 2025)

Differential electric field homogenization postponed dendrite formation of zinc anodes at limiting current for long-life aqueous zinc batteries - Yin Yang; Xin Chen; Jingying Li; Jia Yao; Yi Gan; Junjie Zheng; Luyang Ge; Lin Lv; Li Tao; Jun Zhang; Hanbin Wang; Hao Wang; et al. (Chemical Engineering Journal, 2025)

In-situ upcycling of severely deteriorated LixCoO₂ cathodes into high-voltage-tolerant counterparts - Bingjie Yue; Xiaowei Lv; Xiaodong Zhang; Jiao Lin; Renjie Chen; Feng Wu; Li Li (Chemical Engineering Journal, 2025)

Interfacial charge transfer in Ti3C2O2/NLCOF heterojunction enables efficient photocatalytic H2O2 production - Na Lv; Shu Lin; Lan Ding; Kezhen Qi; Weibin Zhang; Vadim Popkov (Chemical Engineering Journal, 2025)

Self-healing and thickness-insensitive perylene diimide-based cathode interfacial layers for organic solar cells - Wei Chen; Dan Zhou; Lin Hu; Jiangang Ma; Guobin Shen; Wentian Wan; Shuhua Wang; Fang Wang; Ruizhi Lv; Bin Hu; Haitao Xu; Zaifang Li; et al. (Chemical Engineering Journal, 2025)

Gestational Multi-metal Exposure in Relation to Anthropometric Birth Outcomes and Maternal Hormonal Profiles: A Deeper Insight Into Sex-Specific and Trimester-Specific Influences - Jinfeng Fu; Zhanlu Lv; Wenchao Zhu; Sisi Yu; Bingjun Lu; Xulong Chen; Chiqun Shan; Yuli Lin; Zhihong Huang; Yao Yao; Shaoyou Lu (Exposure and Health, 2025)

Adaptive evolution, expression, and functional analysis of Hyou1 gene in response to hypoxic stress in razor clam (Sinonovacula constricta) - Ran Sun; Zhihua Lin; Hanhan Yao; Liyuan Lv; Yinghui Dong (Aquaculture International, 2025)

The molecular mechanisms and therapeutic implications of PANoptosis in ischemic diseases - Jiangpeng Wu; Xunkai Wang; Jin Peng; Jinxi Liang; Jun Lv; Lin Huang; Shenmei Wu; Chen Yao; Guiyun Jin; Tang Deng (Apoptosis, 2025)

Axial enhancement on non-radicals generation in PMS activation process mediated with Co single-atom catalyst encapsulated nanoparticles - Yihui Hu; Hong Guo; Yuancai Lv; Chen Tian; Yinling Lin; Hui Liu (Journal of Hazardous Materials, 2025)

Aerosol sampling-based infection risk model for spatiotemporal resolution informed evaluation of on-site transmission risk - Han Gao; Weihao Li; Mengqing Cheng; Danting Luo; Manman Lv; Haotian Yu; Yemin Han; Weiming Lin; Yan Huang; Dianhuai Meng; Tian Weng; Qiang Zhang; et al. (Journal of Hazardous Materials, 2025)

Impact of small hydropower plants on microbial community structure and functions in benthic biofilms - Huimin Gao; Xinxin Qi; Zongwei Lin; Mali Li; Guohao Liu; Yuanyuan Lv; Sangar Khan; Naicheng Wu (Journal of Environmental Management, 2025)

Damage and acoustic characteristics of water-saturated coals with different ranks under liquid nitrogen freezing and thawing treatments - Lei Qin; Jiawei Li; Haifei Lin; Shugang Li; Miao Mu; Shiyin Lv; Niandong Chen (Geomechanics for Energy and the Environment, 2025)

Metal-organic framework UiO-66-NH2 functionalized polydopamine-modified magnetic multi-walled carbon nanotubes for convenient magnetic solid-phase extraction of sixteen quinolones - Lin Lv; Hongmei Liu; Lei Wang; Sikai Wang; Yue Li; Guoqi Zhang; Yan Zhao (Food Chemistry, 2025)

Controlled release of caffeine from oat globulin nanocomplexes: Biocompatibility and gastrointestinal dynamics - Junyu Lin; Hanhan Liu; Jianyu Yang; Yang Gao; Guanghua Zhao; Chenyan Lv (Food Chemistry, 2025)

Research on the mechanism of flumequine degradation by ultraviolet light activated trichloroisocyanuric acid - Yue Yang; Zihong Xu; Zhenjun Xiao; Jin Luo; Yaoguang Wu; Zili Lin; Ping Chen; Wenying Lv; Guoguang Liu (Environmental Research, 2025)

Long-term simulation of saltmarsh landscape based on hydro-sediment and vegetation Dynamics: Assessing future stability - Feng Luo; Hongbo Wu; Zhipeng Chen; Jinhai Zheng; Aifeng Tao; Hongping Zhao; Yongfu Dong; Lin Lv (Estuarine, Coastal and Shelf Science, 2025)

Elucidating the photodesorption mechanism of sulfamethoxazole on novel photo-responsive copper-phenylacetylide: Cleavage of π-π interactions and Cu O bonds - Rong Chen; Zhenjun Xiao; Zili Lin; Yishun Wang; Yu Chen; Ping Chen; Wenying Lv; Guoguang Liu (Chemical Engineering Journal, 2025)

Screening of biocontrol agents against lily bulb rot caused by F. oxysporum and research on their fermentation process - Bolu Sun; Xinlan Wang; Ying Lv; Xuanxiu Da; Miao Zhou; Jiali Kang; Haiying He; Chenyu Qin; Xiangdong Wang; Lin Yang; Quhuan Ma; Hongxia Shi; et al. (Bioresource Technology Reports, 2025)

Evaluation of carbon flux responses to physical and chemical control strategies of Spartina alterniflora in the Yangtze River Delta - Lv Gong; Yuanhao Song; Wenzhen Zhao; Lin Su; Shupu Wu; Yang Hu; Ben Li; Xiuzhen Li (Plant and Soil, 2025)

One-step synthesis of CdS-CeO2/sepiolite and its efficient removal of Rhodamine B by synergistic adsorption and photocatalysis - Yan Zhang; Xinhui Huang; Yaxue Zhang; Letian Lv; Chengyuan Su; Shu Gao; Zhi Huang; Menglin Chen; Xianfeng Lin (Applied Clay Science, 2025)

Turn-on fluorometric and colorimetric dual-mode assay based on the in situ formation of silicon nanoparticles for the determination of β-galactosidase - Sikai Wang; Weiping Liu; Lei Wang; Lin Lv; Yuanyuan Zhang; Yan Zhao (Analytica Chimica Acta, 2025)

Evaluation of NLLoc positioning method and seismogenic structure analysis of Luanzhou MS 4.3 earthquake - Yang Zhang; Xiao-Shan Wang; Ting Chen; Guo-Jun Lv; Hai-lin Yu; Jun-lin Chen (Applied Geophysics, 2025)

Environmental Features of Heavy Precipitation Under Favorable Synoptic Patterns: A Lesson from the 2021 Henan Extreme Precipitation Event - Nan Lv; Zhongxi Lin; Ji Nie; Zhiyong Meng; Ping Lu (Advances in Atmospheric Sciences, 2025)

Mangrove Transplantation to the North: Carbon Sequestration Capacity—Drivers and Strategies - Kewei Zhou; Yujuan Lv; Yang Gong; Jing Su; Lei Wang; Shengmin Wu; Xi Lin; Qiuying Lai; Yixin Xu; Xingyi Duan (Journal of Marine Science and Engineering, 2025)
Mangroves play a pivotal role in carbon sequestration. To investigate the characteristics and driving factors of carbon sequestration in planted mangrove forests, we focused on planted mangrove forests in Wenzhou City, Zhejiang Province, China. Through a statistical analysis of soil physicochemical properties and plant morphological characteristics, we assessed carbon stock distribution patterns and identified key influencing factors, providing scientific support for the northward expansion of mangroves. The results demonstrated significant differences in soil properties and plant morphological characteristics among different stands (p

Host-mediated environmental microbiome recruitment by black soldier fly (Hermetia illucens) enhances waste biotransformation - Zhe Li; Yuchen Zhou; Lin Lv; Yinguang Long; Mengyao Dong; Qi Xiao; Xianyue Jia; Dechen Ju; Xiaowen Sun; Feng Huang; Minmin Cai; Jibin Zhang; et al. (Waste Management, 2025)

Superconducting phase interference effect in momentum space - Bo Zhan; Qiang Gao; Runze Chi; Yiwen Chen; Lin Zhao; Dingshun Lv; Xingjiang Zhou; Tao Xiang (Science Bulletin, 2025)

Catalytic mechanism of yavapaiite confined in interlayer space of graphite oxide in heterogeneous electro-Fenton oxidation - Shaoyan Lv; Li Cai; Hao Zhang; Jun Lu; Jinglian Wu; Liying Xu; Lin Xu; Quanyuan Chen (Journal of Environmental Management, 2025)

Water availability and hydrological connectivity mediate the responses of alpine soil prokaryotes to temperature changes at the watershed scale - Wencong Lv; Liyuan Ma; Jianqing Du; Li Tang; Biao Zhang; Danhong Chen; Qiang Liu; Shutong Zhou; Zhe Pang; Lin Chen; Yanbin Hao; Kai Xue; et al. (Journal of Environmental Management, 2025)

Preparation of composite microbial dust suppressant using PVA as spore carrier and modified carboxymethyl cellulose sodium as wall material - Gang Zhou; Yinghui Lv; Zhenquan Wei; Hongze Xu; Lin Li; Bo Wei; Lianjie Zhu; Qunzhi Meng (Journal of Environmental Chemical Engineering, 2025)

Unique Chain-Growth and oxygen removal mechanisms in Fischer-Tropsch synthesis on the ε-Fe2C (1–21) Surface: Insights from DFT calculations and microkinetic modeling - Huabo Zhao; Quan Lin; Hong Jiang; Yijun Lv; Zhuowu Men (Fuel, 2025)

NaOH-assisted heat curing towards highly permeable, superior selective, and antifouling TFC nanofiltration membranes - Weiwei Huang; Xiaozhen Lu; Wenzong Zhou; Weiwei Lv; Quan Yuan; Hang Yang; Xinwei Kang; Daoji Wu; Lin Wang; Xuewu Zhu (Desalination, 2025)

Convertible-dielectric triboelectric nanogenerator for chaotic water-current energy harvesting - Fei Zhang; Hao Li; Pengfei Ji; Xiaobo Gao; Shengbo Wang; Huisheng Cai; Kai Lv; Zijie Xu; Zhong Lin Wang; Baodong Chen (Chemical Engineering Journal, 2025)

Interface molecular reconstruction with scarcity active factor for long-life aqueous zinc batteries at thermal environment - Xin Chen; Yin Yang; Runzhi Liang; Junjie Zheng; Jia Yao; Jingying Li; Yi Gan; Xin Liu; Xiaodong Liang; Ze Wang; Qin Liu; Lin Lv; et al. (Chemical Engineering Journal, 2025)

Magnetically-driven Dual-channel Fluorescent Biosensor with Aptamer Logic Gates for Multiplexed Exosomal Protein Profiling and Breast Cancer Subtyping - Yanqiu Wu; Lin Chen; Yao Tong; Changsheng Zhai; Guiyong Xiao; Yupeng Lv; Lutao Du; Juan Li; Peng Ren; Yanyan Jiang (Chemical Engineering Journal, 2025)

Micropatterned piezoelectric films induced by modulated corona field for weak signal detection - Fu Lv; Chenghang Yu; Bing Liu; Jiamin Lin; Zijian Hong; Yongjun Wu; Zhaohui Ren; Qilong Zhang; Shurong Dong; Jikui Luo; Juan Li; Yuhui Huang (Chemical Engineering Journal, 2025)

Benzo(a)pyrene-loaded gypsum dust-induced apoptosis of human bronchial epithelial cells through the Ahr signaling pathway - Yujun Wang; Juan Song; Qingqing Lin; Zhenzhen Lv; Faqin Dong; Jianjun Deng (Molecular & Cellular Toxicology, 2025)

Binding modes and in vitro digestion profiles of an iron-binding peptide (EEEWDRE) derived from fermented scallop skirts - Xu Yan; Ying Yue; Bingrui Guo; Jing Lv; Yiwei Dai; Yingxi Chen; Chaofan Ji; Sufang Zhang; Beiwei Zhu; Xinping Lin (Food Chemistry, 2025)

Effects of ultrasound combined with κ-carrageenan on the rheological behaviours, textural properties and microstructures of meat batters before and after heating treatment - Shiwen Lin; Xin Li; Hong Lv; Baohua Kong; Chuanai Cao; Fangda Sun; Qian Liu; Xinning Huang (Food Hydrocolloids, 2025)

Characteristics of microbial carbon pump in the sediment of kelp aquaculture zone and its contribution to recalcitrant dissolved organic carbon turnover: insights into metabolic patterns and ecological functions - Jun-Yang Ma; Ji-Hua Liu; Cheng-Zhuang Chen; Yi-Ze Zhang; Zhan-Sheng Guo; Min-Peng Song; Feng Jiang; Zi-Tong Chai; Zhu Li; Su-Xian Lv; Yu-Jiao Zhen; Lu Wang; et al. (Environmental Research, 2025)

Ecological connectivity between mangroves and seagrasses increases sediment blue carbon storage - Xinao Guo; Shanshan Song; Lieyi Chen; Conghe Zhang; Shengbin Ye; Yali Ding; Ruikun Gou; Xiaoping Huang; Shuguo Lv; Neil Saintilan; Daniel A. Friess; Guanghui Lin (Estuarine, Coastal and Shelf Science, 2025)

CRISPR/Cas9-mediated genome editing in Ganoderma lucidum: recent advances and biotechnological opportunities - Dongmei Lv; Yan Xu; Zi-Xu Wang; Qi-Lin Zhang; Jin-Ping Yan; Jun-Wei Xu (World Journal of Microbiology and Biotechnology, 2025)

Rice cultivation in saline-alkaline soil shifts the coupling of phosphorus functional genes and salt tolerance genes based on metagenomic analysis - Qilin Lv; Jingbiao Fan; Tairan Zhou; Xiaocheng Pan; Huixian Li; Xueqin Ren; Lin Zhang; Shuwen Hu (Applied Soil Ecology, 2025)

The Interplay Between Climate Warming Driven by Greenhouse Gas Emissions and the Ecotoxicological Effects of Microplastics: Insights From a Meta‐Analysis - Xinyan Lv; Aijun Lin; Xuedan Cui; Yanqi Li; Zi Guo; Xiao Tan; Guilan Duan (Global Change Biology, 2025)
An increasing number of studies have revealed the interconnections and interactions between global warming and microplastics. However, research in this field is still in its early stages, with fragmented content and inconsistent conclusions. Therefore, this paper adopts a meta‐analysis method to summarize and analyze the relevant literature in this area. After screening, a total of 39 research papers and 730 data points related to the interactions between global warming and microplastic pollution were obtained. The research results indicate that, on one hand, soil microplastic pollution significantly increases greenhouse gas CO 2 emissions by 140.20%, N 2 O emissions by 195.27%, and Global Warming Potential by 172.10%, thereby exacerbating global warming. By introducing explanatory variables for analysis, it was found that microplastic type, soil type, and soil dissolved organic carbon are important influencing factors. On the other hand, the study also explains that the rise in water temperature due to global warming amplifies the biological toxicity effects of microplastics, leading to oxidative damage and poisoning in aquatic animals. The bidirectional interaction mechanism between microplastic pollution and global warming may form a vicious cycle, further increasing the vulnerability of ecosystems. This study provides a theoretical basis and research direction for addressing the dual threats of microplastic pollution and global warming.

SIRT1 Regulates Iron Metabolism to Attenuate β-Cell Dedifferentiation by Inhibiting FoxO1 Acetylation - Tingting Li; Rulin Ma; Wennv Tang; Yanxia Zheng; Siyi Lv; Yuxi Liu; Lin Wang; Yusong Ding (Biological Trace Element Research, 2025)

Ignition, combustion and pollutant emissions characteristics of excavated waste in low oxygen concentration and O2/CO2 atmosphere - Jingwen Lv; Beibei Yan; Shengquan Zhou; Zhaoting Wu; Xiaoyun Liu; Sensen Lu; Xiaochao Zhu; Yunan Sun; Jian Li; Fawei Lin; Guanyi Chen (Waste Management, 2025)

Low-dose tire wear chemical 6PPD-Q exposure elicit fatty liver via promoting fatty acid biosynthesis in ICR mice - Lili Wang; Weitian Tang; Nan Sun; Jia Lv; Jiayue Hu; Lin Tao; Cheng Zhang; Hua Wang; Li Chen; De-Xiang Xu; Yihao Zhang; Yichao Huang (Journal of Hazardous Materials, 2025)

Production of C12A7 through co-recycling of secondary aluminum ash and MSWI fly ash by a hydrothermal-calcination method with lower energy consumption than the direct calcination - Lin Xu; YeJia Lv; Wanyu Fang; Zihao Feng; Jia Zhang; Guangren Qian (Journal of Environmental Chemical Engineering, 2025)

Application of gravity gradient measurement in the detection of urban underground space - Zhong-kun Qiao; Jia-jun Zhang; Peng Yuan; Lin-ling Li; Ruo Hu; Hai-xiang Yang; Kan-xing Weng; Zong-yu Zhang; Lin-fei Wang; Pei Qin; Liang-liang Hao; Chuan Yang; et al. (Journal of Applied Geophysics, 2025)

Two new species of the planthopper genus Pitambara Distant, 1906 (Hemiptera, Fulgoromorpha, Lophopidae) from Yunnan Province of China - Shasha Lv; Lin Yang; Yubo Zhang; Xiangsheng Chen (Journal of Asia-Pacific Entomology, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Freestanding vanadium oxides/carbon hybrid cathode with long-term cyclability at low current density for flexible aqueous zinc ion batteries - Zhouyang Qin; Gaoxu Han; Yilin Yang; Shengle Hao; Lingxiao Yu; Yuxiao Lin; Yunsong Li; Ruitao Lv; Wanci Shen; Feiyu Kang; Zheng-Hong Huang (Chemical Engineering Journal, 2025)

Integrative analysis based on CRISPR screen identifies apilimod as a potential therapeutic agent for cisplatin-induced acute kidney injury treatment - Yunpeng Chu; Muyun Wei; Zhongyu Cao; Luan Chen; Jie Tan; Wei Bao; Fan Yang; Yingtian Zhang; Yunxiao Lin; Yutong Zhang; Shiyi Li; Cai Lv; et al. (Science China Life Sciences, 2025)

Graph Neural Networks and Multimodal DTI Features for Schizophrenia Classification: Insights from Brain Network Analysis and Gene Expression - Jingjing Gao; Heping Tang; Zhengning Wang; Yanling Li; Na Luo; Ming Song; Sangma Xie; Weiyang Shi; Hao Yan; Lin Lu; Jun Yan; Peng Li; et al. (Neuroscience Bulletin, 2025)

Chrysoeriol: a natural RANKL inhibitor targeting osteoclastogenesis and ROS regulation for osteoporosis therapy - Hao Luo; Sijian Lin; Hao Lv; Wen Tan; Junlong Zhong; Jiachao Xiong; ZhiMing Liu; Qin Wu; Ming Chen; Kai Cao (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

The Impact of Standardized Training Resident on Pain Management in Patients with Advanced Lung Cancer - Hai-Zhen Yi; Wei Lv; Jin-Jing Chen; Zhan Lin (Journal of Cancer Education, 2025)

Rational design and pairing of single-domain antibodies for developing rapid detection methods for botulinum neurotoxins A and B - Ruomei Lv; Jiaxin Li; Xinyu Fang; Li Tang; Rui Shi; Jin Wang; Wenjing Zhang; Jinglin Wang; Guangyu Zhao; Jing Wang; Shan Gao; Xuefang Xu; et al. (Analytica Chimica Acta, 2025)

Triflumezopyrim-induced changes in the flight ability and energy metabolism of the brown planthopper, Nilaparvata lugens - Jitong Li; Lei Zhu; Xinyi Lv; Xin Zhou; Xinyan Liang; Yiping Wang; Lin Chen; Jinglan Liu (Pesticide Biochemistry and Physiology, 2025)

Exploring the use of bacillomycin D to control citrus sour rot caused by Geotrichum citri-aurantii - Shiquan Qian; Xinrong Zhou; Lin lv; Qi Sun; Xinran Cheng; Qian Xie; Yanrui Chai; Enjie Diao (Journal of Stored Products Research, 2025)

Digestibility modulating and 3D printing of gliadin/resveratrol nanoparticle-filled starch gels - Wen Lv; Lin Zhang; Mengyuan Zhang; Xuanbo Liu; Yibin Zhou; Yongquan Wang (Food Chemistry, 2025)

Reduction-stabilization characteristics, long-term stability and biotoxicity evaluation of Fe(II)/Al layered double hydroxides on Cr(VI) in contaminated soil - Xiao Tan; Qi Liu; YanQi Li; Xinyan Lv; Zi Guo; Guilan Duan; Aijun Lin (Environmental Pollution, 2025)

Treatment of atherosclerosis by biomimetic responsive-targeting hybrid nanoparticles enabled by genetically engineering cell membranes and nucleic acid nanostructures for atorvastatin delivery - Tianyu Chen; Weitong Lv; Mengxi Yang; Yuhuan Jiang; Dexuan Xiao; Xin Qin; Qiang Sun; Yunfeng Lin (Chemical Engineering Journal, 2025)

Microbial traits affect soil organic carbon stability in degraded Moso bamboo forests - Xiaoping Tang; Shaofeng Lv; Tongying Wang; Xin Chen; Taoran Sun; Yiyun Xia; Ning Yuan; Yufeng Zhou; Guomo Zhou; Yongjun Shi; Lin Xu (Plant and Soil, 2025)

The association between anti-inflammatory therapies and renal outcomes in patients with established cardiovascular disease or high cardiovascular risks: a meta-analysis of randomised controlled trials - Wenfeng Yang; Zonglin Li; Chu Lin; Xiaoling Cai; Fang Lv; Wenjia Yang; Linong Ji (Inflammopharmacology, 2025)

DNA nanowires-mediated high sensitive quantum dot-fluorescence-linked immunoassay for proteins analysis - Huanhuan Xing; Xiaojing Xing; Fangfang Chen; Ning Li; Dangdang Xu; Ruili Wu; Yanbing Lv; Lin Song Li (Analytica Chimica Acta, 2025)

Identification of a novel strain of carp edema virus affecting Songpu mirror carp in Liaoning, China - Wen Shi; Bing Han; Huilin He; Ruixue Feng; Siyi Guo; Xuanyu Ren; Jinshan Huang; Xu Lin; Jiyuan Yin; Xiaonan Lv; Min Liu (Aquaculture, 2025)

Multiple electron transfer processes facilitate the simultaneous removal of NO3−-N and Cr(VI) in a pyrrhotite-based mixotrophic constructed wetland - Yue Lin; Hua Lin; Minmin Jiang; Jiang Lv; Xuehong Zhang; Jun Yan (Journal of Water Process Engineering, 2025)

Disinfection efficacy of peroxyacetic acid against bacterial spores - Le Yuan; Weishi Lin; Yue Cao; Junping Lv; Siqi Chao; Yulei Liu; Jun Ma; Jinpeng Guo; Yuehua Ke; Lu Wang; Jinfeng Tie (Journal of Hazardous Materials, 2025)

Process optimization and mechanism for removal of chlorine from ultrasonic-enhanced Municipal Solid Waste Incineration fly ash water washing - Shunda Lin; Lijuan Sun; Zeinab Khalid; Guojun Lv; Xuguang Jiang; Jianhua Yan (Journal of Environmental Chemical Engineering, 2025)

Degradation of phoxim by ultrasonic assisted calcium sulfite activated persulfate: Kinetics and mechanisms insights - Zhenjun Xiao; Junlong Zhang; Yijie Lin; Kaixuan Zheng; Zili Lin; Mengyang Niu; Wanlin Lin; Yuchun Hong; Zhongyang Li; Ping Chen; Qingbin Song; Wenying Lv; et al. (Journal of Environmental Chemical Engineering, 2025)

Insights into potential flavor-active peptides and taste-related compounds in Longjing teas: A comparative study of ‘Longjing 43’ and ‘Qunti’ cultivars - Kangni Yan; Jiatong Wang; Mengxue Zhou; Qunhua Peng; Abdelkader Bassiony Mahmoud; Xue Bai; Susanne Baldermann; Xinbing Jiang; Shan Feng; Yan Wu; Jianyu Fu; Zhi Lin; et al. (Food Chemistry, 2025)

Effects of static magnetic field treatment on the digestive, structural and physicochemical characteristics of germinated corn starch - Xin Jiang; Fangzhu Zheng; Jiankun Yu; Pengwen Lv; He Ban; Huimin Liu; Dan Cai; Lin Xiu; Jingsheng Liu (Food Chemistry, 2025)

Perylene diimide cathode interface layer with siloxane bay-modification for efficient and stable organic solar cells - Dan Zhou; Yujie Pu; Yanyan Wang; Lin Hu; Jianwei Quan; Senmei Lan; Jiangang Ma; Fang Wang; Wentian Wan; Yongfen Tong; Ruizhi Lv; Haitao Xu; et al. (Chemical Engineering Journal, 2025)

Rice-fish co-culture promotes multiple ecosystem services supporting increased yields - Shuang-Xi Li; Jian Jiang; Wei-Guang Lv; Evan Siemann; Ben A. Woodcock; Yu-Quan Wang; Andrea Cavalieri; Na-Ling Bai; Juan-Qin Zhang; Xian-Qing Zheng; Han-Lin Zhang; Hai-Yun Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Correlation between cardiac response and ammonia nitrogen of the razor clam (Sinonovacula constricta) - Gaigai Sun; Liyuan Lv; Hanhan Yao; Zhihua Lin; Nianjun Xu; Yinghui Dong (Aquaculture, 2025)

Efficient removal of p-arsanilic acid using a waste-derived collagen fiber-Zr composite membrane - Xiaoxia Ye; Jian Huang; Yuqing Zhang; Yi Lin; Yuancai Lv; Chunxiang Lin; Liang Song; Guifang Yang; Minghua Liu (Journal of Water Process Engineering, 2025)

Microplastic types dominate the effects of bismuth oxide semi-conductor nanoparticles on their transport in saturated quartz sand - Lin Xu; Shaoyan Lv; Quanyuan Chen; Pin Gao; Genyao Gu; Yongxia Wang; Xiaopeng Min; Hyunjung Kim; Li Cai (Journal of Hazardous Materials, 2025)

Chronic exposure to liquid crystal monomer EBCN at environmentally relevant concentrations induces testicular dysfunction via the gut-testis axis - Jun Wu; Daojun Lv; Wanmei Lin; Yiyou Mao; Yanqing Xia; Leilei Feng; Tianxin Zhao; Xiangming Mao; Fangpeng Shu; Haibin Guo (Journal of Hazardous Materials, 2025)

Activation of persulfates on carbon nanotubes for water decontamination: Is the non-radical process consistently considered across different pH levels? - Jiali Peng; Lun Li; Shihuai Deng; Hongyu Zhou; Yanjun Li; Chenye Fu; Long Lin; Yue Yuan; Wei Wei; Guochun Lv; Gang Yang; Xiaohui Lu; et al. (Journal of Hazardous Materials, 2025)

Performance of electro-assisted ecological floating bed in antibiotics and conventional pollutants degradation: Mechanisms and microbial response - Liangjing Zhang; Yan Luo; Shucong Lv; Yunlong Liu; Rui Wang; Yu Wang; Kuixuan Lin; Lusan Liu (Journal of Environmental Management, 2025)

Another inner truth of shaking: Water migration and transformation-advanced physicochemical alterations in tea leaves - Zhilong Hao; Jinyuan Wang; Jiayun Zhuang; Xinyu Feng; Helin Lv; Jiao Feng; Shuping Ye; Weisu Tian; Guanjun Pan; Ping Chen; Hongzheng Lin; Qiang Chu (Food Chemistry, 2025)

Low-dose bisphenol AF exerts slight effects on glycolipid metabolism but causes metabolic disorders under the stress of Western diet in mice - Chengzhe Guo; Lin Lv; Xuanyue Chen; Hanzhang Wang; Shilin Song; Yuanyuan Li; Zhanfen Qin (Environmental Pollution, 2025)

Carbon dots recovery from waste streams of hydrothermal process - Lin Zhang; Jing Zhang; Siyu Zhao; Chao Feng; Yanan Lv; Zicong Wei; Peitao Zhao; Xueping Song (Biomass and Bioenergy, 2025)

Integrative analysis of the ABC gene family in sorghum revealed SbABCB11 participating in translocation of cadmium from roots to shoots - Bo Zhang; Weitao Jia; Kangqi Lin; Sulian Lv; Zijing Guo; Wenzhu Xie; Yingjiao He; Yinxin Li (Planta, 2025)

Combined impacts of vertical greening and permeable pavement systems on street Canyons' microclimate in hot and humid regions in China - Haoxian Wang; Jiahong Zhao; Jiang Lu; Jian Ge; Guoquan Lv; Xiaoyu Luo; Haiqin Lin; Muye Gu (Urban Climate, 2025)

Thiostrepton suppresses colorectal cancer progression through reactive oxygen species related endoplasmic reticulum stress - Zhexuan Li; Juan Nie; Runyu Zhou; Hui Huang; Xuemei Li; Li Wang; Lin Lv; Sichong Ren; Ming Zhao (Toxicology and Applied Pharmacology, 2025)

AFB1 consolidates HBV harm to induce liver injury and carcinogenic risk by inactivating FTCD-AS1-PXR-MASP1 axis - Yaqi Xing; Wusheng Zhong; Xuejun Wu; Zhengzhong Ni; Wenya Lv; Ying Fan; Ling Chen; Haorui Lin; Yangmin Xie; Jianwei Lin; Yongdong Niu (Toxicology, 2025)

Evaluation of resource-based rural sewage treatment system driven by clean energy in Northwest China - Zilan Liao; Shangbin Ma; Pengyu Li; Yuxin Wang; Yixiao Li; Minghuan Lv; Tianlong Zheng; Jianguo Liu; Lin Li; Junxin Liu (Journal of Water Process Engineering, 2025)

Ultrathin LDH-coated SnO2 catalysts linked by hydrogen bonding for PMS activation via interlayer high-speed electron transfer channels: Performance and mechanism - Guangjie Lv; Haoyang Ye; Cui Lai; Dengsheng Ma; Xuerong Zhou; Xiuqin Huo; Hao Deng; Lin Tang; Tao Tong; Ming Yan; Shuyuan Hu; Lei Qin (Journal of Environmental Chemical Engineering, 2025)

Uncovering characteristic and enantiomeric distribution of volatile components in Huangshan Maofeng and Zhejiang baked green teas - Yu-Hui Zhang; Pan-Deng Lei; Yong Ding; Xiao-Ting Zhai; Xiao-Chun Wan; Wei-Xuan Li; Yue Zhang; Hai-Peng Lv; Zhi Lin; Yin Zhu (Food Chemistry, 2025)

Insight into volatile metabolites and key odorants in black teas processed from Jianghua Kucha tea germplasm (Camellia sinensis var. assamica cv. Jianghua) - Ying-Lin Zhu; Wei-Xuan Li; Yu-Hui Zhang; Han Yan; Long-Yu Guo; Yue Zhang; Hai-Peng Lv; Ling-Hong Zhou; Zhi Lin; Wen-Liang Wu; Yin Zhu (Food Chemistry, 2025)

Harnessing CuCoOX-Modified copper phenylacetylene for enhanced activation of peroxymonosulfate in non-radical sulfisoxazole degradation: Performance, pathways, and mechanisms - Wenjun Li; Daguang Li; Zili Lin; Yuchun Hong; Yishun Wang; Guangzhi Zhang; Ping Chen; Wenying Lv; Guoguang Liu (Environmental Pollution, 2025)

Construction of 3D MXene-SO3/graphene oxide/cyclodextrin heterogeneous hybrid aerogels for green and efficient catalysis production of ethyl acetate - Qi Ao; Xiaoxiao Lv; Lin Jiang; Jun Tang (Chemical Engineering Journal, 2025)

Manganese halides with timely and delayed reversible thermal fluorescence quenching for dual-secure information encryption and anti-counterfeiting - Li Cong; Longyun Lv; Ying Liu; Yuxin Jia; Xuerui Chang; Yufan Lin; Juan Li; Bin-Bin Cui (Chemical Engineering Journal, 2025)

Influences of permeable pavements with different hydraulic properties on evaporative cooling and outdoor thermal environment: Field experiments - Jiahong Zhao; Jiang Lu; Jian Ge; Yifan Fan; Haoxian Wang; Muye Gu; Yucong Xue; Yujie Zhao; Guoquan Lv; Haiqin Lin; Kang Zhao; Xiaoyu Luo (Building and Environment, 2025)

Melatonin mitigates the lipopolysaccharide-induced myocardial injury in rats by blocking the p53/xCT pathway-mediated ferroptosis - Xin Jing; Zhida Chen; Mingdao Zhang; Caiqin Luo; Bo Yang; Yanlan Lv; Yue Li; Lina Zeng; Wenji Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Effects of fine particulate matter bound heavy metals on intentional self-harm deaths in Guangzhou, China, insight from core chemical constituents - Chunyan Gui; Han Zhang; Zhanlu Lv; Tao Liu; Shengbing Yu; Yanjun Xu; Hualiang Lin; Jianpeng Xiao; Wenjun Ma; Bin Luo; Ling-Chuan Guo (International Journal of Biometeorology, 2025)

Decreased net N nitrification rate constrains soil N availability during long-term Camellia oleifera cultivation - Tinghao Zong; Jingwei Ma; Xinming Guan; Yusong Lin; Yuqi Chen; Meiqi Wang; Jiaze Lv; Yichao Rui; Yang Chen; Lichao Wu; Sheng Lu (Applied Soil Ecology, 2025)

Inactivated LMBV vaccine with nano‑aluminum adjuvant provided immune protection in largemouth bass (Micropterus Salmoides) - Xia Luo; Ruoxuan Wang; Baofu Ma; Ouqin Chang; Xiaozhe Fu; Hongru Liang; Yinjie Niu; Qiang Lin; Lihui Liu; Aijun Lv; Ningqiu Li (Aquaculture, 2025)

Data-driven optimization of nose profiles for water entry impact load reduction - Kai Lv; Enfan Lin; Yongze Liu; Zongbao Chen; Yexian Wang; Ming He; Jiale Yan; Pengyu Lv; Yantao Yang; Hongyuan Li; Huiling Duan (Ocean Engineering, 2025)

Achieving pollution abatement and carbon reduction synergistically: How can industrial robots play a role? - Chongchong Xu; Helen Lv Zhang; Boqiang Lin (Journal of Environmental Management, 2025)

Development and antimicrobial activity of composite edible films of chitosan and nisin incorporated with perilla essential oil-glycerol monolaurate emulsions - Zhantong Fang; Yating Yang; Shuimu Lin; Lirong Xu; Shuyi Chen; Wanxia Lv; Nannan Wang; Shiyi Dong; Chunhong Lin; Yutao Xie; Jingru Liu; Meihan Meng; et al. (Food Chemistry, 2025)

Emerging amine-assisted electrolytes for rechargeable magnesium metal batteries: Current understanding and future direction - Lin Yang; Aobing Du; Zhaolin Lv; Zhonghua Zhang; Guicun Li (Chemical Engineering Journal, 2025)

Breaking separation bottleneck in sucralose production: Clarifying the obscure mechanism and pre-embedding second solvents for highly selective separation of chlorinated product - Xiaoping Chen; Jiayan Lei; Zhoulin Lv; Zi'ang Chen; Shitong Lin; Zhenming Guo; Huadong Luo; Yingshu Wang; Jingjing Chen; Haohong Li; Huidong Zheng (Chemical Engineering Journal, 2025)

Outstanding comprehensive energy storage performance in BNT-based lead-free ceramics via synergistic optimization strategy - Zixin Li; Wenjie Zhou; Jinming Guo; Xinye Lv; Shuxin Lin; Yilang Li; Long Gu; Fei Yan (Chemical Engineering Journal, 2025)

High dielectric sulfonyl-containing polyimide binders optimize the long-term stability and safety of NCM811 lithium-ion batteries at high voltages - Lin Chen; Dandan Yang; Junhao Xin; Xiaowei Zhou; Yuchen Zhang; Zixin Lv; Tiegen Guo; Qinghai Chen; Ruofei Gao; Ying Wang; Ning Wang; Shuanyan Kang; et al. (Chemical Engineering Journal, 2025)

Box-shaped necklace-like Fe3O4/MoS2-CNFs composite nanofibers with confinement effect enhancing sodium storage performance - Huayu Wu; Mohan Yue; Lin He; Miao Zhang; Yimin Huang; Chang Sun; Yu Liu; Jindi Wang; Rongguan Lv; Rong Xing (Chemical Engineering Journal, 2025)

The static and dynamic adsorptive performance of a nitrogen and sulfur functionalized 3D chitosan sponge for mercury and its machine learning evaluation - Xianghua Wu; Zhiheng Zhang; Haiying Lin; Qingge Feng; Bin Xue; Mingen Li; Zixuan Chen; Jiatong Lv; Lianghong Li (Carbohydrate Polymers, 2025)

Nrf2 inhibition and NCOA4-mediated ferritinophagy activation synergistically exacerbated S-3′-hydroxy-7′, 2′, 4′-trimethoxyisoxane induced ferroptosis in lung cancer cells - Jiaxin Liu; Songlin Zhou; Jing Chen; Haiyan Lin; Yang Li; Xian Zhang; Shiting Chen; Xiaoyang Lv; Huange Zhao (Chemico-Biological Interactions, 2025)

Uncovering the key lncRNAs in regulating cadmium accumulation and translocation in sweet sorghum - Kangqi Lin; Ze Yi; Sulian Lv; Bo Zhang; Zijin Guo; Yinxin Li (Planta, 2025)

YY1 as a mediator to enhance the resistance of KRAS mutant colorectal cancer cells to cetuximab - Yi Ma; Yuli Hu; Yi Lin; Congying Wang; Yujie Lv; Wei Chen (Journal of Genetics, 2024)

Enhanced humic acid removal by sludge activated carbon/Fe2+ composite in peroxymonosulfate activation: mechanism and performance - Feng Lin; Shuxin Zhang; Baoyu Wang; Huanlei Yang; Jiangtao Lv; Siqi Zhang (Environmental Science and Pollution Research, 2024)

PupaNet: A versatile and efficient silkworm pupae (Bombyx mori) identification tool for sericulture breeding based on near-infrared spectroscopy and deep transfer learning - Haibo He; Hua Huang; Shiping Zhu; Lunfu Shen; Zhimei Lv; Yongkang Luo; Yichen Wang; Yuhang Lin; Liang Gao; Benhua Xiong; Fangyin Dai; Tianfu Zhao (Computers and Electronics in Agriculture, 2024)

Carbon chain elongation characterizations of electrode-biofilm microbes in electro-fermentation - Wei-Tong Ren; Zi-Lin He; Yang Lv; Hua-Zhe Wang; Lin Deng; Shan-Shan Ye; Juan-Shan Du; Qing-Lian Wu; Wan-Qian Guo (Water Research, 2024)

First direct measurements of the nitrogen isotopic composition of vehicle tailpipe-emitted NH3 and implications for the source apportionment of NH3 in urban atmosphere - Yu-Ning Feng; Yunhua Chang; Lin Cheng; Haifeng Yu; Jinling Lv; Wendell W. Walters (Science of The Total Environment, 2024)

Spaceborne high-spectral-resolution lidar ACDL/DQ-1 measurements of the particulate backscatter coefficient in the global ocean - Yichen Yang; Yudi Zhou; Iwona S. Stachlewska; Yongxiang Hu; Xiaomei Lu; Weibiao Chen; Jiqiao Liu; Wenbo Sun; Suhui Yang; Yuting Tao; Lei Lin; Weige Lv; et al. (Remote Sensing of Environment, 2024)

Molecular phylogenetic and estimation of evolutionary divergence and biogeography of the family Schizoparmaceae and allied families (Diaporthales, Ascomycota) - Taichang Mu; Yongsheng Lin; Huili Pu; Nemat O. Keyhani; Yuxiao Dang; Huajun Lv; Zhiying Zhao; Zhiang Heng; Ziyi Wu; Chengjie Xiong; Longbing Lin; Yuxi Chen; et al. (Molecular Phylogenetics and Evolution, 2024)

In vitro and in vivo investigation of the inhibitory effects of Sinoporphyrin sodium-mediated Sonodynamic therapy on human oral squamous cell carcinoma - Guogang Dong; Limin Jia; Shuhua Gao; Monan Lin; Ruilin Wang; Fuyu Yang; Juanjuan Ruan; Yanhong Lv (Journal of Photochemistry and Photobiology B: Biology, 2024)

Insights into pore structure-activity relationships of iron catalysts supported on fluorine–cerium nanosheets for heterogeneous Fenton oxidation - Jing Lv; Hui Ye; Shurui Han; Jinli Zhao; Guodong Yang; Han Zhang; Xiaojian Fu; Jing Zhang; Qingping Xin; Lizhi Zhao; Hong Li; Ligang Lin; et al. (Journal of Environmental Chemical Engineering, 2024)

Operando on-line monitoring of nanoplastics in real environmental water samples enabling an optical microfiber Mach-Zehnder interferometer - Hongtao Li; Aiyun Zheng; Hao Wu; Weisheng Wang; Xu Wang; Yangyang Yu; Lili Liang; Huojiao Sun; Jiping Lin; Liang Lu; Jialiang Lv; Hao Yuan; et al. (Journal of Environmental Chemical Engineering, 2024)

Magnetic sludge-derived biochar for Cu (II) removal: RSM-based preparation and BP artificial neural network adsorption modeling - Yunfan Bai; Danyang Lei; Lin Li; Chuhua Qi; Yongxing Lv; Qilin Guo; Zhixian He; Shuangli Chen; Sijing Zhang (Journal of Environmental Chemical Engineering, 2024)

Study on properties and CO2 emission of self-pulverizing calcium sulfoaluminate (SPCSA) after carbonization curing - Shuguo Li; Yang Lv; Chenhao He; Shengju Hou; Weinan Ma; Xiaodong Wen; Jianming Dan; Junpeng Mei; Lin Chi; Xiangguo Li (Journal of Environmental Chemical Engineering, 2024)

The rational design of ratiometric probe based on fluorescence carbon dots and its PVA film platform for the detection of Hg2+: Tunable mechanism and the performance - Qiuyan Hu; Haiying Lin; Qingge Feng; Xianghua Wu; Lixin Huang; Yu Duan; Wenlu Lan; Zixuan Chen; Lianghong Li; Jiatong Lv; Jie He; Chun Lv; et al. (Journal of Environmental Chemical Engineering, 2024)

A phenological-knowledge-independent method for automatic paddy rice mapping with time series of polarimetric SAR images - Suya Lin; Zhixin Qi; Xia Li; Hui Zhang; Qianwen Lv; Di Huang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Comparison of recombinant protein Z with natural protein Z derived from malt: From structure to functional properties - Hanhan Liu; Kailin Yang; Yang Gao; Junyu Lin; Guanghua Zhao; Chenyan Lv (Food Chemistry, 2024)

Alterations in the nutrient composition, muscle quality, and proteomics of two Sepiidae species (Sepiella maindroni and Sepia esculenta) during storage - Shan-Shan Jiang; Hao-Ran Lv; Hui-Min Lin; Jie Feng; Soottawat Benjakul; Shucheng Liu; Bin Zhang (Food Bioscience, 2024)

Platelet-hitchhiking biomimetic nanoplatforms pry precisely tumor seed and growing soil for inhibiting tumor recurrence and metastasis - Yan Zhang; Weiting Sun; Guozheng Xing; Dunwan Zhu; Lin Mei; Xia Dong; Feng Lv (Chemical Engineering Journal, 2024)

Lactic acid production from food waste: Advances in microbial fermentation and separation technologies - Liang Song; Chenhang Cai; Zengpeng Chen; Chunxiang Lin; Yuancai Lv; Xiaoxia Ye; Yifan Liu; Xiaohu Dai; Minghua Liu (Bioresource Technology, 2024)

Autophagy-related 7 protein-dependent autophagy mediates resveratrol-caused upregulation of mitochondrial biogenesis and steroidogenesis in aged Leydig cell - Fanhong Lin; Shoubing Zhang; Xiaomei Zhu; Zhengmei Lv (Molecular Biology Reports, 2024)

Mitochondrial Protein TAMM41 Modulates Depressive-like Behaviors - Lin Guo; Ziyu Liu; Xiaoxia Jia; Qinghua Wang; Jianlun Ji; Na Lv; Zhidong Liu; Qin Zhou; Congcong Sun; Yun Wang (Molecular Neurobiology, 2024)

Effects of Different Nitrogen Fertilizer Rates on Soil Magnesium Leaching in Tea Garden - Sen Wang; Wei Lin; Qi Ye; Wenzhuo Lv; Penghui Liao; Jinhui Yu; Cong Mu; LiangQuan Wu; Muhammad Atif Muneer; Yinjie Zhang; Runzhi Zhan; Aolin Wu; et al. (Journal of Soil Science and Plant Nutrition, 2024)

Perceptual information processing in table tennis players: based on top-down hierarchical predictive coding - Ziyi Peng; Lin Xu; Jie Lian; Xin An; Shufang Chen; Yongcong Shao; Fubing Jiao; Jing Lv (Cognitive Neurodynamics, 2024)

Protective Role of (-)-Epicatechin on Trimethylamine-N-Oxide (TMAO)-Induced Cardiac Hypertrophy via SP1/SIRT1/SUMO1 Signaling Pathway - Siting Hong; Jing Lu; Jiaoyan Li; Yingchun Luo; Dongxue Liu; Yuanyuan Jin; Zeng Wang; Yibo Wang; Hao Zhang; Xin Zhang; Yang Li; Haoruo Zhang; et al. (Cardiovascular Toxicology, 2024)

Synthesis of Fe-ZSM-5 zeolite from high iron-containing palygorskite with peroxidase-like catalytic performance - Fengya Ran; Meng He; Shiyong Sun; Rui Lv; Sen Lin; Ke Wang; Yevgeny Aleksandrovich Golubev; Olga Borisovna Kotova; Elena Leonidovna Kotova (Applied Clay Science, 2024)

Virus susceptibility of a new cell line derived from the muscle of koi (Cyprinus carpio koi) - Hongli Jing; Lin Mei; Jizhou Lv; Min Zhang; Na Wang; Lipu Xu; Shaoqiang Wu (Archives of Virology, 2024)

The effect of paeoniflorin on the rewarding effect of methamphetamine and the associated cognitive impairment in mice - Xin-shuang Gong; Hai-xing Wang; Xiang-dong Yang; Zhao-ying Yu; Shu-jun Lin; Zhi-ting Zou; Jia-nan Lv; Li-yin Qian; Yu-er Ruan; Zi-zhen Si; Yi Zhou; Yu Liu (Metabolic Brain Disease, 2024)

Super-large diameter slurry shield tunnel encountering boulder formation: Detection, treatment and data analysis - Wei-Hong Yang; Dong Su; Xing-Tao Lin; Zhi-Jia Lv; Zhan-Hu Yao; Hui Li; Ya-Zhou Zhang; Xiang-Sheng Chen (Transportation Geotechnics, 2024)

On the FT-ICR mass spectrometry analysis of dissolved organic matter released by adsorbent during coal chemical wastewater treatment - Qi Wei; Cai Chen; Hong-Peng Ma; Tao Liu; Bing Liu; Tian-Xiang Wang; Sen Zhang; Dan-Hui Yang; Wen-Jie Lv; Hua-Lin Wang (Science of The Total Environment, 2024)

Degradation-driven vegetation-soil-microbe interactions alter microbial carbon use efficiency in Moso bamboo forests - Ning Yuan; Fang Fang; Xiaoping Tang; Shaofeng Lv; Tongying Wang; Xin Chen; Taoran Sun; Yiyun Xia; Yufeng Zhou; Guomo Zhou; Yongjun Shi; Lin Xu (Science of The Total Environment, 2024)

Enhanced cesium removal from wastewater using a potassium hexacyanoferrate/gelatin aerogel composite - Dongjun Chen; Juan Liu; Zhen Qian; Yunpeng Xiao; Yifan Liu; Yuancai Lv; Xiaoxia Ye; Chunxiang Lin (Process Safety and Environmental Protection, 2024)

Efficient degradation of ciprofloxacin by innovative VUV/BN system: Kinetics, mechanism and toxicity assessment - Hongda Zhan; Zili Lin; Lingrong Chen; Zhenjun Xiao; Dezhu Liu; Yishun Wang; Zhihong Chen; Zhenchao Li; Zengkai Fu; Linsheng Liu; Zihong Xu; Shuyue Chen; et al. (Journal of Water Process Engineering, 2024)

Nitrogen-doped cobalt oxide via atmospheric modulation activates PMS for rapid degradation of organic pollutants: Role of nitrogen fraction on sulfapyridine elimination - Lingxiao Zou; Kai Yang; Yihui Hu; Xingyu Guo; Xiaojing Li; Yuancai Lv; Yifan Liu; Xiaoxia Ye; Chunxiang Lin; Minghua Liu (Journal of Water Process Engineering, 2024)

Impacts of land use and crop structure change on the value of ecosystem services in Hetao Irrigation District of China - Lin Yang; Shengwei Zhang; Meng Luo; Xingyu Zhao; Xi Lin; Qian Zhang; Kedi Fang; Shengwei Lv (Journal of Cleaner Production, 2024)

Dissect the association between per- and polyfluoroalkyl substances (PFAS) and kidney function from the perspective of lipid molecules - Yi-Ran Chen; Shao-Bin Lin; Jia-Yun Lv; Yan Wu; Wen-Ru Feng (Environmental Pollution, 2024)

Stabilization of single crystal LiNi0.90Mn0.05Co0.05O2 via ZrO2 dual-functional coating enables superior performance for solid-state lithium battery - Chen Liu; Qiyue Luo; Lin Li; Chaochao Wei; Siwu Li; Xia Li; Wanming Li; Zihan Zhang; Zhongkai Wu; Zilin Jiang; Hui Yang; Long Zhang; et al. (Chemical Engineering Journal, 2024)

PTC-NH2@MOFs-AuNCs: A novel bifunctional signal probe for ratiometric electrochemiluminescence/colorimetry dual-mode aptasensing of lead ion - Libo Li; Panao Jiang; Meiyang Zhen; Xiaohong Liu; Lijun Luo; Wenzhen Lv; Lin Luo; Tianyan You (Chemical Engineering Journal, 2024)

Covalently anchoring phosphorus nitride imide on carbon nanotubes for efficient electrochemical extraction of uranium - Sheng Li; Lin Zhao; Shiyong Wang; Changping Li; Lirong Cai; Sihao Lv; Gang Wang (Chemical Engineering Journal, 2024)

Base on photothermal interfacial molecular transfer for efficient biodiesel catalysis via enzyme@cyclodextrin metal-organic frameworks loaded MXene - Qi Ao; Lin Jiang; Ying Song; Xinglai Tong; Tuohao Jiang; Xiaoxiao Lv; Jun Tang (Carbohydrate Polymers, 2024)

Genome-wide identification of m6A-related gene family and the involvement of TdFIP37 in salt stress in wild emmer wheat - Jiaqian Huang; Yanze Jia; Yan Pan; Huiyuan Lin; Shuzuo Lv; Mohsin Nawaz; Baoxing Song; Xiaojun Nie (Plant Cell Reports, 2024)

Identification of shallow groundwater recharge and circulation in an intensive agricultural area of the Sanjiang Plain, China, based on hydrochemistry, isotopes and hydrogeological conditions - Zhihong Li; Xuxue Cheng; Lin Lv; Huqun Cui; Weipo Liu; Jiangtao Liu; Tingwen Wu (Hydrogeology Journal, 2024)

12-year continuous biochar application: Mitigating reactive nitrogen loss in paddy fields but without rice yield enhancement - Penghui Jin; Zhe Chen; Hui Wang; Runjin Lv; Tianlong Hu; Rong Zhou; Jingru Zhang; Xingwu Lin; Qi Liu; Zubin Xie (Agriculture, Ecosystems & Environment, 2024)

Effects of salinity on nitrogen reduction pathways in estuarine wetland sediments - Hao Zheng; Zhengxin Yin; Liang Chen; Huizhong He; Zhengyuan Li; Xiuya Lv; Jiyu Chen; Wei Du; Xianbiao Lin (Marine Pollution Bulletin, 2024)

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

Quantifying city freight mobility segregation associated with truck multi-tours behavior - Yitao Yang; Yan Chen; Ying-Yue Lv; Xiang-Yu Jia; Xu-Jie Lin; Xiao-Yong Yan; Bin Jia; Ed Manley (Sustainable Cities and Society, 2024)

Female urinary incontinence in China after 15 years’ efforts: Results from large-scale nationwide surveys - Jiming Zhu; Haiyu Pang; Peicheng Wang; Yanhua Chen; Huihui Li; Qing Liu; Luwen Wang; Hangmei Jin; Liyan Gong; Jingyan Xie; Ting Lai; Aiyang Li; et al. (Science Bulletin, 2024)

Water availability may not restrict the implementation of carbon capture utilization and storage technology: Evidence from China's electric power sector - Haodong Lv; Xi Lu; Lin Yang; Ning Wei; Yiming Li; Xian Zhang (Resources, Conservation and Recycling, 2024)

Utilization of cow bone waste and calcium oxide for the solidification and stabilization of MSWI fly ash: Towards sustainable practices - Zeinab Khalid; Lijuan Sun; Guojun Lv; Shunda Lin; Bangji Wei; Yin Duan; Xiaobo Liu; Xuguang Jiang (Process Safety and Environmental Protection, 2024)

Highly-efficient peroxymonosulfate activation by porous nano-MgO for tetracycline degradation: Surface hydroxyl groups and oxygen vacancies synergetic mediated nonradical process - Hongmin Zhang; Xudong Wang; Yujing Lin; Yongtao Lv; Licheng Chen; Lei Wang (Process Safety and Environmental Protection, 2024)

Efficient degradation and mineralization of polyethylene terephthalate microplastics by the synergy of sulfate and hydroxyl radicals in a heterogeneous electro-Fenton-activated persulfate oxidation system - Yinghui Lin; Yuehua Zhang; Yonghao Wang; Yuancai Lv; Linyan Yang; Zhijie Chen; Bing-Jie Ni; Xueming Chen (Journal of Hazardous Materials, 2024)

Analysis the sewage sludge recycling strategy based on real-time pyrolysis performance and pyrochar characteristics - Jingjing Chen; Yuping Zheng; Mengyan Lv; Tingting Zhao; Qingqi Lin; Zhuobiao Ni; Zuotai Zhang; Rongliang Qiu (Journal of Cleaner Production, 2024)

Development of a NiFe2O4 covalent organic framework based magnetic solid-phase extraction approach for specific capture of quinolones in animal innards prior to UHPLC–Q–Orbitrap HRMS detection - Shumin Lin; Yun-kai Lv; Aixue Zhu; Ming Su; Xiliang Li; Shu-xuan Liang (Food Chemistry, 2024)

Enhancing interfacial electron transfer and photoelectrochemical kinetics for efficient water-treatment strategy through N-doped carbon dots modified PhC2Cu - Xiaoyu Zhang; Yishun Wang; Zili Lin; Qingman Chen; Minghao Liu; Dezhu Liu; Zhenchao Li; Ping Chen; Wenying Lv; Guoguang Liu (Environmental Pollution, 2024)

Deccan volcanism's influence on Chicxulub impact signatures at the continental Cretaceous-Paleogene boundary in the Sichuan Basin, China - Liu Xuemin; Lv Xiaowei; Jiang Yao; Shi Zhiqiang; Tian Yaming; Wang Lin (Earth and Planetary Science Letters, 2024)

Immobilization of laccase on mesoporous metal organic frameworks for efficient cross-coupling of ethyl ferulate - Xinqi Xu; Feng Shen; Gan Lv; Juan Lin (World Journal of Microbiology and Biotechnology, 2024)

A 3D bedrock modeling method based on information mining of 2D geological map - Tong Niu; Bingxian Lin; Liangchen Zhou; Guonian Lv (Earth Science Informatics, 2024)

Synergistic activation of persulfate by Fe-based perovskite photocatalysis for alkali lignin degradation in pulp and paper wastewater - Yifan Liu; Zhuangqin Xu; Yuting He; Minghua Liu; Chunxiang Lin; Yuancai Lv (Environmental Science and Pollution Research, 2024)

Prevention and potential repair of colitis: Beneficial effects and regulatory mechanisms of food-derived anti-inflammatory peptides - Renzhi Lv; Na Sun; Chuwen Mao; Zhihong Zheng; Songyi Lin (Critical Reviews in Food Science and Nutrition, 2024)

Association of prenatal multiple metal exposures with child neurodevelopment at 3 years of age: A prospective birth cohort study - Yun Qiu; Yuxin Liu; Ming Gan; Weiting Wang; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; Xin Xu; et al. (Science of The Total Environment, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Small molecule perylene diimide derivatives with different bay site modifications as cathode interface layers for organic solar cells - Yanyan Wang; Dan Zhou; Senmei Lan; Jianwei Quan; Fang Wang; Lin Hu; Ruizhi Lv; Yujie Pu; Haitao Xu; Yongfen Tong; Bin Hu; Zhentian Xu; et al. (Chemical Engineering Journal, 2024)

An optically responsive cancer vaccine for inducing robust anti-tumor immunity by apoptotic body carrying nanoadjuvants - Limin Jin; Shupei Sheng; Yan Zhang; Weiting Sun; Lin Mei; Dunwan Zhu; Xia Dong; Feng Lv (Chemical Engineering Journal, 2024)

PRC2 primes bivalent genes for transcription induction independent of histone methyltransferase activity - Meihan Gong; Ye Yuan; Zhongye Dai; Xuejiao Lv; Jiacheng Su; Dawei Huo; Lin Niu; Xu Chen; Xudong Wu (Science China Life Sciences, 2024)

Kurarinone, a flavonoid from Radix Sophorae Flavescentis, inhibits RANKL-induced osteoclastogenesis in mouse bone marrow–derived monocyte/macrophages - Ling Long; Hao Luo; Yi Wang; Jiaxiang Gu; Jiachao Xiong; Xiaokai Tang; Hao Lv; Faxin Zhou; Kai Cao; Sijian Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Deep learning-based geological map generation using geological routes - Chaoling Li; Fengdan Li; Chang Liu; Zhen Tang; Si Fu; Min Lin; Xia Lv; Shuang Liu; Yuanyuan Liu (Remote Sensing of Environment, 2024)

High-performance elimination of Cr(VI) in actual wastewater with a novel nZVI-based composite anchoring onto amino-grafted chitosan - Lixin Huang; Junqi Wei; Haiying Lin; Bin Xue; Yu Duan; Mingzhi Li; Zixuan Chen; Jiatong Lv; Lianghong Li; Xianghua Wu; Qiuyan Hu (Journal of Water Process Engineering, 2024)

Carbon tax to phase out coal as propylene feedstock and control upstream methane emissions in China: Based on dynamic radiative forcing - Lin Lv; Guobao Song; Miaomiao Liu; Liang Zhao; Xinyue Zhao; Jingwen Chen (Journal of Cleaner Production, 2024)

Visible light-driven characterisation of AgI/CeO2/rGO nanocomposites and their application in levofloxacin degradation - Zhixin Ren; Lin Yang; Xiaoxue Tang; Qing Xu; Yanan Niu; Yuguang Lv; Mingyuan Liu (Journal of Environmental Chemical Engineering, 2024)

Tetrabromobisphenol A exerts thyroid disrupting effects but has little overt impact on postnatal brain development and neurobehaviors in mice - Shilin Song; Yuanyuan Li; Lin Lv; Mengqi Dong; Zhanfen Qin (Journal of Environmental Sciences, 2024)

Natural aromatic extract of black tea improved the water retention of pork meat batter - Wen-ping Xu; Rui-ling Dong; Ao-jing Lv; Yu-cong Li; Li-ting Zeng; Xue-ling Gao; Jun Qi; Zhou Lin; Hui-min Yan; Chun-hui Zhang; Guo-yuan Xiong (Food Research International, 2024)

Smart windows based on ultraviolet-B persistent luminescence phosphors for bacterial inhibition and food preservation - Xiaohui Lin; Chonghui Li; Shicai Xu; Jihua Wang; Huanxin Yang; Yikai Qu; Qingshuai Chen; Zhenghua Li; Mengyu Su; Guofeng Liu; Hanping Liu; Jilei Yang; et al. (Food Chemistry, 2024)

Comprehensive comparison of aroma profiles and chiral free and glycosidically bound volatiles in Fujian and Yunnan white teas - Han Yan; Wei-Xuan Li; Ying-Lin Zhu; Zhi-Yuan Lin; Dan Chen; Yue Zhang; Hai-Peng Lv; Wei-Dong Dai; De-Jiang Ni; Zhi Lin; Yin Zhu (Food Chemistry, 2024)

The Meso-Tethys Ocean: The nature, extension and spatial-temporal evolution - Jian-Jun Fan; Bo-Chuan Zhang; Jian-Bo Zhou; Yaoling Niu; Si-Lin Sun; Jun-Pu Lv; Yang Wang; Yu-Jie Hao (Earth-Science Reviews, 2024)

HO-1 activation contributes to cadmium-induced ferroptosis in renal tubular epithelial cells via increasing the labile iron pool and promoting mitochondrial ROS generation - Yan-Ting Lv; Tian-Bin Liu; Yue Li; Zhen-Yong Wang; Cai-Yu Lian; Lin Wang (Chemico-Biological Interactions, 2024)

Feedback of chain elongation microorganisms on iron-based conductive materials: Enhanced microbial functions and biotoxicity adaptation mechanisms - Wei-Tong Ren; Yang Lv; Zi-Lin He; Hua-Zhe Wang; Lin Deng; Shan-Shan Ye; Qing-Lian Wu; Wan-Qian Guo (Bioresource Technology, 2024)

Alleviating Pentatrichomonas hominis-induced damage in IPEC-J2 cells: the beneficial influence of porcine-derived lactobacilli - Yibin Zhu; Haiming Cai; Zhuanqiang Yan; Hanqin Shen; Siyun Fang; Dingai Wang; Shenquan Liao; Nanshan Qi; Minna Lv; Xuhui Lin; Junjing Hu; Yongle Song; et al. (Veterinary Research Communications, 2024)

Correction to: Gas6 Promotes Microglia Efferocytosis and Suppresses Inflammation Through Activating Axl/Rac1 Signaling in Subarachnoid Hemorrhage Mice - Junjia Tang; Yichao Jin; Feng Jia; Tao Lv; Anatol Manaenko; Lin‑Feng Zhang; Zeyu Zhang; Xin Qi; Yajun Xue; Bin Zhao; Xiaohua Zhang; John H. Zhang; et al. (Translational Stroke Research, 2024)

Acupoint catgut embedding attenuates oxidative stress and cognitive impairment in chronic cerebral ischemia by inhibiting the Ang II/AT1R/NOX axis - Jurui Wei; Qi Ai; Peier Lv; Wenyao Fang; Zixuan Wang; Jiumei Zhao; Wenqing Xu; Lin Chen; Jun Dong; Bijun Luo (Pflügers Archiv - European Journal of Physiology, 2024)

S100A9 Induces Macrophage M2 Polarization and Immunomodulatory Role in the Lesion Site After Spinal Cord Injury in Rats - Junqiao Lv; Zhiqiang Wang; Beiyang Wang; Chen Deng; Wei Wang; Lin Sun (Molecular Neurobiology, 2024)

Single nucleotide polymorphisms reveal the uniqueness of Gushan semi-rock tea in the tea germplasm resources of Fujian, China - Pan Wang; Shuiyuan Lv; Wentao Yu; Cheng Lin; Yanyu Zhu; Wenjing Gui; Caiguo Liu; Naixing Ye (Genetic Resources and Crop Evolution, 2024)

Dynamic brain functional states associated with inhibition control under different altitudes - Lin Yitao; Zhou Lv; Wei Xin; Fan Yongchen; Wu Ying (Cognitive Neurodynamics, 2024)

Integrated application of multi-omics and biochemical analysis revealed the physiological response mechanism of ammonia nitrogen tolerance in the razor clam (Sinonovacula constricta) - Gaigai Sun; Liyuan Lv; Hanhan Yao; Zhihua Lin; Nianjun Xu; Yinghui Dong (Frontiers in Marine Science, 2024)
As one of the major limiting environment factors in aquaculture, ammonia nitrogen brings severe threat to the growth and survival of aquatic animals, especially mollusk in benthic zones. However, the molecular mechanism underlying the toxic response and tolerance of mollusks to ammonia nitrogen remain unclear. In this study, transcriptome, metabolome and physiological indicators were combined to investigate the metabolic mechanism of adult razor clam ( Sinonvacula constricta ), which was exposed to ~46mg/L ammonia nitrogen for 1 day (A1) and 10 days (A10). It was observed that compared with A1, the contents of free amino acids, including taurine (Tau), alanine (Ala) and arginine (Arg), the activities of immune-related enzymes acid phosphatase (ACP) and alkaline phosphatase (AKP), and antioxidation-related enzymes superoxide dismutase (SOD) and glutathione peroxidase (GPX) in hepatopancreas, were significantly increased in A10, while the content of malondialdehyde (MDA) was significantly decreased ( P < 0.05). Furthermore, the contents of glucose and pyruvate in hepatopancreas, foot and hemolymph urea nitrogen (HUN) were significantly changed ( P < 0.05). Meantime, the comparative transcriptome analysis between A1 and A10 groups revealed the effects of ammonia stress on immune defense, antioxidant system and metabolic pathway. Likewise, metabolomic analysis showed that ammonia exposure interfered with amino acid metabolism, lipid metabolism and carbohydrate metabolism, with metabolism related-genes changed according to RNA-seq analysis. By comparing the metabolites and transcripts profiles of A10 and A1, the expression of some genes involved in detoxification and ammonia excretion was significantly changed. Combined with the changes in metabolites, we speculated that the convert endogenous ammonia to alanine, alanine-glucose cycle and urea synthesis might be adaptive strategies of the razor clam after ammonia stress. Collectively, the combination of physiological, transcriptome and metabolome will greatly contribute to the progressively understand the toxicity of ammonia exposure and the defense mechanism of razor clam against ammonia toxicity, and provide new sights on the potential molecular mechanisms of ammonia adaptive strategies in benthic mollusk.

The detoxification ability of sex-role reversed seahorses determines the sexual dimorphism in immune responses to benzo[a]pyrene exposure - Kai Wang; Yuanyuan Xue; Yali Liu; Xiaolei Su; Lei Wei; Chunhui Lv; Xu Zhang; Lele Zhang; Longwu Jia; Shiyi Zheng; Yicong Ma; Hansheng Yan; et al. (Science of The Total Environment, 2024)

Electro-assisted anaerobic digestion of waste activated sludge for biomethane production enhanced by hyperosmosis of sodium chloride: Characteristics and microbial mechanisms - Xiaodong Xin; Jiaqian Xie; Yanfang Wang; Wenxuan Wei; Linjuan Li; Lin Li; Wei Li; Sihao Lv; Junguo He; Liguo Zhang (Process Safety and Environmental Protection, 2024)

Benzo[a]pyrene evokes epithelial-mesenchymal transition and pulmonary fibrosis through AhR-mediated Nrf2-p62 signaling - Meng-Die Li; Li-Hong Chen; Hui-Xian Xiang; Ya-Lin Jiang; Bian-Bian Lv; De-Xiang Xu; Hui Zhao; Lin Fu (Journal of Hazardous Materials, 2024)

Simultaneous Cu(II)-EDTA decomplexation and Cu(II) recovery using integrated contact-electro-catalysis and capacitive deionization from electroplating wastewater - Xiaoyan Shen; Shiyong Wang; Lin Zhao; Haoran Song; Wei Li; Changping Li; Sihao Lv; Gang Wang (Journal of Hazardous Materials, 2024)

Transcriptomic analysis reveals the effects of maternal exposure to bisphenol AF on hypothalamic development in male neonatal mice - Lin Lv; Yuanyuan Li; Xuanyue Chen; Zhanfen Qin (Journal of Environmental Sciences, 2024)

Differential accumulation patterns of flavor compounds in Longjing 43 and Qunti fresh leaves and during processing responding to altitude changes - A. Bassiony; Qunhua Peng; Susanne Baldermann; Shan Feng; Kangni Yang; Yongcheng Zhang; Jianyu Fu; Haipeng Lv; Zhi Lin; Jiang Shi (Food Research International, 2024)

A systematic study on the chemical model of polycyclic aromatic hydrocarbons formation from nutrients (glucose, amino acids, fatty acids) in food - Qiuyi Lin; Haolin Zhang; Xiaomei Lv; Ruiwei Xie; Bing-Huei Chen; Yu-Wen Lai; Lei Chen; Hui Teng; Hui Cao (Food Chemistry, 2024)

Exploring the roles of excess amino acids, creatine, creatinine, and glucose in the formation of heterocyclic aromatic amines by UPLC-MS/MS - Haolin Zhang; Xiaomei Lv; Weiming Su; Bing-Huei Chen; Yu-Wen Lai; Ruiwei Xie; Qiuyi Lin; Lei Chen; Hui Cao (Food Chemistry, 2024)

New insight into the effects of p-benzoquinone on photocatalytic reduction of Cr(VI) over Fe-doped g-C3N4 - Shi-Wen Lv; Jialu Pan; Xiaoran Wang; Yifan Shao; Yanqing Cong; Lin Che (Environmental Research, 2024)

Endowing turbostratically porous carbon with rich edge nitrogen active sites for efficient capacitive removal of phosphate - Peng Zhang; Fukuan Li; Peng Lin; Dezhi Fang; Bowen Li; Xueli Zhang; Cuicui Lv; Kexun Li; Hao Wang (Desalination, 2024)

Insights into nitrogen-doped BiOBr with oxygen vacancy and carbon quantum dots photocatalysts for the degradation of sulfonamide antibiotics: Actions to promote exciton dissociation and carrier migration - Zhenchao Li; Chenghui Wen; Daguang Li; Zheng Fang; Zili Lin; Dezhu Liu; Yishun Wang; Xiaoyu Zhang; Ping Chen; Wenying Lv; Guoguang Liu (Chemical Engineering Journal, 2024)

Construction of short synthetic promoters for optimization of ovalbumin expression level in Saccharomyces cerevisiae - Ying Lin; Xiaomin Dong; Xueqin Lv; Long Liu; Jianghua Li; Guocheng Du; Jian Chen; Yanfeng Liu (Systems Microbiology and Biomanufacturing, 2024)

An improved representative of stomatal models for predicting diurnal stomatal conductance at low irradiance and vapor pressure deficit in tropical rainforest trees - Wei Xue; Xue-min He; Quan Wang; Pei-jun Shi; Guang-hui Lv; Jian-feng Huang; Da Yang; Jiao-lin Zhang (Agricultural and Forest Meteorology, 2024)

AKR1C2 genetic variants mediate tobacco carcinogens metabolism involving bladder cancer susceptibility - Yanping Xiao; Yang Shen; Hui Song; Fang Gao; Zhenguang Mao; Qiang Lv; Chao Qin; Lin Yuan; Dongmei Wu; Haiyan Chu; Meilin Wang; Mulong Du; et al. (Archives of Toxicology, 2024)

Two new anti-inflammatory compounds from the roots and rhizomes of Clematis terniflora var . manshurica (Rupr.) Ohwi - Ping Shao; Sheng Dong; Lin-Tong Mu; Ling Han; Chong-Ning Lv; Jiu-Zhi Yuan; Jin-Cai Lu (Natural Product Research, 2024)

Study on the purification mechanism for ammonia nitrogen in micro-polluted rivers by herbaceous plant - Rumex japonicus Houtt - Xiangyang Zhang; Huiliang Wang; Wei Zhang; Hong Lv; Xiaoying Lin (Chemosphere, 2024)

Phthalate and DINCH exposure and ovarian reserve markers among women seeking infertility care - Yangqian Jiang; Yiqun Xu; Shuxin Xiao; Xianxian Zhu; Hong Lv; Lu Zang; Shuifang Lei; Xin Xu; Bo Xu; Xiumei Han; Jin Zhu; Jiangbo Du; et al. (Science of The Total Environment, 2024)

Structurally diverse 1,2-diarylpropanes from the fruit of Crataegus pinnatifida and the investigation on their mirror-image ECD spectra with the same absolute configurations - Tian-Ming Lv; Rui Guo; Bo-Han Yang; Peng Zhao; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2024)

Modification of coal gasification slag-based activated coke by KOH activation method and its adsorption performance on methyl orange - Xiaofang You; Lixin Song; Jingwei Wang; Jianqiao Lv; Liqing Sun; Lin Li; Meng He (Journal of Water Process Engineering, 2024)

A robust transformer-based pipeline of 3D cell alignment, denoise and instance segmentation on electron microscopy sequence images - Jiazheng Liu; Yafeng Zheng; Limei Lin; Jingyue Guo; Yanan Lv; Jingbin Yuan; Hao Zhai; Xi Chen; Lijun Shen; LinLin Li; Shunong Bai; Hua Han (Journal of Plant Physiology, 2024)

A novel approach to heavy metal immobilization in municipal solid waste incineration fly ash: Investigating the use of chicken eggshell waste and CaO addition - Zeinab Khalid; Lijuan Sun; Guojun Lv; Shunda Lin; Bangji Wei; Yin Duan; Xiaobo Liu; Xuguang Jiang (Journal of Environmental Chemical Engineering, 2024)

Facile construction of a cobalt-incorporated N-doped porous carbon from biomass for highly efficient removal of tetracycline - Fengzhen Wu; Jiamei Qian; Changfu He; Yiming Mao; Guanfeng Lin; Feng Zhu; Yandan Chen; Jianhua Lv; Biao Huang; Beili Lu (Journal of Environmental Chemical Engineering, 2024)

An improved process for removal and recovery of heavy petroleum from solids using a ferrate-based hybrid oxidant - Yurou Guo; Peng Lv; Juan Li; Changqing He; Lin He; Hong Sui (Environmental Research, 2024)

Co-exposure to fluoride and sulfur dioxide induces abnormal enamel mineralization in rats via the FGF9-mediated MAPK signaling pathway - Ying Lv; Jin Yao; Yang Wang; Guohui Bai; Changhu Lin; Chenglong Tu (Environmental Research, 2024)

Unveiling the unique role of iron in the metabolism of methanogens: A review - Yuxin Ma; Ying Qu; Xiangwu Yao; Chujun Xia; Mengjie Lv; Xiao Lin; Lili Zhang; Meng Zhang; Baolan Hu (Environmental Research, 2024)

Formation behavior of PCDD/Fs during waste pyrolysis and incineration: Effect of temperature, calcium oxide addition, and redox atmosphere - Yuanjun Tang; Dongsheng Tao; Guoneng Li; Chao Ye; Zhongming Bu; Rong Shen; Yonghui Lin; Wei Lv (Environmental Pollution, 2024)

Stochastic processes shape microbial community assembly in biofilters: Hidden role of rare taxa - Yong-Chao Wang; Ya-Hui Lv; Can Wang; Ye Deng; Yu-Ting Lin; Guan-Yu Jiang; Xu-Rui Hu; John C. Crittenden (Bioresource Technology, 2024)

An Efficient Vector-Based CRISPR/Cas9 System in Zebrafish Cell Line - Xiaokang Ye; Jiali Lin; Qiuji Chen; Jiehuan Lv; Chunsheng Liu; Yuping Wang; Shuqi Wang; Xiaobo Wen; Fan Lin (Marine Biotechnology, 2024)

Association Between Prenatal Per- and Polyfluoroalkyl Substance Exposure and Maternal Serum Total Bile Acid Levels During Pregnancy: Effect Modification by Infant Sex and Maternal Prepregnancy BMI - Qian Liao; Huishen Huang; Peng Tang; Jun Liang; Jiehua Chen; Lei Lei; Yanye Song; Dongxiang Pan; Mengrui Lin; Fangfang Lv; Xue Liang; Xiaoyun Zeng; et al. (Exposure and Health, 2024)

Numerical Study on Electromagnetic Thermal Performance of Non-Metallic Armoured Optoelectronic Cable Winch System - Wenhua Li; Huaizhao Wu; Shanying Lin; Weiwei Shen; Qingtao Lv (Journal of Marine Science and Engineering, 2024)
Non-metallic armoured optoelectronic cable winch systems (NAOCWSs) play critical roles in facilitating signal transmission and powering subsea equipment. Due to the varying depths in these applications, deploying the entire cable length is unnecessary. However, the portion of the cable that remains coiled around the winch can generate an electromagnetic field, which may interfere with signal transmission and induce electromagnetic heating. This can lead to elevated temperatures within the system, affecting the cable’s lifespan. Consequently, this study examines the distributions of magnetic and temperature fields within the NAOCWS with different currents (10–30 A) and numbers of winding layers (1–10). Findings indicate that the magnetic flux density (MFD) changes periodically, and the period is closely related to the distance between the cables. At the centre of the cable, the flux density is minimum. Temperature distribution correlates with both current amplitude and the number of winding layers, where an increase in either parameter amplifies the temperature variance between the edge and intermediate cables within the same layer. The current does not affect the internal temperature distribution pattern. With the number of winding layers determined, the layer where the highest temperature of the system is located is well defined and does not vary with current.

Performance and mechanistic studies of rapid atenolol degradation through peroxymonosulfate activation by V, Co, and bamboo carbon catalyst - Yihui Hu; Kai Yang; Yule Lin; Xin Weng; Yanting Jiang; Jian Huang; Yuancai Lv; Xiaojuan Li; Yifan Liu; Chunxiang Lin; Minghua Liu (Environmental Science and Pollution Research, 2024)

Performance on adsorption of toluene by ionic liquid-modified AC in high-humidity exhaust gas - Ji-feng Guo; Zhao-li Ping; Nan Liu; Xin Zhang; Jia-lin Lv; Yan-yan Yao; Jia-jun Hu; Wen-juan Wang; Ji-xiang Li (Environmental Science and Pollution Research, 2024)

Manure replacing synthetic fertilizer improves crop yield sustainability and reduces carbon footprint under winter wheat–summer maize cropping system - Jincan Niu; Qudsia Saeed; Wenning Wang; Runze Zhang; Lin Liu; Fenglian Lv; Jiaxing Xu; Yan Han; Panxin Zhang; Changlu Hu; Hu Xu; Benhua Sun; et al. (Journal of Environmental Management, 2024)

Construction of Ni3S4@ZIS@C3N5 photocatalyst with type II and Z-type heterojunctions by self-assembly for efficient photocatalytic hydrogen evolution - Huixiang Yan; Wei Li; Huixing Yang; Yongzhuo Yu; Chaoyu Lv; Linlin Hou; Wenxu Zhang; Di Lin; Shichao Jiao (Environmental Research, 2024)

Selective capture of uranium by p-block bismuth-based metal–organic framework - Lin Zhao; Zhihao Pan; Lirong Cai; Shiyong Wang; Bing Lu; Sihao Lv; Yongfu Qiu; Gang Wang (Desalination, 2024)

A fractal Langmuir adsorption equation on coal: Principle, methodology and implication - Zhen Zhang; Gaofeng Liu; Xiaoming Wang; Runsheng Lv; Huan Liu; Jia Lin; George Barakos; Ping Chang (Chemical Engineering Journal, 2024)

Therapeutic strategies for small-diameter vascular graft calcification - Yanjiao Teng; Yang Xu; Pengfei Lv; Lin Song; Jianing Yang; Xiudan Wang; Xiaoqin Guo; Shufang Wang; Shike Hou; Qi Lv; Jie Shi (Chemical Engineering Journal, 2024)

SbYS1 and SbWRKY72 regulate Cd tolerance and accumulation in sweet sorghum - Weitao Jia; Zijing Guo; Sulian Lv; Kangqi Lin; Yinxin Li (Planta, 2024)

Zinc application facilitates the turnover of organic phosphorus in rice rhizosphere soil by modifying microbial communities - Haihan Lv; Jingli Ding; Lin Zhang; Chuang Wang; Hongmei Cai (Plant and Soil, 2024)

Tree barriers height information extraction under power line based on watershed segmentation and local maximum algorithm - Yan Li; Lv Zhou; Xue Lin Wen; Tai Ying Wu; Mian Lan; Di Zhang; Yi Zhan Zhao; Peng De Lai (International Journal of Remote Sensing, 2024)

Separation and reutilization of heavy metal ions in wastewater assisted by p-BN adsorbent - Jianzheng Zhen; Lingshan Miao; Zhilong Lin; Jiahao Sun; Haoxiang Yan; Yunzhan Ying; Zenglong Wu; Wenkai Song; Weiyang Lv; Changsheng Song; Yuyuan Yao (Chemosphere, 2024)

Enhanced lactic acid production from household food waste under hyperthermophilic conditions: Mechanisms and regulation - Liang Song; Chenhang Cai; Chunxiang Lin; Yuancai Lv; Yifan Liu; Xiaoxia Ye; Minghua Liu; Xiaohu Dai (Waste Management, 2024)

Immunoprotective effects of DNA vaccine against Eimeria tenella based on EtAMA3 and EtRON2L2 - Xiangjie Chen; Xixi Qiu; Junli Ni; Shenquan Liao; Nanshan Qi; Juan Li; Minna Lv; Xuhui Lin; Haiming Cai; Junjing Hu; Yongle Song; Lijun Yin; et al. (Veterinary Parasitology, 2024)

Spatially selective defect management of CsPbI3 films for high-performance carbon-based inorganic perovskite solar cells - Hailiang Wang; Qixian Zhang; Zedong Lin; Huicong Liu; Xiaozhen Wei; Yongfa Song; Chunyu Lv; Weiping Li; Liqun Zhu; Kexiang Wang; Zhenhua Cui; Lan Wang; et al. (Science Bulletin, 2024)

Isolation and characterization of seven neovibsane-type diterpenoids from Viburnum odoratissimum and their neuroblastoma cell protective effects - Jin-Ling Han; Tian-Ming Lv; Jia-Qi Niu; Jin-Le Hao; Guo-Dong Yao; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2024)

Sulfate-functionalized Fe-based MOF for removal of Pb(Ⅱ) and NO3- in industrial wastewater - Rui-Dong Wang; Wen-Qian Zhang; Hong-Bo Lv; Yan-Ting Chen; Lei Wang; Si-Han Zhou; Lin Du; Qi-Hua Zhao (Journal of Environmental Chemical Engineering, 2024)

Analysis of coal dust consolidation performance and mechanism based on in-situ screening of high urease-producing bacteria - Gang Zhou; Yinghui Lv; Lin Li; ShuaiLong Li; Xinyuan Zhang; Yongwei Liu (Journal of Environmental Chemical Engineering, 2024)

Enhanced peroxymonosulfate (PMS) activation process mediated by vanadium modified CoO catalyst for rapid degradation of organic pollutants: Insights into the role of V - Yanting Jiang; Xin Weng; Yihui Hu; Yuancai Lv; Zhendong Yu; Yifan Liu; Xiaojuan Li; Chunxiang Lin; Xiaoxia Ye; Guifang Yang; Minghua Liu (Journal of Environmental Chemical Engineering, 2024)

Emergence of tet(X4)-positive Enterobacterales in retail eggs and the widespread of IncFIA(HI1)-HI1A-HI1B(R27) plasmids carrying tet(X4) - Chao Yue; Yuman Bai; Tong Li; Haotian Deng; Litao Lu; Wannan Lin; Xiaoxiao Cui; Luchao Lv; Guolong Gao; Jian-Hua Liu; Yi-Yun Liu (International Journal of Food Microbiology, 2024)

Unique role of sulfonic acid exchange resin on preventing copper and zinc precipitation and enhancing metal removal in electrokinetic remediation - Han Cui; Yuchen Wang; Zichen Lin; Hongfeng Lv; Chongwei Cui (Chemical Engineering Journal, 2024)

Ultrasmall ruthenium nanozyme with RONS scavenging and anti-inflammatory effects for effective prevention of postoperative peritoneal adhesion - Jia Liu; Lin Shi; Xiaohuan Lu; Cheng Zhou; Zhixin Zhou; Qiying Lv; Lin Wang; Zheng Wang (Chemical Engineering Journal, 2024)

Design, synthesis and mechanism study of coumarin-sulfonamide derivatives as carbonic anhydrase IX inhibitors with anticancer activity - Qianqian Lv; Jing Zhang; Jianghong Cai; Lexian Chen; Jiajie Liang; Tianwan Zhang; Jiahui Lin; Ruiyao Chen; Zhiling Zhang; Peiting Guo; Yue Hong; Lingxue Pan; et al. (Chemico-Biological Interactions, 2024)

Protein extraction from chlorella pyrenoidosa microalgae: Green methodologies, functional assessment, and waste stream valorization for bioenergy production - Zijing Wang; Wangfang Ye; Yijing Wu; Xiaoyu Lin; Cuirong Luan; Xiaowei Xie; Yue Peng; Xiaohong Sun; Chuangyang Shi; Yuancai Lv; Jianlin Shen; Tess Astatkie; et al. (Bioresource Technology, 2024)

Tailpipe volatile organic compounds (VOCs) emissions from Chinese gasoline vehicles under different vehicle standards, fuel types, and driving conditions - Peiji Liu; Yajun Wu; Zongxuan Li; Zongyan Lv; Jinsheng Zhang; Yan Liu; Ainan Song; Ting Wang; Lin Wu; Hongjun Mao; Jianfei Peng (Atmospheric Environment, 2024)

Cognitive Deficits and Alzheimer’s Disease-Like Pathologies in the Aged Chinese Tree Shrew - Hongli Li; Bo-Lin Xiang; Xiao Li; Cong Li; Yu Li; Ying Miao; Guo-Lan Ma; Yu-Hua Ma; Jia-Qi Chen; Qing-Yu Zhang; Long-Bao Lv; Ping Zheng; et al. (Molecular Neurobiology, 2024)

Global response of different types of grasslands to precipitation and grazing, especially belowground biomass - Xi Lin; Hongbin Zhao; Shengwei Zhang; Vijay P. Singh; Ruishen Li; Meng Luo; Shuai Wang; Xingyu Zhao; Shengwei Lv; Xinghui Chen (Agriculture, Ecosystems & Environment, 2024)

Quantitative comparison of 2D and 3D monitoring dimensions in fish behavior analysis - Kai Lin; Shiyu Zhang; Junjie Hu; Xingdong Lv; Hongsong Li (Journal of Fish Biology, 2024)
To improve the accuracy and efficiency of fish behavior assessment, this paper focuses on quantitatively exploring the variations and relationships between different monitoring dimensions. A systematic comparison was conducted between 3D and 2D behavioral factors using an infrared tracing system, during both day and night. Significant differences in swimming distance were observed among the different monitoring methods, as determined by two‐way ANOVA and Tukey's test. A correction was applied to account for the disparities observed in 2D swimming distance, ensuring accurate measurements. These findings present a cost‐effective and efficient approach for obtaining precise 3D distance data. Additionally, a kinematic factor called the “number of U‐turns” was proposed to provide a more intuitive characterization of directional changes in fish swimming. Significant differences were observed between 2D and 3D data, with higher percentages of false U‐turn counts and missing U‐turn counts compared to correct counts in the 2D view. These findings suggest that reducing the monitoring dimension may impact the accurate estimation of swimming motion, potentially resulting in inaccurate outcomes. Finally, the statistical analyses of the non‐linear properties of fractal dimension revealed significant differences among the various monitoring methods. This conclusion has practical implications for biologists and physicists, enabling them to improve the accuracy of behavioral phenotyping for organisms exhibiting 3D motion.

Wind-driven hydrodynamic characteristics of Lake Taihu, a large shallow lake in China - Zongpu Xue; Wei Zhu; Lin Cheng; Yi Lv; Ganyu Feng (Environmental Science and Pollution Research, 2024)

Ecological and human health hazards of soil heavy metals after wildfire: A case study of Liangshan Yi autonomous prefecture, China - Lin Rao; Chao Zheng; Jian-Bin Chen; Jun-Zhuo Cai; Zhan-Biao Yang; Xiao-Xun Xu; Guo-Chun Lv; Chang-Lian Xu; Gui-Yin Wang; Yu-Bon Man; Ming-Hung Wong; Zhang Cheng (Chemosphere, 2024)

Sorption of cadmium by layered double hydroxides: Performance, structure-related mechanisms, and sequestration stability assessment - Dong Zhang; Zhishun Zhong; Zilong Liu; Shichong He; Jun Lin; Yiyan Lv; Ting Lü; Ying Pan; Huading Shi; Hongting Zhao (Chemosphere, 2024)

Environmentally realistic dose of tire-derived metabolite 6PPD-Q exposure causes intestinal jejunum and ileum damage in mice via cannabinoid receptor-activated inflammation - Yan Yang; Nan Sun; Jia Lv; Haojia Chen; Hongqian Wang; Jingjing Xu; Jiayue Hu; Lin Tao; Mingliang Fang; Yichao Huang (Science of The Total Environment, 2024)

Glyphosate drives autophagy-dependent ferroptosis to inhibit testosterone synthesis in mouse Leydig cells - Lu Lu; Cai-Yu Lian; Yan-Ting Lv; Shu-Hui Zhang; Long Wang; Lin Wang (Science of The Total Environment, 2024)

Nitrogen doped sinocalamus oldhami lignin-based activated biochar with high specific surface area: Preparation and its adsorption for malachite green contaminant - Hong Guo; Yaohua Liu; Yuancai Lv; Yifan Liu; Yunzhi Lin; Minghua Liu (Process Safety and Environmental Protection, 2024)

Insights into major pigment accumulation and (non)enzymatic degradations and conjugations to characterized flavors during intelligent black tea processing - Yongcheng Zhang; Kangni Yan; Qunhua Peng; Shan Feng; Zhangfeng Zhao; Long Chen; Lin Ye; Jianyu Fu; Haipeng Lv; Dan Mu; Chunwang Dong; Zhi Lin; et al. (Food Chemistry, 2024)

Effects of atrazine and curcumin exposure on TCMK-1 cells: Oxidative damage, pyroptosis and cell cycle arrest - Mengyao Ren; Xiunan Lv; Tong Xu; Jiatong Sun; Meichen Gao; Hongjin Lin (Food and Chemical Toxicology, 2024)

An enhanced monitoring method for spatio-temporal dynamics of salt marsh vegetation using google earth engine - Wenbin Yi; Nan Wang; Huiying Yu; Yinghui Jiang; Dong Zhang; Xinyang Li; Lin Lv; Zhenglei Xie (Estuarine, Coastal and Shelf Science, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Load Assessment Method for Multi-Layer Oceanographic Winch with Synthetic Fibre Ropes Based on Non-Rotation Symmetric Cylindrical Model - Haoran Ye; Wenhua Li; Shanying Lin; Qingtao Lv; Dinghua Zhang (Journal of Marine Science and Engineering, 2024)
Offshore winches are crucial in marine engineering, particularly in marine scientific research and deep-sea exploration. The use of fibre ropes presents significant opportunities for the weight reduction of winches as a consequence of the low length–strength ratio and characteristics of corrosion resistance. Nonetheless, a challenge arises in underestimating the stress load levels in load assessments of multi-layer winch systems using synthetic fibre ropes. Traditional computational methods reliant on symmetrically rotational models fall short in accurately predicting and assessing practical applications. This paper introduces a finite element analysis model based on a non-rotationally symmetric approach with four surfaces subjected to various radial pressure on account of the deformation of the fibre ropes. In the design model, sixteen stress detection paths have been incorporated to identify and confirm non-linear stresses. The outcomes of the finite element simulations have been compared with experimental results with two synthetic fibre ropes, each with distinct deformation characteristics utilised. The findings demonstrate that the application of the model aligns well with experimental results, showcasing its relevance and practical value in real-world scenarios. Precise theoretical calculations and experimental validation are pivotal to ensuring that equipment reliability and safety are maintained alongside the pursuit of light-weighting.

The adsorption and release mechanism of different aged microplastics toward Hg(II) via batch experiment and the deep learning method - Lianghong Li; Bin Xue; Haiying Lin; Wenlu Lan; Xinyi Wang; Junqi Wei; Mingen Li; Mingzhi Li; Yu Duan; Jiatong Lv; Zixuan Chen (Chemosphere, 2024)

Unveiling the nitrogen and phosphorus removal potential: Comparative analysis of three coastal wetland plant species in lab-scale constructed wetlands - Xiaoqing Gao; Yuxin Bi; Lin Su; Ying Lei; Lv Gong; Xinhan Dong; Xiuzhen Li; Zhongzheng Yan (Journal of Environmental Management, 2024)

Construction of copper-manganese based aminoclays with significant laccase-like activity and its prominent degradation performance towards bisphenol A - Yifan Zeng; Shiyong Sun; Rui Lv; Ke Wang; Yevgeny Aleksandrovich Golubev; Sen Lin; Faqin Dong; Elena Leonidovna Kotova; Olga Borisovna Kotova (Journal of Environmental Chemical Engineering, 2024)

The Earth Summit Mission-2022: Successful ozone soundings contribute to source identification in the north Mt. Qomolangma region - Jinqiang Zhang; Chunxiang Ye; Yuejian Xuan; Zhixuan Bai; Weili Lin; Dan Li; Lingkun Ran; Baofeng Jiao; Yaoming Ma; Weiqiang Ma; Nan Yao; Yunshu Zeng; et al. (Journal of Environmental Sciences, 2024)

Microbial metabolic flexibility guarantees function resilience in response to starvation disturbance - Yong-Chao Wang; Ya-Hui Lv; Xu-Rui Hu; Yu-Ting Lin; John C. Crittenden; Can Wang (Bioresource Technology, 2024)

Enhancing effluent quality prediction in wastewater treatment plants through the integration of factor analysis and machine learning - Jiaqiang Lv; Lili Du; Hongyong Lin; Baogui Wang; Wanxin Yin; Yunpeng Song; Jiaji Chen; Jixian Yang; Aijie Wang; Hongcheng Wang (Bioresource Technology, 2024)

Short-term exposure to ambient air pollution and hospital admissions for angina among older adults in South China - Luxi Xu; Ruijun Xu; Yunshao Ye; Rui Wang; Jing Wei; Chunxiang Shi; Qiaoxuan Lin; Ziquan Lv; Suli Huang; Qi Tian; Yuewei Liu (Atmospheric Environment, 2024)

NADPH oxidase 4-mediating oxidative stress contributes to endometriosis - Xiaojie Wang; Xiaona Jiang; Xin Lv; Xinshu Wang; Aimin Lin; Yangyang Li (Journal of Applied Genetics, 2024)

Sea buckthorn oil regulates primary myoblasts proliferation and differentiation in vitro - Jiamin Zhao; Lin Liang; Weipeng Zhang; Xuan Liu; Guoqiang Huo; Xiangdong Liu; Xiaoyang Lv; Junxing Zhao (In Vitro Cellular & Developmental Biology - Animal, 2024)

Degradation of sulfonamide antibiotic via UV/MgO2 system: kinetic, application, and mechanism - Yixun Zheng; Zhenjun Xiao; Yijie Lin; Zheng Fang; Deyang Liu; Zifeng Lin; Qianxin Zhang; Ping Chen; Zhenheng Zhang; Lu Xv; Wenying Lv; Guoguang Liu (Environmental Science and Pollution Research, 2024)

Dual-color nanospheres based on aggregation-induced emission and catalytic hairpin assembly for simultaneous imaging of acrylamide and miR-21 in living cells - Jiajun Wu; Xianfeng Lin; Jin Li; Ziyu Lv; Nuo Duan; Zhouping Wang; Shijia Wu (Journal of Hazardous Materials, 2024)

Abscisic acid promotes selenium absorption, metabolism and toxicity via stress-related phytohormones regulation in Cyphomandra betacea Sendt. (Solanum betaceum Cav.) - Xun Wang; Wen Lu; Ziming Zhao; Wenhui Hao; Ruimin Du; Zhiyu Li; Zhihui Wang; Xiulan Lv; Jin Wang; Dong Liang; Hui Xia; Yi Tang; et al. (Journal of Hazardous Materials, 2024)

Association of adverse fetal outcomes with placental inflammation after oral gestational exposure to hexafluoropropylene oxide dimer acid (GenX) in Sprague-Dawley rats - Di Lv; Hongyun Liu; Qi An; Chengwei Lei; Yanxuan Wang; Jin Sun; Chuanhai Li; Yongfeng Lin; Qing Dong; Zhugen Yang; Kui Che; Wendong Liu; et al. (Journal of Hazardous Materials, 2024)

Evaluation the life cycle carbon emissions of the aerogel glazing under different weather conditions - Yang Liu; Jiamin Yan; Zhangbao Hu; Youming Chen; Lin Lv (Journal of Cleaner Production, 2024)

Exploration of sustainable driving path of rural domestic wastewater treatment-from the perspective of life cycle assessment - Pengyu Li; Yuxin Wang; Tianlong Zheng; Yingnan Cao; Xiuyuan Lv; Xiaoqin Zhou; Guangtao Zhang; Yingqun Ma; Lin Li; Junxin Liu (Journal of Cleaner Production, 2024)

Process optimization and mechanism for removal of high-concentration chlorine from municipal solid waste incineration fly ash washing wastewater by Friedel's salt - Shunda Lin; Guojun Lv; Zeinab Khalid; Xuguang Jiang; Jianhua Yan (Journal of Environmental Management, 2024)

Rapid survey method for large-scale outdoor surveillance cameras using binary space partitioning - Xin Lan; Liangchen Zhou; Bingxian Lin; Jiahao Li; Guonian Lv (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Potential of a novel endophytic diazotrophic Serratia sp. Wed4 for pyrene biodegradation - Chaoba Lin; Fuying Zhang; Rui Chen; Shiping Lin; Peiyuan Jiao; Yajing Ma; Xuezhu Zhu; Baitao Lv (International Biodeterioration & Biodegradation, 2024)

Comprehensive analysis of pigment alterations and associated flavor development in strip and needle green teas - Yongcheng Zhang; Kangni Yan; Qunhua Peng; Susanne Baldermann; Yin Zhu; Weidong Dai; Shan Feng; Jesus Simal-Gandara; Jianyu Fu; Haipeng Lv; Zhi Lin; Jiang Shi (Food Research International, 2024)

Engineering of zeolitic imidazolate frameworks based on magnetic three-dimensional graphene as effective and reusable adsorbent to enhance the adsorption and removal of caffeine from tea samples - Yuwei Hua; Guangyang Liu; Zhihao Lin; Zhou Jie; Chenxi Zhao; Jiatong Han; Ge Chen; Linyun Li; Xiaodong Huang; Zhongxiao Liu; Jun Lv; Donghui Xu (Food Chemistry, 2024)

The brominated flame retardant tetrabromobisphenol A-bis(2,3-dibromo-2-methylpropyl ether) as well as hexabromocyclododecane lead to lipid disorders in mice - Xuan-Yue Chen; Yuan-Yuan Li; Lin Lv; Yi-Ming Xiong; Zhan-Fen Qin (Environmental Pollution, 2024)

Ammonium intercalation engineering regulated structural stability of V6O13 cathodes for durable zinc ion batteries - Ziang Wu; Jia Yao; Chi Chen; Xiang Chen; Xiaoxin Pan; Junjie Zheng; Yi Gan; Jingying Li; Xingtai Liu; Chao Xia; Lin Lv; Hao Wang; et al. (Chemical Engineering Journal, 2024)

Matrine Mediated Immune Protection in MS by Regulating Gut Microbiota and Production of SCFAs - Mengmeng Dou; Yaojuan Chu; Xueliang Zhou; Mengru Wang; Xinyu Li; Rui Ma; Zhirui Fan; Xiaoyu Zhao; Wenbin Wang; Silu Li; Ying Lv; Lin Zhu (Molecular Neurobiology, 2024)

Underwater Object Detection in Marine Ranching Based on Improved YOLOv8 - Rong Jia; Bin Lv; Jie Chen; Hailin Liu; Lin Cao; Min Liu (Journal of Marine Science and Engineering, 2023)
The aquaculture of marine ranching is of great significance for scientific aquaculture and the practice of statistically grasping existing information on the types of living marine resources and their density. However, underwater environments are complex, and there are many small and overlapping targets for marine organisms, which seriously affects the performance of detectors. To overcome these issues, we attempted to improve the YOLOv8 detector. The InceptionNeXt block was used in the backbone to enhance the feature extraction capabilities of the network. Subsequently, a separate and enhanced attention module (SEAM) was added to the neck to enhance the detection of overlapping targets. Moreover, the normalized Wasserstein distance (NWD) loss was proportionally added to the original CIoU loss to improve the detection of small targets. Data augmentation methods were used to improve the dataset during training to enhance the robustness of the network. The experimental results showed that the improved YOLOv8 achieved the mAP of 84.5%, which was an improvement over the original YOLOv8 of approximately 6.2%. Meanwhile, there were no significant increases in the numbers of parameters and computations. This detector can be applied on platforms for seafloor observation experiments in the field of marine ranching to complete the task of real-time detection of marine organisms.

Numerical Analysis of Dynamic Response and Liquefaction Phenomena in Sandy Seabed Foundation around a Semi-Circular Breakwater under Wave Loading - Junwei Liu; Yunping Jia; Lin Cui; Honglei Sun; Xu Lv; Mohsen Saleh Asheghabadi (Journal of Marine Science and Engineering, 2023)
Understanding the stability of the seabed foundation holds paramount significance in guaranteeing the safety and structural soundness of the breakwater alongside additional offshore structures. This study aimed to investigate the stability of a sandy seabed foundation around a semi-circular breakwater under wave loading in nearshore areas. A coupled numerical model of waves, a semi-circular breakwater, and the seabed was developed based on the OpenFOAM platform. The VARANS equations were used to govern the wave behavior. Meanwhile, the Biot’s partially dynamic model was employed to numerically simulate the seabed response considering both consolidation under self-weight and dynamic response under wave loading. The effects of various wave parameters, seabed properties, and the radius of the structure on the dynamic response of the seabed and the depth of liquefaction were investigated. The numerical results indicate that an increase in wave height, period, and permeability coefficient intensifies the dynamic response of the seabed soil. Furthermore, an increase in water depth weakened the soil’s dynamic response. There was a negative correlation between the radius of the semi-circular breakwater and the dynamic response. The influence of Poisson’s ratio on the dynamic response of the seabed was relatively small. Furthermore, a stronger dynamic pore pressure response was observed at the connection between the semi-circular breakwater and the rubble foundation.

Clinical characteristics and outcomes of patients with COVID-19 and tuberculosis coinfection - Jun Lv; Mengyu Liang; Lin Wang; Minmin Zhang; Renjie Liu; Han Liang; Chen Wang; Liuqun Jia; Qinglei Zeng; Pengfei Zhu (Infectious Diseases, 2023)

Association of glyphosate exposure with multiple adverse outcomes and potential mediators - Wenxiang Li; Daizai Lei; Guangyi Huang; Ningning Tang; Peng Lu; Li Jiang; Jian Lv; Yunru Lin; Fan Xu; Yuan-jun Qin (Chemosphere, 2023)

Self-assembly construction of 1D carbon nitride nanotubes and cobalt-modified for superior photocatalytic degradation of sulfonamide antibiotics - Zifeng Lin; Zhongquan Wang; Zihong Xu; Zhenjun Xiao; Zheng Fang; Jin Luo; Ping Li; Ping Chen; Wenying Lv; Guoguang Liu (Chemosphere, 2023)

The effect of novel aquaculture mode on phosphorus sorption-release in pond sediment - Juchen Xu; Jie Wang; Shen Lin; Liang Hou; Shuaibing Ma; Yabing Lv; Ruiya Chen; Xugang He; Jie Hou (Science of The Total Environment, 2023)

Selective recovery of lithium from spent lithium-ion batteries via mild hydrothermal driven Lewis acid-base reaction in aqua solution - Weiguang Lv; Jin Zhang; Yunpeng Liu; Jiao Lin; Xiaohong Zheng; Wenyi Yan; Hongbin Cao; Yi Zhang; Zhi Sun (Resources, Conservation and Recycling, 2023)

Modeling the long-term transport and fate of oil spilled from the 2021 A Symphony tanker collision in the Yellow Sea, China: Reliability of the stochastic simulation - Ruichen Cao; Zengrui Rong; Haibo Chen; Yi Liu; Lin Mu; Xianqing Lv (Ocean Modelling, 2023)

Algal strains, treatment systems and removal mechanisms for treating antibiotic wastewater by microalgae - Juan Peng; Kai-Lu Cao; Si-Bo Lv; Yu-Xuan Hu; Jia Lin; Qian-Zhi Zhou; Jiang-Hai Wang (Journal of Water Process Engineering, 2023)

Multi-objective optimization of gas-steam-power system for an integrated iron and steel mill considering carbon emission reduction and cost - Tingting Xu; Zhaoyi Huo; Tong Wang; Jiawei Lv; Yixuan Han; Lin Mu (Journal of Cleaner Production, 2023)

Study on Cu- and Pb-contaminated loess remediation using electrokinetic technology coupled with biological permeable reactive barrier - Lin Wang; Wen-Chieh Cheng; Zhong-Fei Xue; Yi-Xin Xie; Xin-Jiang Lv (Journal of Environmental Management, 2023)

Mapping trade-offs among key ecosystem functions in tidal marsh to inform spatial management policy for exotic Spartina alterniflora - Wenzhen Zhao; Xiuzhen Li; Liming Xue; Shiwei Lin; Yuxi Ma; Lin Su; Zeyuan Li; Lv Gong; Zhongzheng Yan; Peter I. Macreadie (Journal of Environmental Management, 2023)

Corrigendum to “Aroma characterisation of Liu-pao tea based on volatile fingerprint and aroma wheel using SBSE-GC-MS” [Food Chem. 414 (2023) 135739] - Wanjun Ma; Yin Zhu; Shicheng Ma; Jiang Shi; Han Yan; Zhi Lin; Haipeng Lv (Food Chemistry, 2023)

Antibacterial food packaging capable of sustained and unidirectional release carvacrol/thymol nanoemulsions for pork preservation - Lin Wang; Mengyuan Yuan; Enze Sun; Jiang Wu; Anboyuan Lv; Xu Zhang; Jiaxiang Guo; Yu Zhu; Hongbo Guo; Xiaozhou Li; Ke Wang (Food Hydrocolloids, 2023)

Molecular cloning, expression, and functional analysis of a putative lectin from the pearl oyster (Pinctada fucata, Gould 1850) - Peng Liu; Wenyue Li; Yue Peng; Siyin Han; Zhongxiu Liang; Yanhui Cen; Xinrong Li; Peiyan Wang; Huiying Lv; Qingying Zhang; Honglin Chen; Jiang Lin (Fish & Shellfish Immunology, 2023)

An integrated mycotoxin-mitigating agent can effectively mitigate the combined toxicity of AFB1, DON and OTA on the production performance, liver and oviduct health in broiler breeder hens - Meng-Ling Ruan; Jie Wang; Zhi-Yuan Xia; Xue-Wu Li; Bo Zhang; Guan-Lin Wang; Yuan-Yuan Wu; Yanming Han; Jiang Deng; Lv-Hui Sun (Food and Chemical Toxicology, 2023)

Highly sensitive metal-enhanced fluorescence platform based on high-quality CdSe/ZnS quantum dots and gold nanodendrites - Fangfang Chen; Ruixue Zhang; daman Que; Huanhuan Xing; Ning Li; Yihan Li; Yanbing Lv; Ruili Wu; Huaibin Shen; Dangdang Xu; Lin Song Li (Chemical Engineering Journal, 2023)

Polysaccharide from walnut green husk alleviates liver inflammation and gluconeogenesis dysfunction by altering gut microbiota in ochratoxin A-induced mice - Yang Yang; Linjie Lv; Shanshan Shi; Gaofeng Cai; Lin Yu; Shuwen Xu; Tianyu Zhu; Xinyue Su; Ningning Mao; Yue Zhang; Song Peng; Jin He; et al. (Carbohydrate Polymers, 2023)

Construction of molecular enrichment accelerators via assembly of enzyme surface grafted polymer and cyclodextrin achieving rapid and stable ester catalysis for biodiesel synthesis - Qi Ao; Lin Jiang; Xinglai Tong; Ying Song; Xiaoxiao Lv; Jun Tang (Carbohydrate Polymers, 2023)

Gas6 Promotes Microglia Efferocytosis and Suppresses Inflammation Through Activating Axl/Rac1 Signaling in Subarachnoid Hemorrhage Mice - Junjia Tang; Yichao Jin; Feng Jia; Tao Lv; Anatol Manaenko; Lin-Feng Zhang; Zeyu Zhang; Xin Qi; Yajun Xue; Bin Zhao; Xiaohua Zhang; John H. Zhang; et al. (Translational Stroke Research, 2023)

Low-dose IL-2 Treatment Rescues Cognitive Deficits by Repairing the Imbalance Between Treg and Th17 Cells at the Middle Alzheimer’s Disease Stage - Lin Yuan; Lei Xie; Hao Zhang; Yu Zhang; Yunbo Wei; Jinhong Feng; Li Cui; Rui Tian; Jia Feng; Di Yu; Cui Lv (Journal of Neuroimmune Pharmacology, 2023)

The Daily Intake Levels of Copper, Selenium, and Zinc Are Associated with Osteoarthritis but Not with Rheumatoid Arthritis in a Cross-sectional Study - Wei-ming Yang; Jiao-feng Lv; Yuan-yuan Wang; Yan-mei Xu; Jin Lin; Jing Liu; Juan-juan Chen; Xiao-zhong Wang (Biological Trace Element Research, 2023)

Variations of air temperature differences at different temporal scales over the Tibetan Plateau since 1961 and their possible causes - Jingjing Lin; Guangsheng Zhou; Qiang Zhang; Xiaomin Lv; Feng Fang; Guannan Zhao; Ting Miao (International Journal of Climatology, 2023)
The air temperature difference is an essential indicator to measure weather and climate change. The Tibetan Plateau (TP) is a sensitive area to global climate change. The study on its temperature difference variations is of great significance for further understanding the evolution of weather and climate systems, and scientific disaster prevention and mitigation. In this study, the spatio‐temporal evolution characteristics of the temperature difference on daily, monthly, seasonal and annual scales and their possible causes are analysed based on the daily observations at 59 meteorological stations over the TP from 1961 to 2020 and the circulation indexes such as the East Asian summer monsoon, South Asian summer monsoon, midlatitude westerly and TP summer monsoon. The results indicate that the diurnal temperature range (DTR) on the TP tends to decrease from 1961 to 2020. Compared with the situation in the late 20th century, the annual average of the DTR in the eastern TP turns from a nonsignificant increasing trend into a pronounced decreasing trend, while that in the western TP maintains a decreasing trend. This phenomenon is primarily influenced by the minimum and maximum temperature, precipitation and atmospheric circulations. The standardized temperature difference at different temporal scales shows decreasing trends and is distributed in north–south and east–west distribution patterns. The annual temperature range is mainly influenced by the remarkable increase of the minimum temperature, especially in the northern and southeastern TP. Besides, the increases of maximum temperature and precipitation also affect the annual temperature range. In terms of the seasonal temperature range, it is dramatically influenced by different meteorological factors, especially in the northern TP. The monthly temperature range (Mon‐TR) is dramatically influenced by the maximum and minimum temperature in the first and second half years, respectively. Moreover, the circulation systems, such as the midlatitude westerly, South Asian summer monsoon and TP summer monsoon, are the main influencing factors of the temperature difference variations on the TP. The midlatitude westerly have a large influence on Mon‐TR in June and September, and the significantly influenced stations reaches 54.2% and 35.6%. The impact stations of the TP summer monsoon on Mon‐TR is the largest in August, and the significantly influenced stations is 39%. In July, the influenced stations of the TP summer monsoon and South Asian summer monsoon on the Mon‐TR reaches 30.5%–33.9%. The influenced area of the Mon‐TR in June is largest affected by single summer monsoon or westerly index. Previous studies have shown that the warming mechanisms and their influencing factors have changed in the TP since the 21st century. The study results might provide the foundation for a scientific understanding of climate warming on the TP.

Peptidomic Analysis and Potential Bioactive Peptides Identification Targeting Endometrial Cancer - Hanzi Xu; Shenglong Yuan; Lin Zhou; Huixin Li; Juan Lv; Xiaoyan Shi; Wangfei Wu; Zhijian Feng; Zhen Gong (International Journal of Peptide Research and Therapeutics, 2023)

Low transplacental transfer of PFASs in the small-for-gestational-age (SGA) new-borns: Evidence from a Chinese birth cohort - Yijun Fan; Liyan Guo; Ruolan Wang; Jingjing Xu; Yuanyuan Fang; Wenxin Wang; Jia Lv; Weitian Tang; Hua Wang; De-Xiang Xu; Lin Tao; Yichao Huang (Chemosphere, 2023)

Hydroxyl-groups engineering of triazole-based polymers for efficient photocatalytic hydrogen peroxide production - Feng Lin; Zhaoyang Ju; Yao Li; Jia Liu; Liyong Ding; Haijie Ben; Yulin Wang; Yuechao Wu; Ying Lei; Huiming Zeng; Shaohong Zang; Jun Chen; et al. (Journal of Cleaner Production, 2023)

Facile preparation of nitrogen-doped microporous carbon from potassium citrate/urea for effective CH4 separation and uptake - Li Zhang; Yonggang Dong; Dan Zhang; Wenfei Li; Hong Qin; Ziming Luo; Yongyong Shi; Yutao Lv; Cuiwei Zhang; Hongyan Pan; Qian Lin (Fuel, 2023)

High-efficiency foam fractionation of anthocyanin from perilla leaves using surfactant-free active Al2O3 nanoparticle as collector and frother: Performance and mechanism - Lin Chen; Nan Hu; Chunquan Zhao; Xiaodan Sun; Rong Han; Yanyan Lv; Zhijun Zhang (Food Chemistry, 2023)

Selenium alleviates lead-induced CIK cells pyroptosis and inflammation through IRAK1/TAK1/IKK pathway - Xiunan Lv; Mengyao Ren; Tong Xu; Meichen Gao; Huanyi Liu; Hongjin Lin (Fish & Shellfish Immunology, 2023)

The disruption of blood-brain barrier induced by long-term arsenic exposure is associated with the increase of MMP-9 and MMP-2: The characteristics are similar to those caused by senescence - Man Lv; Xinbo Ma; Kunyu Zhang; Meichen Zhang; Yi Ji; Lin Cheng; Xinhua Shao; Ziqiao Guan; Jia Cui; Yanhui Gao; Yang Liu; Yanmei Yang; et al. (Chemico-Biological Interactions, 2023)

Changing maize hybrids helps adapt to climate change in Northeast China: revealed by field experiment and crop modelling - Jin Zhao; Zhijuan Liu; Shuo Lv; Xiaomao Lin; Tao Li; Xiaoguang Yang (Agricultural and Forest Meteorology, 2023)

Extended exposure to tetrabromobisphenol A-bis(2,3-dibromopropyl ether) leads to subfertility in male mice at the late reproductive age - Yuan-Yuan Li; Yi-Ming Xiong; Xuan-Yue Chen; Jia-Yi Sheng; Lin Lv; Xing-Hong Li; Zhan-Fen Qin (Archives of Toxicology, 2023)

Two new triterpenoid saponins from Bupleurum marginatum Wall. ex DC - Ke Luo; Rong-Ji Dai; Zhi Wang; Yan-Bo Zeng; Yu-Lin Deng; Fang Lv (Natural Product Research, 2023)

One-step synthesis of thiol-functionalized metal coordination polymers: effective and superfast removal of Hg (II) in the different matrices to ppb level - Mingzhi Li; Yongjie Tuo; Qiuxia Wu; Haiying Lin; Qingge Feng; Yu Duan; Junqi Wei; Zixuan Chen; Jiatong Lv; Lianghong Li (Chemosphere, 2023)

Effects of heavy metal exposure on hypertension: A machine learning modeling approach - Wenxiang Li; Guangyi Huang; Ningning Tang; Peng Lu; Li Jiang; Jian Lv; Yuanjun Qin; Yunru Lin; Fan Xu; Daizai Lei (Chemosphere, 2023)

Single-atom Zr embedded Ti4O7 anode coupling with hierarchical CuFe2O4 particle electrodes toward efficient electrooxidation of actual pharmaceutical wastewater - Anqi Wang; Xingxin Liu; Yukai Wen; Yongfu Qiu; Sihao Lv; Manman Xu; Cuilin Meng; Kai Wang; Fengjie Lin; Shuibo Xie; Qiongfang Zhuo (Water Research, 2023)

Interconnectedness between land resource misallocation and environmental pollution: Exploring the sustainable development potential in China - Feng Gao; Yijie Lin; Xuanming Zhang; Shanhong Li; Yanqin Lv (Resources Policy, 2023)

Adsorption and reduction behavior and mechanism of Au(III) on reductive cellulose-based aerogel - Rengui Weng; Guohong Chen; Yifan Liu; Yuancai Lv; Chunxiang Lin; Xiaoxia Ye; Minghua Liu (Process Safety and Environmental Protection, 2023)

Achievement of partial denitrification in SBR treating acidic wastewater: Performance and mechanism of nitrite accumulation - Yong-Tao Lv; Yuxuan Su; Meiting Li; Li Lin; XuDong Wang; Lei Wang (Journal of Water Process Engineering, 2023)

Strategy for improvement of molecular oxygen activation capacity of PPECu by chlorine doping for water decontamination - Yingyi Chen; Zili Lin; Jinfan Zhang; Yang Liu; Danluo Liang; Daguang Li; Yudan Zhang; Haijin Liu; Ping Chen; Wenying Lv; Guoguang Liu (Journal of Hazardous Materials, 2023)

Simplified synthesis of direct Z-scheme Bi2WO6/PhC2Cu heterojunction that shows enhanced photocatalytic degradation of 2,4,6-TCP: Kinetic study and mechanistic insights - Jinfan Zhang; Zili Lin; Zongshun Yu; Yudan Zhang; Danluo Liang; Yingyi Chen; Yu Chen; Ping Chen; Haijin Liu; Wenying Lv; Guoguang Liu (Journal of Hazardous Materials, 2023)

A real-time NO emission inventory from heavy-duty vehicles based on on-board diagnostics big data with acceptable quality in China - Zhaofeng Lv; Yingzhi Zhang; Zhe Ji; Fanyuan Deng; Mengshuang Shi; Qiwei Li; Miao He; Lin Xiao; Yingnan Huang; Huan Liu; Kebin He (Journal of Cleaner Production, 2023)

Chloride removal from sewage using bismuth trioxide: Characterization and optimization by response surface methodology (RSM) - Liangjing Zhang; Yu Wang; Yunlong Liu; Shucong Lv; Rui Wang; Xiaokun Hu; Yuchen Liu; Zhaojun Dong; Kuixuan Lin; Lusan Liu (Journal of Environmental Chemical Engineering, 2023)

Pd decorated MoS2 nanoflowers as photothermal catalyst for enhanced NIR-induced 4-nitrophenol reduction - Hanhan Lv; Min Lin; Chiyan Yu; Haifeng Wang; Maoquan Li; Lisha Zhang; Zixiao Liu; Zhigang Chen (Journal of Environmental Chemical Engineering, 2023)

Impact of COVID-19 pandemic on profiles of antibiotic-resistant genes and bacteria in hospital wastewater - Liang Zhao; Ziquan Lv; Liangqiang Lin; Xiaowei Li; Jian Xu; Suli Huang; Yuhua Chen; Yulin Fu; Changfeng Peng; Tingting Cao; Yuebin Ke; Xi Xia (Environmental Pollution, 2023)

A zinc-octacarboxylate MOF with an unusual (6, 8)-connected ocu topology for high-capacity adsorptive separation of C8 alkylaromatics - Xiuping Deng; Maojun Deng; Yu-Lin Li; Zewei Liu; Tian-Fu Liu; Xin Chen; Shuhan Cai; Biying Liu; Jiesen Li; Daofei Lv; Jing Li; Wenbing Yuan (Chemical Engineering Journal, 2023)

Benzeneboronic−alginate/quaternized chitosan−catechol powder with rapid self-gelation, wet adhesion, biodegradation and antibacterial activity for non-compressible hemorrhage control - Yan Du; Xingtao Chen; Lin Li; Heng Zheng; Aiping Yang; Hong Li; Guoyu Lv (Carbohydrate Polymers, 2023)

Trichoscopy for early diagnosis and follow-up of pet-related neonatal tinea capitis - Hui-Lin Zhi; Xiu-Jiao Xia; Hong Shen; Wen-Wen Lv; Yan Zhong; Bo Sang; Qiu-Ping Li; Ze-Hu Liu (Mycopathologia, 2023)

PLK3 promotes the proneural–mesenchymal transition in glioblastoma via transcriptional regulation of C5AR1 - Shuo Yu; Lin Lv; Yang Li; Qian Ning; Tingting Liu; Tinghua Hu (Molecular Biology Reports, 2023)

Co-exposure to iron, copper, zinc, selenium and titanium is associated with the prevention of gastric precancerous lesions - Tingting Wang; Fang Xu; Xiao Lin; Yaning Lv; Xiaohui Zhang; Wenli Cheng; Li Wang; Min Wang; Meng Zhang; Tao Xia; Shiqing Qian; Min Tang; et al. (BioMetals, 2023)

Tigliane-and daphnane-type diterpenoids from the buds of Daphne genkwa with their cytotoxic activities - Ying Chen; Cai-Lin Zhao; Wei Dong; Fei-Fan Song; Li-Na Guo; Hong-Lian Zhang; Lv Zhen; Li Li; Jin Ye; Bo Song (Natural Product Research, 2023)

Association between co-exposure to phenols, phthalates, and polycyclic aromatic hydrocarbons with the risk of frailty - Wenxiang Li; Guangyi Huang; Ningning Tang; Peng Lu; Li Jiang; Jian Lv; Yuanjun Qin; Yunru Lin; Fan Xu; Daizai Lei (Environmental Science and Pollution Research, 2023)

Net-chasing training improves the size homogeneous of freshwater prawn Macrobrachium rosenbergii reared at high stocking density through behavioral regulation - Jiangtao Li; Lingyun Yu; Sijia Xu; Li Lin; Xiaojing Lv (Aquaculture, 2023)

Association between PM2.5 exposure and the outcomes of ART treatment: A prospective birth cohort study - Yifan Wang; Yun Qiu; Bo Huang; Jiangbo Du; Liya Liu; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; et al. (Science of The Total Environment, 2023)

Mitochondrial RNA m3C methyltransferase METTL8 relies on an isoform-specific N-terminal extension and modifies multiple heterogenous tRNAs - Meng-Han Huang; Jin-Tao Wang; Jian-Hui Zhang; Xue-Ling Mao; Gui-Xin Peng; Xiuying Lin; Daizhu Lv; Chen Yuan; Huan Lin; En-Duo Wang; Xiao-Long Zhou (Science Bulletin, 2023)

Biomass-derived foams with three-dimensional hierarchical structure for efficient p-arsanilic acid removal - Xiaoxia Ye; Yi Lin; Wang Lin; Huiting Lin; Yuancai Lv; Chunxiang Lin; Yifan Liu; Jie Chen (Process Safety and Environmental Protection, 2023)

Key role of Fe(VI)-activated Bi2WO6 in the photocatalytic oxidation of sulfonamides: Mediated electron transfer mechanism - Yudan Zhang; Ping Chen; Wenying Lv; Zhenjun Xiao; Jinfan Zhang; Jianqing Wu; Zili Lin; Guangzhi Zhang; Zongshun Yu; Haijin Liu; Guoguang Liu (Journal of Hazardous Materials, 2023)

Copper removal and recovery from electroplating effluent with wide pH ranges through hybrid capacitive deionization using CuSe electrode - Shiyong Wang; Haohong Zhuang; Xiaoyan Shen; Lin Zhao; Zhihao Pan; Lizhi Liu; Sihao Lv; Gang Wang (Journal of Hazardous Materials, 2023)

Real world emission characteristics of Chinese fleet and the current situation of underestimated ship emissions - Lei Yang; Qijun Zhang; Zongyan Lv; Jingbo Zhao; Chao Zou; Ning Wei; Zhenyu Jia; Yanjie Zhang; Fei Fu; Jianhua Lv; Lin Wu; Ting Wang; et al. (Journal of Cleaner Production, 2023)

Particulate emissions from gasoline vehicles using three different fuel injection technologies - Zongyan Lv; Jianfei Peng; Jinsheng Zhang; Lei Yang; Dongping Guo; Ning Wei; Yajun Wu; Tiange Fang; Ainan Song; Chaoyang Fan; Lin Wu; Qijun Zhang; et al. (Journal of Cleaner Production, 2023)

Quantitative proteomics provides insights into the mechanism of the differences in heat-induced gel properties for egg white proteins with different interior quality during ageing in laying hens - Guang Li; Siyuan Mi; Qi Zeng; Lin Wang; Xingbo Liu; Ming Zhang; Zengpeng Lv; Yongguo Jin; Junyou Li; Yuming Guo; Bingkun Zhang (Food Chemistry, 2023)

Spatio-temporal distribution of organochlorine pesticides in agricultural soils of southeast China during 2014-2019 - Wei Zuo; Qin Lin; Xinju Liu; Lu Lv; Chunrong Zhang; Shenggan Wu; Xi Cheng; Yijun Yu; Tao Tang (Environmental Research, 2023)

Heavy vehicles’ non-exhaust exhibits competitive contribution to PM2.5 compared with exhaust in port and nearby areas - Tiange Fang; Ting Wang; Chao Zou; Quanyou Guo; Jianhua Lv; Yanjie Zhang; Lin Wu; Jianfei Peng; Hongjun Mao (Environmental Pollution, 2023)

The ionome and proteome landscape of aging in laying hens and relation to egg white quality - Guang Li; Yuqing Feng; Jian Cui; Qihang Hou; Tanfang Li; Meiting Jia; Zhengtian Lv; Qiuyu Jiang; Ying Wang; Ming Zhang; Lin Wang; Zengpeng Lv; et al. (Science China Life Sciences, 2023)

Slope stability analysis based on convolutional neural network and digital twin - Gongfa Chen; Wei Deng; Mansheng Lin; Jianbin Lv (Natural Hazards, 2023)

IRAK-M Ablation Promotes Status Epilepticus-Induced Neuroinflammation via Activating M1 Microglia and Impairing Excitatory Synaptic Function - Xiao-Shan Liang; Ting-Lin Qian; Yi-Fan Xiong; Xiao-Tao Liang; Yue-Wen Ding; Xiao-Yu Zhu; Yun-Lv Li; Jie-Li Zhou; Le-Yi Tan; Wei-Peng Li; Wei Xie (Molecular Neurobiology, 2023)

Long noncoding RNA XLOC_006786 inhibits the proliferation, invasion and metastasis of osteosarcoma cells through NOTCH3 signaling pathway by targeting miR-491-5p - Jia-Yi Xu; Yang-fan Lv; Ya Cao; Hong-min Ma; Xiang-lin Hao; Lu Huang; Xue-feng Tang; Qiao-nan Guo (Human Cell, 2023)

Updates on the chemistry, processing characteristics, and utilization of tea flavonoids in last two decades (2001-2021) - Jiang Shi; Gaozhong Yang; Qiushuang You; Shili Sun; Ruohong Chen; Zhi Lin; Jesus Simal-Gandara; Haipeng Lv (Critical Reviews in Food Science and Nutrition, 2023)

First report of Pestalotiopsis neolitseae causing leaf blight on Photinia × fraseri in China - Xiu-Lan Xu; Si-Yi Liu; Qian-Gang Xiao; Yi-Cong Lv; Ying-Gao Liu; Chun-Lin Yang (Journal of Plant Pathology, 2023)

Schizophrenia in the genetic era: a review from development history, clinical features and genomic research approaches to insights of susceptibility genes - Ye Lv; Lin Wen; Wen-Juan Hu; Chong Deng; Hui-Wen Ren; Ya-Nan Bao; Bo-Wei Su; Ping Gao; Zi-Yue Man; Yi-Yang Luo; Cheng-Jie Li; Zhi-Xin Xiang; et al. (Metabolic Brain Disease, 2023)

Association between prenatal exposure to trace elements mixture and visual acuity in infants: A prospective birth cohort study - Zijin Wang; Yuanyan Dou; Wenhui Guo; Yuan Lin; Yangqian Jiang; Tao Jiang; Rui Qin; Hong Lv; Qun Lu; Guangfu Jin; Hongxia Ma; Zhibin Hu; et al. (Chemosphere, 2023)

Persulfate promoted visible photocatalytic elimination of bisphenol A by g-C3N4–CeO2 S-scheme heterojunction: The dominant role of photo-induced holes - Yin Xu; Xin Tang; Yan Xiao; Huiling Tang; Heng Lin; Yujuan Lv; Hui Zhang (Chemosphere, 2023)

Potential food safety risk factors in plant-based foods: Source, occurrence, and detection methods - Xianfeng Lin; Nuo Duan; Jiajun Wu; Ziyu Lv; Zhouping Wang; Shijia Wu (Trends in Food Science & Technology, 2023)

Assessing the environmental sustainability of different soil disinfestation methods used in solar greenhouse vegetable production systems - Li Wan; Yiming Zhao; Longlong Xia; Jing Hu; Tongxin Xue; Haofeng Lv; Zhisheng Yao; Fanqiao Meng; Guoyuan Li; Shan Lin; Klaus Butterbach-Bahl (Science of The Total Environment, 2023)

A new insight into the CaO-induced inhibition pathways on PCDD/F formation: Metal passivation, dechlorination and hydroxide substitution - Xiaoxiao Wang; Jiabao Lv; Yuxuan Ying; Yunfeng Ma; Angjian Wu; Xiaoqing Lin; Ang Cao; Xiaodong Li; Jianhua Yan (Science of The Total Environment, 2023)

Dual-targeting lanthanide-ICG-MOF nanoplatform for cancer Theranostics: NIR II luminescence imaging guided sentinel lymph nodes surgical navigation - Bi Lin; Ruiyi Dai; Zhenghao Liu; Wenjing Li; Jingwen Bai; Guojun Zhang; Ruichan Lv (Journal of Photochemistry and Photobiology B: Biology, 2023)

Enhanced photochemical degradation and transformation of ciprofloxacin in a UV/calcium peroxide system: pH effects, defluorination kinetics, and different components numerical analysis - Zheng Fang; Zifeng Lin; Ping Chen; Mengying Feng; Haijin Liu; Zhenjun Xiao; Zili Lin; Dagaung Li; Dezhu Liu; Yudan Zhang; Wenying Lv; Guoguang Liu (Journal of Cleaner Production, 2023)

Homoacetogenesis is altering the metabolic pathway of acidogenic microbiome and combating volatile fatty acid accumulation in anaerobic reactors - Zunjing Lv; Xiaofang Pan; Zhi-Long Ye; Irini Angelidaki; Nan Lv; Yanlin Li; Guanjing Cai; Lifeng Lin (Journal of Environmental Chemical Engineering, 2023)

Mitigating the adverse effects of Aflatoxin B1 in LMH, IPEC-J2 and 3D4/21 cells by a novel integrated agent - Yi-Xin Mo; Meng-Ling Ruan; Jie Wang; Ying Liu; Yuan-Yuan Wu; Guan-Lin Wang; Yan-Ming Han; Hai-Feng Wan; Dessalegn Lamesgen; Kamil Kuča; Jiang Deng; Lv-Hui Sun (Food and Chemical Toxicology, 2023)

Concatenated dynamic DNA network modulated SERS aptasensor based on gold-magnetic nanochains and Au@Ag nanoparticles for enzyme-free amplification analysis of tetracycline - Yan Lv; Shuo Qi; Imran Mahmood Khan; Xiaoze Dong; Mingwei Qin; Lin Yue; Yin Zhang; Zhouping Wang (Analytica Chimica Acta, 2023)

A cathodic photoelectrochemical biosensor based on CRISPR/Cas12a trans-cleavage mediated p-n heterojunction quenching mode for microRNA determination - Mengwei Lv; Chengxue Zong; Xiaodong Chen; Xiaojia Lin; Linghui Kong; Chunxiang Li (Analytica Chimica Acta, 2023)

Drip fertigation with straw incorporation promotes soil microbial network complexity and potentially reduces pathogen abundance in greenhouse vegetable production systems - Jing Hu; Yifei Sun; Meiju Liu; Yiming Zhao; Haofeng Lv; Yafang Wang; Guoyuan Li; Jingguo Wang; Klaus Butterbach-Bahl; Shan Lin (Agriculture, Ecosystems & Environment, 2023)

The interference between effects of PFAS exposure on thyroid hormone disorders and cholesterol levels: an NHANES analysis - Liang Zheng; Zhecun Wang; Rui Yang; Wanna Chen; Jing Zhang; Ruixia Li; Weiming Lv; Bo Lin; Jiajun Luo (Environmental Science and Pollution Research, 2023)

Highly efficient removal of rare earth elements by two-dimensional titanium carbide nanosheets as impacted via water chemistry - Yinzhi Lv; Lin Chen; Anning Zhang; Guodong Sheng; Qing Liao (Environmental Science and Pollution Research, 2023)

Effect of chemical regulation combined with mechanical filtration on deep dewatering and consolidation characteristics of sludge - Feng Lin; Weihua Qin; Jiongxian Wei; Jiangtao Lv; Peng Yang (Environmental Science and Pollution Research, 2023)

Benzo(a)pyrene regulates chaperone-mediated autophagy via heat shock protein 90 - Min Su; Shuhong Zhou; Jun Li; Nan Lin; Tao Chi; Mengdi Zhang; Xiaoli Lv; Yuxia Hu; Tuya Bai; Fuhou Chang (Toxicology Letters, 2023)

A hybrid safety monitoring framework for industrial FCC disengager coking rate based on FPM, CFD, and ML - Mengxuan Zhang; Zhe Yang; Yunpeng Zhao; Mingzhu Lv; Xingying Lan; Xiaogang Shi; Jinsen Gao; Chuankun Li; Zhuang Yuan; Yang Lin (Process Safety and Environmental Protection, 2023)

Effective adsorption and removal of malachite green and Pb2+ from aqueous samples and fruit juices by pollen–inspired magnetic hydroxyapatite nanoparticles/hydrogel beads - Yuwei Hua; Donghui Xu; Zhongxiao Liu; Jie Zhou; Jiatong Han; Zhihao Lin; Dan Xu; Ge Chen; Xiaodong Huang; Jing Chen; Jun Lv; Guangyang Liu (Journal of Cleaner Production, 2023)

A biomass fiber adsorbent grafted with phosphate/amidoxime for efficient extraction of uranium from seawater by synergistic effect - Xiaoxia Ye; Ruiyang Chi; Zhihao Wu; Jinteng Chen; Yuancai Lv; Chunxiang Lin; Yifan Liu; Wei Luo (Journal of Environmental Management, 2023)

Suppression mechanism of L-lysine on the Epigallocatechin-3-gallate-induced loss of myofibrillar protein gelling potential - Mengyuan Wang; Jingchao Kang; Lin Chen; Gongchen He; Yaping Liu; Xiaojing Fan; Xin Lv; Xinglian Xu; Guanghong Zhou; Xianchao Feng (Food Research International, 2023)

Enantiomeric separation and precise quantification of chiral volatiles in Wuyi rock teas using an efficient enantioselective GC × GC-TOFMS approach - Yue Zhang; Yu-Hui Zhang; Han Yan; Chen-Yang Shao; Wei-Xuan Li; Hai-Peng Lv; Zhi Lin; Yin Zhu (Food Research International, 2023)

Aroma characterisation of Liu-pao tea based on volatile fingerprint and aroma wheel using SBSE-GC–MS - Wanjun Ma; Yin Zhu; Shicheng Ma; Jiang Shi; Han Yan; Zhi Lin; Haipeng Lv (Food Chemistry, 2023)

Hyoscyamine induces developmental toxicity by disrupting metabolism in zebrafish embryo (Danio rerio) - Yinni Lv; Zhanyu Lin; Jingpei Chen; Kecheng Jiang; Anli Wang; Binjie Wang; Yuanzhao Wu; Zhongshi Xu; Jiye Wang; Weixuan Yao (Food and Chemical Toxicology, 2023)

Establishment of a lipopolysaccharide-induced inflammation model of human fetal colon cells - Keqi Yu; Shengtao Liao; Chuanfei Li; Ya Song; Zhechuan Mei; Lin Lv (Molecular Biology Reports, 2023)

Sludge source-redox mediators obtainment and availability for enhancing bioelectrogenesis and acidogenesis: Deciphering characteristics and mechanisms - Xiaodong Xin; Jiaqian Xie; Yanfang Wang; Lin Li; Wei Li; Sihao Lv; Zhidan Wen; Junguo He; Ying Xin (Water Research, 2023)

Newcastle disease virus activates methylation-related enzymes to reprogram m6A methylation in infected cells - Weifeng Yuan; Yuechi Hou; Qingyi Wang; Ting Lv; Jinlian Ren; Lei Fan; Juncheng Cai; Bin Xiang; Qiuyan Lin; Ming Liao; Chan Ding; Libin Chen; et al. (Veterinary Microbiology, 2023)

Degradation reduces greenhouse gas emissions while weakening ecosystem carbon sequestration of Moso bamboo forests - Ning Yuan; Enhui Wang; Shaofeng Lv; Xiaoping Tang; Tongying Wang; Gang Wang; Yufeng Zhou; Guomo Zhou; Yongjun Shi; Lin Xu (Science of The Total Environment, 2023)

Sampling period and disease severity of bacterial wilt significantly affected the bacterial community structure and functional prediction in the sesame rhizosphere soil - Ruiqing Wang; Fengjuan Lv; Rujie Lv; Hongxin Lin; Zhihua Zhang; Lingen Wei (Rhizosphere, 2023)

Solar-driven wastewater treatment coupled with hydrogen and electricity production via a bismuth-doped TiO2 nanorod array - Beibei Gao; Jing Tan; Yuhan Cao; Qingsong Zhang; Yanjun Wen; Qingming Zeng; Guolong Tang; Junwen Lv; Lin Wang; Qingyi Zeng (Journal of Environmental Chemical Engineering, 2023)

Preparation of Single-Ni atom active points by anchoring Anderson polyoxometalate in HKUST-1 for efficient Symmetric/ Asymmetric device energy storage and electrocatalytic overall water splitting - Yu Liang; Hongquan Jiang; Hong Lin; Chunmei Wang; Kai Yu; Chunxiao Wang; Jinghua Lv; Baibin Zhou (Chemical Engineering Journal, 2023)

Hierarchical phosphorus-oxygen incorporated cobalt sulfide hollow micro/nano-reactor for highly-efficient electrocatalytic overall water splitting - Ben Chong; Mengyang Xia; Yang Lv; He Li; Xiaoqing Yan; Bo Lin; Guidong Yang (Chemical Engineering Journal, 2023)

Deletion of the cheZ gene results in the loss of swimming ability and the decrease of adhesion ability to Caco-2 cells in Escherichia coli Nissle 1917 - Bingming Ou; Haihui Lv; Hua Ge; Dexiang Fu; Xin Lin; Saiqiao Huang; Xiaojie Chen; Yufu Liu; Sainan Li; Wenhua Liu; Lihua Huang; Ying Yang; et al. (Folia Microbiologica, 2023)

Distribution of polycyclic aromatic hydrocarbons in indoor/outdoor window films and the indoor film/air partition of northeastern Chinese college dormitories - Yu Sun; Li-Yan Liu; Lin-Lin Lv; Xi-Xi Zhou; Yu-Yan Luo; Jin-Ze Qu; Wan-Li Ma; Zi-Feng Zhang; Li Song; Li Wang; Yi-Fan Li (Chemosphere, 2023)

Insight into the genetic basis of ammonia tolerance in razor clam Sinonovacula constricta by genome-wide association study - Liyuan Lv; Chenxin Hu; Hongqiang Xu; Jianfen Ren; Biao Wu; Yinghui Dong; Zhihua Lin (Aquaculture, 2023)

Fabrication of covalent organic frameworks modified nanofibrous membrane for efficiently enriching and detecting the trace polychlorinated biphenyls in water - Yuancai Lv; Jiachen Ma; Zhendong Yu; Shuting Liu; Guifang Yang; Yifan Liu; Chunxiang Lin; Xiaoxia Ye; Yongqian Shi; Minghua Liu (Water Research, 2023)

Monomethylarsonous acid binds to Cys-104α and Cys-112β of hemoglobin in acute promyelocytic leukemia patients treated with arsenic trioxide - Chunlu Gao; Liwang Lin; Jing Li; Mengliang Wu; Jian Lv; Shuo Tian; Xin Hai (Toxicology Letters, 2023)

Feasibility study of applying electrokinetic technology coupled with enzyme-induced carbonate precipitation treatment to Cu- and Pb-contaminated loess remediation - Lin Wang; Wen-Chieh Cheng; Zhong-Fei Xue; Yi-Xin Xie; Xin-Jiang Lv (Journal of Cleaner Production, 2023)

In-situ gastritis diagnosis by an oral-administration NIR fluorescent probe with a large Stokes shift and high signal-to-noise ratio - Yanyan Ma; Jie Niu; Xing Liang; Lin Wang; Yimeng Zhang; Hongmin Lv; Tao Wang; Jing Wang; Xiaonan Zhang; Shanshan Xu; Qing Zhu; Zike Jiang; et al. (Chemical Engineering Journal, 2023)

In-situ construction of hexagonal-star-shaped MnCo2S4@MoS2 boosting overall water splitting performance at large-current-density: Compositional-electronic regulation, functions, and mechanisms - Tiantian Ma; Xueran Shen; Qingze Jiao; Yun Zhao; Hansheng Li; Yaoyuan Zhang; Yuzhen Lv; Caihong Feng; Lin Guo (Chemical Engineering Journal, 2023)

Upcycling of nickel iron slags to hierarchical self-assembled flower-like photocatalysts for highly efficient degradation of high-concentration tetracycline - Zhen Wu; Mengye Wang; Yang Bai; Han Song; Jiaxin Lv; Xiaofeng Mo; Xiaoqin Li; Zhang Lin (Chemical Engineering Journal, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Quercetin alleviates tubulointerstitial inflammation by inhibiting exosomes-mediated crosstalk between tubular epithelial cells and macrophages - Di Yin; Jing-Yuan Cao; Yan Yang; Zhong-Tang Li; Hong Liu; Tao-Tao Tang; Wei-Jie Ni; Yi-Lin Zhang; Wei Jiang; Yi Wen; Zuo-Lin Li; Jing Zhao; et al. (Inflammation Research, 2023)

The ginsenoside Rh2 protects porcine oocytes against aging and oxidative stress by regulating SIRT1 expression and mitochondrial activity - Hongye Liu; Zhi-Yong An; Zhou-Yan Li; Liu-Hui Yang; Xiu-Li Zhang; Yan-Tong Lv; Xi-Jun Yin; Lin-Hu Quan; Jin-Dan Kang (Theriogenology, 2023)

Preparation of multi-layered microcapsule-shaped activated biomass carbon with ultrahigh surface area from bamboo parenchyma cells for energy storage and cationic dyes removal - Yao Xia; Haifeng Zuo; Jialin Lv; Siyuan Wei; Yuxuan Yao; Zhigao Liu; Qiuqin Lin; Yanglun Yu; Wenji Yu; Yuxiang Huang (Journal of Cleaner Production, 2023)

An overview on constructed wetland-microbial fuel cell: Greenhouse gases emissions and extracellular electron transfer - Liangjing Zhang; Yunlong Liu; Shucong Lv; Rui Wang; Yu Wang; Kuixuan Lin; Xiaokun Hu; Yuchen Liu; Zhaojun Dong; Lusan Liu (Journal of Environmental Chemical Engineering, 2023)

Rapid degradation of PFOA by the activated peroxymono-sulfate with FeCo/MoS2 catalyst - Yuancai Lv; Shiyu He; Shuting Liu; Zhendong Yu; Yanting Jiang; Yihui Hu; Yifan Liu; Chunxiang Lin; Xiaoxia Ye; Guifang Yang; Minghua Liu (Journal of Environmental Chemical Engineering, 2023)

Dual photoluminescence emission carbon dots for ratiometric optical dual-mode and smartphone-integrated visual detection of mercury ion - Dan Chang; Lin Li; Xiaorui Dong; Hu Shi; Shuo Wang; Zhonghua Zhao; Liuliu Lv; Yongxing Yang; Lihong Shi (Journal of Environmental Chemical Engineering, 2023)

First detection of tet(X4)-positive Enterobacterales in retail vegetables and clonal spread of Escherichia coli ST195 producing Tet(X4) in animals, foods, and humans across China and Thailand - Chao Yue; Xun Gao; Litao Lu; Yi-Yun Liu; Lu-Chao Lv; Xiaotong He; Guolong Gao; Yanxiang Jiao; Huiying Yue; Wannan Lin; Jian-Hua Liu (International Journal of Food Microbiology, 2023)

Antioxidant soy peptide can inhibit xanthine oxidase activity and improve LO2 cell damage - Yifei Dong; Na Sun; Qi Ge; Renzhi Lv; Songyi Lin (Food Bioscience, 2023)

Ultra-efficient adsorption of diclofenac sodium on fish-scale biochar functionalized with H3PO4 via synergistic mechanisms - Jia Xie; Minghua Liu; Miao He; Yifan Liu; Jian Li; Fangxia Yu; Yuancai Lv; Chunxiang Lin; Xiaoxia Ye (Environmental Pollution, 2023)

Recent advances in photochemical transformations using water as an oxygen source - Yan Liu; Lin Zuo; Qiyan Lv; Bing Yu (Current Opinion in Green and Sustainable Chemistry, 2023)

Activating α7nAChR helps post-myocardial infarction healing by regulating macrophage polarization via the STAT3 signaling pathway - Xiao-Hui Niu; Rong-Hua Liu; Xiao Lv; Rui-Lin He; Fang-Zhou Lv; Shu-Jie Wu; Xu-Qing Li; Lei Li; Jia-Feng Lin (Inflammation Research, 2023)

Spatiotemporal analysis and prediction of water quality in Pearl River, China, using multivariate statistical techniques and data-driven model - HaoNan Ding; Xiaojun Niu; Dongqing Zhang; Mengyu Lv; Yang Zhang; Zhang Lin; Mingli Fu (Environmental Science and Pollution Research, 2023)

Identifying spatial agglomeration and driving forces of land use by green industries: a case study of Jiangsu Province, China - Qi Wang; Xiao-feng Zhao; Sheng-Hau Lin; Xian-jin Huang; Jian-cheng Lv (Environmental Science and Pollution Research, 2023)

The evolution and determinants of Chinese inter-provincial green development efficiency: an MCSE-DEA-Tobit-based perspective - Lin Yang; Zhanxin Ma; Jie Yin; Yiming Li; Haodong Lv (Environmental Science and Pollution Research, 2023)

Foreign direct investment, geographic condition, and their influence on haze pollution: evidence from prefecture-level cities in China - Jie Lv; Yingjie Zheng; Lin Li; Zhenkun Wei; Yizhang Li (Environment, Development and Sustainability, 2023)

Leonurine improves bovine oocyte maturation and subsequent embryonic development by reducing oxidative stress and improving mitochondrial function - Lv Zheng; Yuwen Luo; Dan Zhou; Hongyu Liu; Guizhen Zhou; Lin Meng; Yunpeng Hou; Changbin Liu; Jun Li; Xiangwei Fu (Theriogenology, 2023)

Associations of per- and polyfluoroalkyl substances and their alternatives with bone mineral density levels and osteoporosis prevalence: A community-based population study in Guangzhou, Southern China - Shujun Fan; Yan Wu; Michael S. Bloom; Jiayun Lv; Li Chen; Weiping Wang; Zhi Li; Qinqin Jiang; Li Bu; Jie Shi; Tongxing Shi; Xiaowen Zeng; et al. (Science of The Total Environment, 2023)

Corrigendum to “Induction of core symptoms of autism spectrum disorders by in vivo CRISPR/Cas9-based gene editing in the brain of adolescent rhesus monkeys” [Sci. Bull. 66(9) (2021) 937–946] - Shi-Hao Wu; Xiao Li; Dong-Dong Qin; Lin-Heng Zhang; Tian-Lin Cheng; Zhi-Fang Chen; Bin-Bin Nie; Xiao-Feng Ren; Jing Wu; Wen-Chao Wang; Ying-Zhou Hu; Yi-lin Gu; et al. (Science Bulletin, 2023)

A self-powered wearable piezoelectric nanogenerator for physiological monitoring based on lead zirconate titanate/microfibrillated cellulose@polyvinyl alcohol (PZT/MFC@PVA) composition - Yanfang Guan; Mingyang Bai; Qilong Wang; Lei Liu; Shaobo Yu; Bingru Kong; Feng Lv; Mingshuo Guo; Guangyu Liu; Lingfeng Li; Lin Zhang; Yang Lin; et al. (Chemical Engineering Journal, 2023)

Locking-DNA network regulated CRISPR-Cas12a fluorescent aptasensor based on hollow flower-like magnetic MoS2 microspheres for sensitive detection of sulfadimethoxine - Yan Lv; Yuhan Sun; Imran Mahmood Khan; Qiaofeng Li; You Zhou; Lin Yue; Yin Zhang; Zhouping Wang (Chemical Engineering Journal, 2023)

Simulated impacts of the wetter arid area of Northwestern China on the energy budget and atmospheric circulation over Tibetan Plateau and central part of North China plain in summer - Di Ma; Xianhong Meng; Shihua Lv; Yaohui Li; Haipeng Yu; Lele Shu; Lin Zhao; Zhaoguo Li (Atmospheric Research, 2023)

Transcriptome profiling reveals the roles of pigment formation mechanisms in yellow Paeonia delavayi flowers - Hongzhu Zou; Lin Zhou; Lulu Han; JiHang Lv; YingHua Jia; Yan Wang (Molecular Genetics and Genomics, 2023)
The yellow colour of ornamental varieties of tree peony originated from Paeonia delavayi . However, but P. delavayi and Paeonia suffruticosa belong to different subgroups, so hybridization is difficult and results in a long breeding cycle. However, no comprehensive transcriptomic profiling has focused on the colour formation mechanisms of yellow tree peony petals. Analysing the colour formation mechanism of yellow petals in P. delavayi is very important for directional molecular breeding. In this study, the transcriptional map of yellow pigment development in petals was used to analyse the mechanism of petal colour formation. We analysed the genes related to the metabolism of flavonoids and carotenoids and the transcription factors (TFs) involved in P. delavayi var. lutea (pure yellow individual) yellow pigment development using transcriptome sequence profiling. Transcriptome sequence profiles revealed three and four differentially expressed transcripts (DETs) involved in flavonoid biosynthesis and carotenoid biosynthesis, respectively. An analysis of DETs in the flavonoid pathway showed that chalcone synthase ( CHS ) and chalcone 2´-glucosyltransferases (THC 2’GT ) act in synergy to synthesize isosalipurposide (ISP). CHS and flavonol synthase ( FLS ) synergistically synthesize quercetin and kaempferol. DEG analysis of the carotenoid pathway revealed that phytoene synthase ( PSY ), carotenoid isomerase ( CRTISO ) and β-carotene hydroxylases ( CHYB ) play a key role in regulating lutein formation, and carotenoid cleavage dioxygenase ( CCD ) plays an important role in the degradation of carotenoids. These two pathways may be regulated by TF families such as bHLH , ARF , and MYB . The results of the transient overexpression of genes showed that CHS and CHI are regulated by PdMYB2 . In this study, the molecular mechanism of ISP synthesis was analysed in depth, and the complete metabolic pathway of carotenoids in Paeonia L. was reported for the first time. By studying the formation mechanism of yellow pigment in P. delavayi petals, a breeding strategy for improving flavonol and carotenoid contents and reducing anthocyanin synthesis by genetic engineering was suggested.

Towards effective wildlife protection law for marine species in China: A stakeholders’ perspective - Kit Yue Kwan; Ruifang Chen; Chun-Chieh Wang; Shuhao Lin; Lv Wu; Xiaoyong Xie; Zhaohong Weng; Menghong Hu; Haichao Zhou; Zhou Wu; Yijian Fu; Wenquan Zhen; et al. (Frontiers in Marine Science, 2023)
Introduction As one of the megadiverse countries, the effectiveness of wildlife protection in China is of great significance to global biodiversity conservation. With continued evolution and revisions, China’s Wildlife Protection Law has listed over 140 marine species; however, it is still inclined toward terrestrial animals. Methods To narrow the gap between compliance and enforcement, we collected 1,309 effective responses from various coastal cities of China through an anonymous online questionnaire survey, to investigate their exposure, understanding and attitudes toward Wildlife Protection Law for marine species (mWPL). Results Most respondents demonstrated an overall good understanding about the context, necessity and effectiveness of mWPL. The fisher communities were found to be more aware of the dissemination and implementation of mWPL. However, they understood less of the penal system, and exhibited negative attitudes toward the necessity and punishment of the legislation, probably due to the conflicts between resource utilizations and legislative interventions. The participants also indicated that seahorses, horseshoe crabs and corals were commonly subjected to illegal exploitations. Discussion While most respondents suggested greater fines, tighter laws and better public enforcement, we advocate the exploration of bottom-up options such as community engagement and environmental education to improve compliance and implementation of mWPL for the benefit of marine wildlife conservation in China.

Nicosulfuron stress on the glyoxalase system and endogenous hormone content in sweet maize seedlings - Zhen-Xing Wu; Jian Wang; Xiao-Hu Lin; Qing Yang; Ting-Zhen Wang; Jian-Jian Chen; Xiang-Nan Li; Yuan Guan; Gui-Hua Lv (Environmental Science and Pollution Research, 2023)

Exploring the driving factors of haze events in Beijing during Chinese New Year holidays in 2020 and 2021 under the influence of COVID-19 pandemic - Lining Luo; Xiaoxuan Bai; Yunqian Lv; Shuhan Liu; Zhihui Guo; Wei Liu; Yan Hao; Yujiao Sun; Jiming Hao; Kai Zhang; Hongyan Zhao; Shumin Lin; et al. (Science of The Total Environment, 2023)

Comparison of CO2, NOx, and VOCs emissions between CNG and E10 fueled light-duty vehicles - Zongyan Lv; Lin Wu; Chao Ma; Luna Sun; Jianfei Peng; Lei Yang; Ning Wei; Qijun Zhang; Hongjun Mao (Science of The Total Environment, 2023)

A new catalyst CHCP-Fe2O3 for enhanced removal of tetracycline through the Fenton-like process: Economical synthesis, catalytic performance, and practicability - Jiao He; Baoyou Pei; Chenglong Deng; Dongha Huang; Bihong Lv; Cheng Peng; Genggeng Luo; JinQing Lin (Journal of Water Process Engineering, 2023)

Facile synthesis of direct Z-scheme UiO-66-NH2/PhC2Cu heterojunction with ultrahigh redox potential for enhanced photocatalytic Cr(VI) reduction and NOR degradation - Zili Lin; Yuliang Wu; Xiaoyu Jin; Danluo Liang; Yuhan Jin; Shoubin Huang; Zhongquan Wang; Haijin Liu; Ping Chen; Wenying Lv; Guoguang Liu (Journal of Hazardous Materials, 2023)

Process design, modeling and life cycle analysis of energy consumption and GHG emission for jet fuel production from bioethanol in China - Xiao Wang; Lin Guo; Jing Lv; Maoshuai Li; Shouying Huang; Yue Wang; Xinbin Ma (Journal of Cleaner Production, 2023)

Studies on micromorphology and permeability of hydrate-bearing porous media - Gang Li; Yi-Fan Weng; Xiao-Sen Li; Ze-Lin Xu; Qiu-Nan Lv; Chun-Gang Xu (Fuel, 2023)

Effect of Saccharomyces cerevisiae LXPSC1 on microorganisms and metabolites of sour meat during the fermentation - Jing Lv; Xinping Lin; Mengyang Liu; Xu Yan; Huipeng Liang; Chaofan Ji; Shengjie Li; Sufang Zhang; Yingxi Chen; Beiwei Zhu (Food Chemistry, 2023)

Joint effects of per- and polyfluoroalkyl substance alternatives and heavy metals on renal health: A community-based population study in China - Li-Xia Liang; Pengxin Dong; Yang Zhou; Lin Zhang; Zhengmin Qian; Sarah Dee Geiger; Elizabeth Bingheim; Xiaojiang Tang; Yan Wu; Jiayun Lv; Li-Zi Lin; Mohammed Zeeshan; et al. (Environmental Research, 2023)

Immobilizing of lead and copper using chitosan-assisted enzyme-induced carbonate precipitation - Lin Wang; Wen-Chieh Cheng; Zhong-Fei Xue; Bin Zhang; Xin-Jiang Lv (Environmental Pollution, 2023)

Synergizing Fenton oxidation and in-situ coagulation over a wide pH range for the simultaneous removal of multiple pollutants - Ruoyun Lin; Fangjie Lv; Hao Zhang; Yang Li; Jiangang Lu; Jiansheng Li (Chemical Engineering Journal, 2023)

Analytical stress solution for cold region tunnels with unequal ground stress and support delay under different frost heave conditions of surrounding rock - Zhitao Lv; Shiqing Yuan; Hai Lin (Cold Regions Science and Technology, 2023)

In situ phytostabilization of arable soils severely contaminated with cadmium at Yangshuo, Southern China, using cash crops and amendments: a comprehensive performance evaluation - Bo-Fang Yan; Mei-Lin Yan; Xue Xiao; Rong-Liang Qiu; Yuan-Qing Chao; Yin-Xin Li; Su-Lian Lv; Zhong-Xin Tan; Ye-Tao Tang (Journal of Soils and Sediments, 2023)

The linear behavior of the joint initial-boundary-value predictability of the climate system - Jianlin Yong; Shaoqing Zhang; Zhengyu Liu; Yang Gao; Lixin Wu; Jianping Li; Lv Lu; Yingjing Jiang; Xiaolin Yu; Mingkui Li; Haoran Zhao; Xiaopei Lin (Climate Dynamics, 2023)

Sodium Fluoride and Sulfur Dioxide Derivatives Induce TGF-β1-Mediated NBCe1 Downregulation Causing Acid–Base Disorder of LS8 Cells - Ying Lv; Wentai Wang; Lili Yao; Jiaojiao He; Guohui Bai; Changhu Lin; Chenglong Tu (Biological Trace Element Research, 2023)

Experimental study on failure law of subgrade concrete with different damage base - Xiangfeng Lv; Lingfeng Meng; Xin Lin; Xuan Ji; Yahan Yang (European Journal of Environmental and Civil Engineering, 2023)

Tire wear particles: An emerging threat to soil health - Jing Ding; Min Lv; Dong Zhu; Eva F. Leifheit; Qing-Lin Chen; Yun-Qing Wang; Ling-Xin Chen; Matthias C. Rillig; Yong-Guan Zhu (Critical Reviews in Environmental Science and Technology, 2023)

Effect of wind on summer chlorophyll-a variability in the Yellow Sea - Lei Lin; Dongyan Liu; Yueqi Wang; Ting Lv; Yue Zhao; Wei Tan (Frontiers in Marine Science, 2023)
Winds potentially affect primary production in shelf seas during the stratified season by enhancing upwelling and mixing. However, the exact extent and modalities of this effect in the Yellow Sea remain unclear. Here, based on the satellite and in situ observation data, statistical method, and wind-driven upwelling theory, we examined the wind effect on the chlorophyll-a (Chl-a) variability in the summer of 2002-2020 and the effect mechanism. The satellite data revealed a significantly positive correlation between anomalies of the monthly mean of the summer sea surface Chl-a and wind speed at the continental slope region (water depth of 20-60 m) in the southwestern Yellow Sea where strong wind-driven upwelling has been indicated by previous studies. The wind-driven upwelling along the continental slope was further verified using two summer in-situ observations. After a fortnight of southeasterly wind, the upwelling patterns of high salinity and rich nutrients from the Yellow Sea cold water mass were observed, and consequently, high Chl-a concentrations occurred in the upper layer of the slope region. The wind-driven upwelling occurred in the region at water depth of ~20-60 m, which is consistent with the result of the wind-driven coastal upwelling theory (0.5 D < water depth < 1.25 D , where D is the thickness of the Ekman layer). The dissolved inorganic nitrogen, phosphorus, and silicate fluxes contributed by wind-driven upwelling were estimated as 1345 ± 674 μmol/m 2 /d, 81 ± 45 μmol/m 2 /d and 1460 ± 899 μmol/m 2 /d, respectively, accounting for 30%-40% of total nutrient supply, and were several times larger than that contributed by the turbulent mixing, which can explain why the strong wind-Chl-a correlation only occurred at the upwelling region rather than the entire sea. In addition, in this region, the interannual variability of the summer mean Chl-a was negatively correlated to both the Pacific Decadal Oscillation (PDO) and El Niño-Southern Oscillation (ENSO) indexes, due to the opposite phase of the summer wind anomaly and the PDO/ENSO. This study revealed the wind effect on the shelf phytoplankton is regional and highlighted that wind could be a pivotal factor driving the climate variability of shelf primary production in the stratified season.

Effect of water regime on the dynamics of free ammonia during high solid anaerobic digestion of pig manure - Jian Su; Wenjuan Lv; Liheng Ren; Xiaoliang Kong; Lin Luo; Mukesh Kumar Awasthi; Binghua Yan (Chemosphere, 2023)

Prenatal titanium exposure and child neurodevelopment at 1 year of age: A longitudinal prospective birth cohort study - Yangqian Jiang; Yongyue Wei; Wenhui Guo; Jiangbo Du; Tao Jiang; Hongxia Ma; Guangfu Jin; Ting Chen; Rui Qin; Shiyao Tao; Qun Lu; Hong Lv; et al. (Chemosphere, 2023)

Theoretical study on pyrolysis mechanism of decabromodiphenyl ether (BDE-209) using DFT method - Yao Wang; Jinbao Huang; Hong Wang; Lin Lan; Xin Mu; Weiwei Xu; Shanjin Lv; Xinsheng Li (Chemosphere, 2023)

Microplastics are transferred by soil fauna and regulate soil function as material carriers - Yunchao Luo; Lin Wang; Tingting Cao; Junxiu Chen; Meiqi Lv; Sijie Wei; Shangxian Lu; Xingjun Tian (Science of The Total Environment, 2023)

Understanding and revealing the intrinsic impacts of the COVID-19 lockdown on air quality and public health in North China using machine learning - Yunqian Lv; Hezhong Tian; Lining Luo; Shuhan Liu; Xiaoxuan Bai; Hongyan Zhao; Kai Zhang; Shumin Lin; Shuang Zhao; Zhihui Guo; Yifei Xiao; Junqi Yang (Science of The Total Environment, 2023)

Association of phthalate exposure with low birth weight in couples conceiving naturally or via assisted reproductive technology in a prospective birth cohort - Lu Zang; Hong Lv; Jiangbo Du; Yitao Pan; Yuan Lin; Jiayin Dai (Science of The Total Environment, 2023)

Copper sulfide engineered covalent organic frameworks for pH-responsive chemo/photothermal/chemodynamic synergistic therapy against cancer - Shuangling Wang; Yu Pang; Shuyang Hu; Jie Lv; Yulong Lin; Meng Li (Chemical Engineering Journal, 2023)

Insights into CQDs-doped perylene diimide photocatalysts for the degradation of naproxen - Zheng Fang; Yang Liu; Ping Chen; Daguang Li; Haijin Liu; Zhenjun Xiao; Yixun Zheng; Zifeng Lin; Jin Luo; Wenying Lv; Guoguang Liu (Chemical Engineering Journal, 2023)

Establishment of a Ca(II) ion-quantum dots fluorescence signal amplification sensor for high-sensitivity biomarker detection - Yanbing Lv; Panpan Wang; Jinjie Li; Ning Li; Dangdang Xu; Ruili Wu; Huaibin Shen; Lin Song Li (Analytica Chimica Acta, 2023)

Deep Learning-Based Classification of Raw Hydroacoustic Signal: A Review - Xu Lin; Ruichun Dong; Zhichao Lv (Journal of Marine Science and Engineering, 2022)
Underwater target recognition is a research component that is crucial to realizing crewless underwater detection missions and has significant prospects in both civil and military applications. This paper provides a comprehensive description of the current stage of deep-learning methods with respect to raw hydroacoustic data classification, focusing mainly on the variety and recognition of vessels and environmental noise from raw hydroacoustic data. This work not only aims to describe the latest research progress in this field but also summarizes three main elements of the current stage of development: feature extraction in the time and frequency domains, data enhancement by neural networks, and feature classification based on deep learning. In this paper, we analyze and discuss the process of hydroacoustic signal processing; demonstrate that the method of feature fusion can be used in the pre-processing stage in classification and recognition algorithms based on raw hydroacoustic data, which can significantly improve target recognition accuracy; show that data enhancement algorithms can be used to improve the efficiency of recognition in complex environments in terms of deep learning network structure; and further discuss the field’s future development directions.

Golden 2-like transcription factor contributes to the major QTL against rice black-streaked dwarf virus disease - Xuejuan Li; Feng Lin; Chenyang Li; Linlin Du; Zhiyang Liu; Wenjuan Shi; Jianying Lv; Xiaoyan Cao; Ying Lan; Yongjian Fan; Yijun Zhou; Tong Zhou (Theoretical and Applied Genetics, 2022)

Correction to: COX-2/PGE2 Pathway Inhibits the Ferroptosis Induced by Cerebral Ischemia Reperfusion - Yunfei Xu; Ying Liu; Kexin Li; Dun Yuan; Shun Yang; Lin Zhou; Yao Zhao; Shuying Miao; Caihong Lv; Jie Zhao (Molecular Neurobiology, 2022)

Comparison of groundwater hydrogeochemistry of karst areas in northern and southern China with emphasis on their performance in karst development - Peng Yuming; Xiao Qiong; Xue Honglei; Lv Minghui; Lin Guangqi; Zhao Haijuan; Wu Peiyan; Guo Yongli (Carbonates and Evaporites, 2022)

Effects of low-dose bisphenol AF on mammal testis development via complex mechanisms: alterations are detectable in both infancy and adulthood - Yuanyuan Li; Yiming Xiong; Lin Lv; Xinghong Li; Zhanfen Qin (Archives of Toxicology, 2022)

Study on the chemical composition of Caesalpinia sinensis - Lu-Fen Leng; Qi Lai; Dian Lv; Jun-Lin Yin; Guang-Zhi Zeng (Natural Product Research, 2022)

Design of deep-sea chemical data collector for the seafloor observatory network - Bin Lv; Jie Chen; Hai-lin Liu; Chao Liu; Zhao-wen Zhang; Xiao-nan Zhang; Hao Gao; Yu-long Cai (Marine Georesources & Geotechnology, 2022)

Development of diagnostic molecular markers to differentiate sharp eyespot and Fusarium crown rot isolates collected from common wheat fields in China - Yan Ren; Yue Wang; Li-yan Wang; Xia-Lei Lv; Ti Liu; Jing-yun Nie; Peng Guo; Lin Ma; Xiao-nan Sun; Feng Chen (Phytoparasitica, 2022)

Organic–inorganic calcium lignosulfonate compounds for soil acidity amelioration - Fei Kang; Qi-lin Lv; Jin Liu; Yun-shan Meng; Zi-he Wang; Xue-qin Ren; Shu-wen Hu (Environmental Science and Pollution Research, 2022)

A novel mutation in HINT1 gene causes autosomal recessive axonal neuropathy with neuromyotonia, effective treatment with carbamazepine and review of the literature - Ling Xu; Guangyu Wang; Xiaoqing Lv; Dong Zhang; Chuanzhu Yan; Pengfei Lin (Acta Neurologica Belgica, 2022)

Potential and Distribution of Natural Gas Hydrate Resources in the South China Sea - Pibo Su; Lin Lin; Yaoyao Lv; Jinqiang Liang; Yunbao Sun; Wei Zhang; Huice He; Baiquan Yan; Zhanhuai Ji; Lifeng Wang; Feifei Wang; Mengya Cai (Journal of Marine Science and Engineering, 2022)
The amount of natural gas contained in the world’s gas hydrate accumulations is enormous, but these estimates remain highly speculative. So far, it is still challenging to locate spatial distribution of marine gas hydrate and quantitatively characterize the evaluation parameters and systematic improvement of evaluation systems. Considering the systematic review of the key accumulation factors, such as heat flow, deposition rate and total organic carbon in the typical passive continental margin, the evaluation results of global marine gas hydrate resources were analyzed based on the characteristics of gas hydrate geology, geophysics and geochemistry anomalies in the South China Sea. We analyze the problems on the evaluation of marine gas hydrate resources, probing into the geological characteristics and distribution laws of marine gas hydrate resources in the South China Sea, and estimate the parameters for in-place resource evaluation, in which the volume method based on Monte Carlo probability was used to evaluate the gas hydrate potential resources in the South China Sea. The probability distribution ranges from 37.6 billion (with 90% probability) to 117.7 billion (with 10% probability) tons of oil equivalent, with an expected value of 74.4 billion tons of oil equivalent. The study results show that the gas hydrate resource density in the South China Sea is similar to that in the typical sea areas, and the estimated global resources are basically consistent with the assessment results at this stag; this shows that the South China Sea has great potential for gas hydrate resources. The research results can provide guidance for the evaluation of global climate change and the exploration and development of hydrate resources.

Distribution Characteristics and Ecological Risk Assessment of Heavy Metals in Marine Sediments of Binhai County, Jiangsu Province - Shu Chen; Min Xu; Dandan Cui; Lin Lv; Zaifeng Wang; Baiqiong Liu; Jing Wang (Journal of Marine Science and Engineering, 2022)
In recent years, research on heavy metals has become very popular, because the status of heavy metals can reflect the marine environment of a region. Based on this, this paper carries out the evaluation and analysis of heavy metals in marine sediments. Based on the content of the heavy metals in the coastal sediments of Binhai, Jiangsu, from coastal waters in the autumns of 2012, 2015, and 2018, the environmental quality was quantitatively evaluated using the geoaccumulation index and potential ecological risk. The sources of the heavy metals were identified by a multivariate analysis, and the changes over the years and the distribution characteristics were analyzed. Hg and Cr were at a clean grade, while other heavy metals contents indicated mild-to-moderate pollution in the three sets of monitoring data. The comprehensive ecological risk index assessment showed that Hg and Cd were at a moderate ecological risk level in the three sets of monitoring data. Overall, the study area exhibited a mild-to-moderate ecological risk level, with a continuously increasing trend. The overall content of heavy metal in this sea area is greatly affected by human activities, with high values occurring in ports, estuaries, and outer seas.

Ancylostoma ceylanicum Infection in a Miniature Schnauzer Dog Breed - Xu-Hui Lin; Hai-Ming Cai; Zhuan-Qiang Yan; Shen-Quan Liao; Min-Na Lv; Cai-Yan Wu; Juan Li; Jun-Jing Hu; Wen-Wan Xiao; Jian-Fei Zhang; Nan-Shan Qi; Ming-Fei Sun (Acta Parasitologica, 2022)

Research on an Extensible Monitoring System of a Seafloor Observatory Network in Laizhou Bay - Jie Chen; Hailin Liu; Bin Lv; Chao Liu; Xiaonan Zhang; Hui Li; Lin Cao; Junhe Wan (Journal of Marine Science and Engineering, 2022)
An extensible remote monitoring system for a seafloor observatory network in Laizhou Bay was established to realize long-term, continuous and on-line monitoring for a marine ranching environment. This paper deals with data communication, device management and data quality control. A control model is introduced that is structured into four layers, enabling bidirectional information flow. Based on the control model, the standardized communication protocol and device object model-oriented dynamic management method are designed as plug-and-play, for data processing and control of a large number of devices. An improved data quality control method is proposed to reduce the data error rate. The monitoring system was developed based on socket network programming, MySQL database technologies and modular ideas. The seafloor observatory network was successfully deployed in Laizhou Bay marine ranching. The experimental results demonstrate that the monitoring system obtains better performance. The proposed algorithms can also be used in many other similar systems with adaptive requirements.

Isolation and identification of two new sargentodoxosides from Sargentodoxa cuneata and their agonistic effects against FXR - Wen Zhang; Cheng-Peng Sun; Yu-Lin Peng; Wen-Yu Zhao; Zheng-Yue Wang; Jing Ning; Xia Lv; Zhen-Long Yu; Shuang Zhou; Wei Peng; Bang-Jiang Fang; Xiao-Chi Ma (Natural Product Research, 2022)

Isolation of Three Coliphages and the Evaluation of Their Phage Cocktail for Biocontrol of Shiga Toxin-Producing Escherichia coli O157 in Milk - Lili Zhu; Yanyan Hou; Xi Huang; Shuang Wang; Rui Xie; Jie Yang; Qingjie Lv; Lin Hua; Wan Liang; Zhong Peng; Bin Wu (Current Microbiology, 2022)

Ar-plasma enhanced copper-nickel alloy catalysis for ammonia synthesis - Zhou Yimeng; Lv Jiabao; Peng Yaqi; Lin Xiaoqing; Lv Xingjie; Ye Qiulin; Liu Shaojun; Wu Angjian; Li Xiaodong (Waste Disposal & Sustainable Energy, 2022)

Bedside Diagnosis for Disseminated Deep Dermatophytosis: a Case Series Study - Xiu-Jiao Xia; Hong Shen; Hui-Lin Zhi; Yan Zhong; Bo Sang; Wen-Wen Lv; Qiu-Ping Li; Ze-Hu Liu (Mycopathologia, 2022)

Association between MAP3K4 gene polymorphisms and the risk of schizophrenia susceptibility in a Northeast Chinese Han population - Yang Sun; Ye Lv; Hui-Wen Ren; Guan-Yu Wang; Li-Na Xuan; Yi-Yang Luo; Zhi-Lin Luan (Metabolic Brain Disease, 2022)

Responses of photosynthesis, antioxidant enzymes, and related gene expression to nicosulfuron stress in sweet maize (Zea mays L.) - Zhen-Xing Wu; Ning-Wei Xu; Min Yang; Xiang-Ling Li; Jin-Ling Han; Xiao-Hu Lin; Qing Yang; Gui-Hua Lv; Jian Wang (Environmental Science and Pollution Research, 2022)

Probiotic Potential and Effects on Gut Microbiota Composition and Immunity of Indigenous Gut Lactobacilli in Apis cerana - Mingkui Lv; Sifan Wang; Huajuan Yin; Kun Dong; Yiqiu Liu; Hongbin Pan; Qiuye Lin; Zhenhui Cao (Probiotics and Antimicrobial Proteins, 2022)

Autophagy modulation in resveratrol protective effects on steroidogenesis in high-fat diet-fed mice and H2O2-challenged TM3 cells - Ping Wang; Mengyu Lin; Chao Chen; Zheng-mei Lv (Molecular Biology Reports, 2022)

The RNA-binding protein SND1 promotes the degradation of GPX4 by destabilizing the HSPA5 mRNA and suppressing HSPA5 expression, promoting ferroptosis in osteoarthritis chondrocytes - Min Lv; Yuanzhen Cai; Weikun Hou; Kan Peng; Ke Xu; Chao Lu; Wenxing Yu; Weisong Zhang; Lin Liu (Inflammation Research, 2022)

COX-2/PGE2 Pathway Inhibits the Ferroptosis Induced by Cerebral Ischemia Reperfusion - Yunfei Xu; Ying Liu; Kexin Li; Dun Yuan; Shun Yang; Lin Zhou; Yao Zhao; Shuying Miao; Caihong Lv; Jie Zhao (Molecular Neurobiology, 2022)

Transcriptomic Analysis of Gill and Hepatopancreas in Razor Clam (Sinonovacula constricta) Exposed to Acute Ammonia - Liyuan Lv; Jianfeng Ren; Huan Zhang; Changsen Sun; Yinghui Dong; Zhihua Lin (Frontiers in Marine Science, 2022)
Accumulation of excessive ammonia is a big threat to aquatic animals, which causes adverse effects on the health, production reduction, and even high mortality. The razor clam Sinonovacula constricta , a bivalve living in intertidal mudflat with a deep-burrowing lifestyle, often faces a high concentration of ambient ammonia. However, there is less available information concerning the toxic effects of ammonia on razor clam and its molecular mechanisms of adaptation to ammonia stress. The aim of this study was to investigate the effects of ammonia exposure on the gill and hepatopancreas of razor clam by transcriptome sequencing. The results showed that the median lethal concentration of ammonia was 244.55 mg/L for 96 h. A total of 1,415 and 306 differentially expressed genes (DEGs) were identified in the gill and hepatopancreas, respectively. The functional annotation showed that DEGs of the gill were mainly involved in the regulation of nitrogen compound metabolic process, nitrogen compound transport, and amide transport. The DEGs of the hepatopancreas were mostly enriched in oxidation-reduction process, response to stress, and amine metabolic process. The expression levels of NH 3 /NH 4 + transporting channels and H + excreting-related genes, including Rhesus glycoproteins ( Rh ), Na + /K + -ATPase (NKA), Na + /H + exchanger , V-ATPase ( VHA ), and carbonic anhydrase ( CA ), were upregulated significantly in the gill ( p < 0.05). In addition, the expression levels of glutamine and urea synthesis-related genes that played vital roles in ammonia detoxification, such as glutamine synthetase ( GS ), arginase ( ARG ), and argininosuccinate synthetase ( ASS ), were also increased obviously in the hepatopancreas ( p < 0.05). Taken together, our results indicate that the synergistic action of ammonia excretion in the gill and ammonia metabolism in the hepatopancreas might be the mechanism through which the clams tolerate to environmental ammonia. This study provides a molecular basis for the better evaluation of the responding mechanism of ammonia tolerance.

The potential importance of soil denitrification as a major N loss pathway in intensive greenhouse vegetable production systems - Waqas Qasim; Yiming Zhao; Li Wan; Haofeng Lv; Shan Lin; Gretchen M. Gettel; Klaus Butterbach-Bahl (Plant and Soil, 2022)
Background About 30 % of vegetables in China are produced in intensively managed greenhouses comprising flood irrigation and extreme rates of nitrogen fertilizers. Little is known about denitrification N losses. Methods Soil denitrification rates were measured by the acetylene inhibition technique applied to anaerobically incubated soil samples. Four different greenhouse management systems were differentiated: Conventional flood irrigation and over-fertilization (CIF, 800 kg N ha −1 , 460 mm); CIF plus straw incorporation (CIF+S, 889 kg N ha −1 , 460 mm); Drip fertigation with reduced fertilizer application rates (DIF, 314 kg N ha −1 , 190 mm); DIF plus straw incorporation (DIF+S, 403 kg N ha −1 , 190 mm). Soil denitrification was measured on nine sampling dates during the growing season (Feb 2019-May 2019) for the top-/ subsoil (0 – 20/ 20- 40 cm) and on three sampling dates for deep soils (40-60/ 80-100 cm). Data was used to constrain N-input-output balances of the different vegetable production systems. Results Rates of denitrification were at least one magnitude higher in topsoil than in sub- and deep soils. Total seasonal denitrification N losses for the 0 – 40 cm soil layer ranged from 76 (DIF) to 422 kg N ha −1 (CIF+S). Straw addition stimulated soil denitrification in top- and subsoil, but not in deep soil layers. Integrating our denitrification data (0-100 cm) with additional data on N leaching, N 2 O emissions, plant N uptake, and NH 3 volatilization showed, that on average 50 % of added N fertilizers are lost due to denitrification. Conclusions Denitrification is likely the dominant environmental N loss pathway in greenhouse vegetable production systems. Reducing irrigation and fertilizer application rates while incorporating straw in soils allows the reduction of accumulated nitrate.

Isolation and structural elucidation of a low-molecular-weight polysaccharide from the roots of Panax ginseng C. A. Meyer - Bin Zhao; Xin-Ying Wang; Wen Luo; Yue Lin; Chong-Ning Lv; Jin-Cai Lu (Natural Product Research, 2022)

Structure reassignment of two triterpenes with CASE algorithms and DFT chemical shift predictions - Zhi-Kang Duan; Tian-Ming Lv; Guan-Shan Song; Yu-Xi Wang; Bin Lin; Xiao-Xiao Huang (Natural Product Research, 2022)

N-acetylcysteine alleviates pulmonary inflammatory response during benzo[a]pyrene-evoked acute lung injury - Hui Zhao; Lin Fu; Hui-Xian Xiang; Ying Xiang; Meng-Die Li; Bian-Bian Lv; Zhu-Xia Tan; Lan Gao; Cheng Zhang; De-Xiang Xu (Environmental Science and Pollution Research, 2022)

Functional variants of RPS6KB1 and PIK3R1 in the autophagy pathway genes and risk of bladder cancer - Lan Ma; Dongjian Zhang; Zhengkai Huang; Rui Zheng; Mulong Du; Qiang Lv; Chao Qin; Haiyan Chu; Lin Yuan; Zhengdong Zhang (Archives of Toxicology, 2022)

Genome-Wide Characterization and Analysis of Expression of the Histone Gene Family in Razor Clam, Sinonovacula constricta - Jiaying Lian; Liyuan Lv; Hanhan Yao; Zhihua Lin; Yinghui Dong (Fishes, 2021)
The Chinese razor clam (Sinonovacula constricta), a bivalve species widely distributed in estuaries and mudflats, is often exposed to extreme environmental and microbial stresses. Histones are fundamental components of chromatin and play an important role in innate immunity, as demonstrated by its antimicrobial activities in clams. However, little attention has been paid to histones in bivalves. To fill this gap, we investigated the genomic distribution, structural characteristics, conserved motifs, and phylogenetic relationships of histones in S. constricta. A total of 114 histone genes were detected in the S. constricta genome, which were divided into 25 types in phylogenetic analysis. Among them, partial histones exhibited a tissue-dependent expression pattern, indicating that they may be involved in sustaining the homeostasis of organs/tissues in adult S. constricta. Furthermore, mRNA expression of certain histones changed significantly in S. constricta when infected with Vibrio parahaemolyticus, suggesting that histones play a role in the immune defense of S. constricta. All together, this study on histone genes in S. constricta not only greatly expands our knowledge of histone function in the clam, but also histone evolution in molluscs.

Rehabilitation of motor function in children with cerebral palsy based on motor imagery - Jiaxin Xie; Lin Jiang; Yanan Li; Baodan Chen; Fali Li; Yuanling Jiang; Dongrui Gao; Lili Deng; XuLin Lv; XianKun Ma; Gang Yin; Dezhong Yao; et al. (Cognitive Neurodynamics, 2021)

Complete genome sequence of a putative novel ilarvirus isolated from Eleocharis dulcis - Lanqing Lv; Xinyang Wu; Jiajia Weng; Yuchao Lai; Kelei Han; Yuwen Lu; Jiejun Peng; Lin Lin; Shaofei Rao; Guanwei Wu; Jianping Chen; Hongying Zheng; et al. (Archives of Virology, 2021)

Adhesion GPR123 is an indicator for recurrence and prognosis in bladder cancer - Yaming Liu; Guodong Wang; Tongwei Cui; Lin Lv (Genes & Genomics, 2021)

Master regulator NtrC controls the utilization of alternative nitrogen sources in Pseudomonas stutzeri A1501 - Zhimin Yang; Qin Li; Yongliang Yan; Xiubin Ke; Yueyue Han; Shaoyu Wu; Fanyang Lv; Yahui Shao; Shanshan Jiang; Min Lin; Yunhua Zhang; Yuhua Zhan (World Journal of Microbiology and Biotechnology, 2021)
Pseudomonas stutzeri A1501 is a model strain used to study associative nitrogen fixation, and it possesses the nitrogen regulatory NtrC protein in the core genome. Nitrogen sources represent one of the important factors affecting the efficiency of biological nitrogen fixation in the natural environment. However, the regulation of NtrC during nitrogen metabolism in P. stutzeri A1501 has not been clarified. In this work, a phenotypic analysis of the ntrC mutant characterized the roles of NtrC in nitrogen metabolism and the oxidative stress response of P. stutzeri A1501. To systematically identify NtrC-controlled gene expression, RNA-seq was performed to further analyse the gene expression differences between the wild-type strain and the ∆ ntrC mutant under nitrogen fixation conditions. A total of 1431 genes were found to be significantly altered by ntrC deletion, among which 147 associative genes had NtrC-binding sites, and the pathways for nitrogen fixation regulation, nitrogenous compound acquisition and catabolism and nitrate assimilation were discussed. Furthermore, the oxidative stress-related gene ( katB ), which was upregulated by ntrC deletion, was suggested to be a potential target gene of NtrC, thus highlighting the importance of NtrC in nitrogenase protection against oxygen damage. Based on these findings, we propose that NtrC is a high-ranking element in the regulatory network of P. stutzeri A1501 that controls a variety of nitrogen metabolic and oxidative stress responsive traits required for adaptation to complex rhizosphere environments.

Nuclear-localized eukaryotic translation initiation factor 1A is involved in mouse preimplantation embryo development - Yue Liu; Jiandong Sun; Yang Su; Jianmin Lin; Chengyu Lv; Kaien Mo; Songhua Xu; Shie Wang (Journal of Molecular Histology, 2021)

Irradiation-related longitudinal white matter atrophy underlies cognitive impairment in patients with nasopharyngeal carcinoma - Xiaoshan Lin; Linquan Tang; Mengjie Li; MingLi Wang; Zheng Guo; Xiaofei Lv; Yingwei Qiu (Brain Imaging and Behavior, 2021)

Ambient climate determines the directional trend of community stability under warming and grazing - Peipei Liu; Wangwang Lv; Jianping Sun; Caiyun Luo; Zhenhua Zhang; Xiaoxue Zhu; Xingwu Lin; Jichuang Duan; Guangping Xu; Xiaofeng Chang; Yigang Hu; Qiaoyan Lin; et al. (Global Change Biology, 2021)
Changes in ecological processes over time in ambient treatments are often larger than the responses to manipulative treatments in climate change experiments. However, the impacts of human‐driven environmental changes on the stability of natural grasslands have been typically assessed by comparing differences between manipulative plots and reference plots. Little is known about whether or how ambient climate regulates the effects of manipulative treatments and their underlying mechanisms. We collected two datasets, one a 36‐year long‐term observational dataset from 1983 to 2018, and the other a 10‐year manipulative asymmetric warming and grazing experiment using infrared heaters with moderate grazing from 2006 to 2015 in an alpine meadow on the Tibetan Plateau. The 36‐year observational dataset shows that there was a nonlinear response of community stability to ambient temperature with a positive relationship between them due to an increase in ambient temperature in the first 25 years and then a decrease in ambient temperature thereafter. Warming and grazing decreased community stability with experiment duration through an increase in legume cover and a decrease in species asynchrony, which was due to the decreasing background temperature through time during the 10‐year experiment period. Moreover, the temperature sensitivity of community stability was higher under the ambient treatment than under the manipulative treatments. Therefore, our results suggested that ambient climate may control the directional trend of community stability while manipulative treatments may determine the temperature sensitivity of the response of community stability to climate relative to the ambient treatment. Our study emphasizes the importance of the context dependency of the response of community stability to human‐driven environmental changes.

A new monoterpene-lactone with neuroprotective activity from corn silk - Wei-Yu Zhou; Tian-Ming Lv; Zi-Lin Hou; Ming Bai; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Natural Product Research, 2021)

Experimental study on integrated and autonomous conductivity-temperature-depth (CTD) sensor applied for underwater glider - Bin Lv; Hai-lin Liu; Yi-fan Hu; Cheng-xuan Wu; Jie Liu; Hai-jing He; Jie Chen; Jian Yuan; Zhao-wen Zhang; Lin Cao; Hui Li (Marine Georesources & Geotechnology, 2021)

Effects of Heat Stress on Gut Microbiome in Rats - Qian Qu; Hua Li; Lin Bai; Shiwei Zhang; Jiaqi Sun; Weijie Lv; Chunxin Ye; Cui Liu; Dayou Shi (Indian Journal of Microbiology, 2021)
Gut microbiome, as the largest and most important micro-ecosystem, plays a critical role in health. The purpose of this study was to evaluate whether heat stress modulates the composition and diversity of the gut microbiome in rats. The heat stress model was prepared in rats with the heating temperature maintained at 35–38°C. Cecum contents were collected after heat stress for 3 h and days 1, 3 and 7. Total DNA was extracted for 16 S rRNA sequencing and analysis of intestinal microbiome composition and diversity. The study showed that the composition of the intestinal microbiome of heat stress group was changed. And the heat stress modulated key phylotypes of gut microbiota at the level of phylum and genus. In particular, the genus of Lactobacillus and Bacteroides were significantly reduced, whereas the Oscillospira and Clostridium were increased by heat stress. Meanwhile, the rats under the heat stress encountered the change in carbohydrate metabolism, amino acid metabolism, and membrane transport to defense against stress. Taken together, the composition and structure of gut microbiome were affected by heat stress and some key phylotypes were also significantly altered. We conclude that the heat stress could impact multiple biological functions, via altering the gut microbiome.

Multifunctional graphene-based nanocomposites for simultaneous enhanced photocatalytic degradation and photothermal antibacterial activity by visible light - Ya-kun Lv; Lin Mei; Liu-xue Zhang; De-hong Yang; Zi-yu Yin (Environmental Science and Pollution Research, 2021)

Future variation in mountainous discharge in arid northwestern China: A basin case study - Lei Wu; Chang-bin Li; Xu-hong Xie; Jia-nan Lv; Jian-mei Wei; Xuan Zhou; Lin-shan Yang (Journal of Mountain Science, 2021)

Jatrophacine, a 4,5- seco -rhamnofolane diterpenoid with potent anti-inflammatory activity from Jatropha curcas - Yang Hu; Huimin Zhao; Aiping Yang; Qi Lv; Ning Ding; Tu-Lin Lu; Lihong Hu; Xiachang Wang (Natural Product Research, 2021)

Geographic modeling and simulation systems for geographic research in the new era: Some thoughts on their development and construction - Min Chen; Guonian Lv; Chenghu Zhou; Hui Lin; Zaiyang Ma; Songshan Yue; Yongning Wen; Fengyuan Zhang; Jin Wang; Zhiyi Zhu; Kai Xu; Yuanqing He (Science China Earth Sciences, 2021)
Regionality, comprehensiveness, and complexity are regarded as the basic characteristics of geography. The exploration of their core connotations is an essential way to achieve breakthroughs in geography in the new era. This paper focuses on the important method in geographic research: Geographic modeling and simulation. First, we clarify the research requirements of the said three characteristics of geography and its potential to address geo-problems in the new era. Then, the supporting capabilities of the existing geographic modeling and simulation systems for geographic research are summarized from three perspectives: Model resources, modeling processes, and operational architecture. Finally, we discern avenues for future research of geographic modeling and simulation systems for the study of regional, comprehensive and complex characteristics of geography. Based on these analyses, we propose implementation architecture of geographic modeling and simulation systems and discuss the module composition and functional realization, which could provide theoretical and technical support for geographic modeling and simulation systems to better serve the development of geography in the new era.

Study on the Quantitative Relationship Among Canopy Hyperspectral Reflectance, Vegetation Index and Cotton Leaf Nitrogen Content - Caixia Yin; Jiao Lin; Lulu Ma; Ze Zhang; Tongyu Hou; Lifu Zhang; Xin Lv (Journal of the Indian Society of Remote Sensing, 2021)
Study the response mechanism of Canopy spectral reflectance (CSR) to cotton nitrogen fertilizer, propose the sensitive band and center wavelength of cotton leaf nitrogen content (LNC), and compare the response characteristics of various vegetation indexes to LNC, propose a vegetation index that responds well to LNC and construct estimating model. This experiment sets five nitrogen fertilizer levels, namely N 0 (control), N 120 (120 kg/hm 2 ), N 240 (240 kg/hm 2 ), N 360 (360 kg/hm 2 ), N 480 (480 kg/hm 2 ). Among them, referring to the conventional nitrogen fertilizer is applied by local farmers (N 330 , 330 kg/hm 2 ). The results showed the following: (1) Visible light and near-infrared (NIR) can be used as two large ranges for precise monitoring of nitrogen, especially the CSR in the NIR range differs significantly under different nitrogen fertilizers. In the early stage of cotton growth, the CSR decreased with the nitrogen application rate increase, in a suitable nitrogen environment (360 kg/hm 2 ), and beyond N 360 , vice versa. In the later growth period, the CSR increases with the increase in nitrogen fertilizer. This trend is most evident in the short-wave NIR regions;(2) the range of 690–709 nm, 717–753 nm, and 940–958, which can be remote sensed by the spectral reflectance when cotton is affected in poor or rich nitrogen. The center wavelength corresponding to the nitrogen-sensitive band, respectively, are 697 nm, 735 nm, 953 nm, the band width can maintain 5–15 nm, generally not more than 20 nm;(3) compared with the ratio vegetation index, difference vegetation index, and normalized vegetation index, the combined vegetation index of more than two bands has a better effect on cotton LNC monitoring, of which the index (R 560 −R 670 )/(R 560 + R 670 −R 450 ), (R 700 −1.7 × R 670 + 0.7 × R 450 )/(R 700 + 2.3 × R 670 −1.3 × R 450 ) are significantly related to LNC in this papers, and the correlation coefficients can reach, respectively, 0.935 * and 0.936 * . These findings help to estimate the model of LNC. The model is as follows: Y = 19.883 × x + 42.285, where x refers to the combined vegetation index (R 700 −1.7 × R 670 + 0.7 × R 450 )/(R 700 + 2.3 × R 670 −1.3 × R 450 ), Y is LNC, but the model accuracy will be affected in the crop different phenological stage, and the model has the highest monitoring accuracy during the bud period.

Comparative analysis of sRNAs, degradome and transcriptomics in sweet sorghum reveals the regulatory roles of miRNAs in Cd accumulation and tolerance - Weitao Jia; Kangqi Lin; Tengxue Lou; Juanjuan Feng; Sulian Lv; Ping Jiang; Ze Yi; Xuan Zhang; Duoliya Wang; Zijing Guo; Yetao Tang; Rongliang Qiu; et al. (Planta, 2021)

Defense of COVID-19 by Human Organoids - Ting Lv; Fanlu Meng; Meng Yu; Haihui Huang; Xinhua Lin; Bing Zhao (Phenomics, 2021)

Preparation of Ce0.9Zr0.1O2/SnIn4S8 composite photocatalyst and its degradation of typical antibiotic pollutants - Yuancai Lv; Jianying Yu; Siyi Huang; Kaiyun Zheng; Guifang Yang; Yifan Liu; Chunxiang Lin; Xiaoxia Ye; Minghua Liu (Environmental Science and Pollution Research, 2021)

Complete genome sequence of a previously undescribed monopartite begomovirus and betasatellite infecting Malvastrum coromandelianum in Cambodia - Yafei Tang; Zhenggang Li; Xiaoman She; Lin Yu; Guobing Lan; Lihua Lv; Judith K. Brown; Zifu He (Archives of Virology, 2021)

QTL mapping of the genetic basis of stem diameter in soybean - Chong-Yuan Sun; Yu-Ming Yang; Lin Jia; Xiao-Qian Liu; Huan-Qing Xu; Hai-Yan Lv; Zhong-Wen Huang; Dan Zhang (Planta, 2021)

MiR-124 and Small Molecules Synergistically Regulate the Generation of Neuronal Cells from Rat Cortical Reactive Astrocytes - Yangyang Zheng; Zhehao Huang; Jinying Xu; Kun Hou; Yifei Yu; Shuang Lv; Lin Chen; Yulin Li; Chengshi Quan; Guangfan Chi (Molecular Neurobiology, 2021)

Effects of indole acetic acid on the growth and selenium absorption characteristics of Cyphomandra betacea seedlings - Yunmin Huan; Liu Yang; Qin Liu; Lijin Lin; Ming’an Liao; Zhihui Wang; Dong Liang; Hui Xia; Yi Tang; Xiulan Lv; Jin Wang (Acta Physiologiae Plantarum, 2021)

GTree: an Open-source Tool for Dense Reconstruction of Brain-wide Neuronal Population - Hang Zhou; Shiwei Li; Anan Li; Qing Huang; Feng Xiong; Ning Li; Jiacheng Han; Hongtao Kang; Yijun Chen; Yun Li; Huimin Lin; Yu-Hui Zhang; et al. (Neuroinformatics, 2021)

Increased depression risk for elderly women with high blood levels of strontium and barium - Jia Lv; Yan-ling Li; Wen-qiang Ren; Rong Li; Jian-rong Chen; Chao Bao; Zhi-ping Du; Shun Feng; Ling Gu; Hui Gao; Kai-yong Liu; Lin-sheng Yang; et al. (Environmental Chemistry Letters, 2021)

Differential proteomics reveals main determinants for the improved pectinase activity in UV-mutagenized Aspergillus niger strain - Weiling Lin; Xiaohong Xu; Ruirui Lv; Wei Huang; Hafeez ul Haq; Yuanyuan Gao; Hongli Ren; Canhua Lan; Baoyu Tian (Biotechnology Letters, 2021)

Contamination assessment, health risk evaluation, and source identification of heavy metals in the soil-rice system of typical agricultural regions on the southeast coast of China - Yanjun Ren; Meng Lin; Qingming Liu; Zhonghao Zhang; Xufeng Fei; Rui Xiao; Xiaonan Lv (Environmental Science and Pollution Research, 2021)

Experimental Investigation of CS2 Extraction to Enhance the Permeability of Coal - Zhen Zhang; Gaofeng Liu; Yunxing Cao; Jia Lin; Yi Jin; Baoan Xian; Runsheng Lv; Zhou Zhang (Transport in Porous Media, 2021)

Rapid assessment of landslide risk level based on deep learning - Fei Tan; Jin Yu; Yu-Yong Jiao; Dawei Lin; Jiahe Lv; Yi Cheng (Arabian Journal of Geosciences, 2021)

Application of solid-phase extraction based on magnetic nanoparticle adsorbents for the analysis of selected persistent organic pollutants in environmental water: A review of recent advances - Aiming Wu; Xiaoli Zhao; Junyu Wang; Zhi Tang; Tianhui Zhao; Lin Niu; Wenqiang Yu; Chunyan Yang; Mengyuan Fang; Hongzhou Lv; Shasha Liu; Fengchang Wu (Critical Reviews in Environmental Science and Technology, 2021)

Complete genome sequence of a new achyranthes virus A isolate from Achyranthes bidentata in China - Xinyang Wu; Yuchao Lai; Lanqing Lv; Kelei Han; Ziqiang Chen; Yuwen Lu; Jiejun Peng; Lin Lin; Jianping Chen; Hongying Zheng; Fei Yan (Archives of Virology, 2021)

Genetic variants in N6-methyladenosine are associated with bladder cancer risk in the Chinese population - Hanting Liu; Jingjing Gu; Yu Jin; Qi Yuan; Gaoxiang Ma; Mulong Du; Yuqiu Ge; Chao Qin; Qiang Lv; Guangbo Fu; Meilin Wang; Haiyan Chu; et al. (Archives of Toxicology, 2021)

Altered properties of brain white matter structural networks in patients with nasopharyngeal carcinoma after radiotherapy - Qinyuan Chen; Xiaofei Lv; Shufei Zhang; Jiabao Lin; Jie Song; Bolin Cao; Yihe Weng; Li Li; Ruiwang Huang (Brain Imaging and Behavior, 2020)

Transcriptome analysis of strawberry fruit in response to exogenous arginine - Jinhua Lv; Qianqian Pang; Xueqin Chen; Teng Li; Jinggui Fang; Shaoyan Lin; Haifeng Jia (Planta, 2020)

Erythropoietin-Induced Autophagy Protects Against Spinal Cord Injury and Improves Neurological Function via the Extracellular-Regulated Protein Kinase Signaling Pathway - Lin Zhong; Hui Zhang; Zheng-Fei Ding; Jian Li; Jin-Wei Lv; Zheng-Jun Pan; De-Xiang Xu; Zong-Sheng Yin (Molecular Neurobiology, 2020)

Three new species of Terriera (Rhytismatales, Ascomycota) from China - Shu-Rui Cai; Shi-Juan Wang; Tu Lv; Cheng-Lin Hou (Mycological Progress, 2020)

Initial chest CT findings in COVID-19: correlation with clinical features - Zhu-jing Shen; Nan Lu; Lu-lu Gao; Jian Lv; Hua-fu Luo; Ji-feng Jiang; Chao Xu; Shi-ya Li; Ju-jiang Mao; Kai Li; Xiao-pei Xu; Bin Lin (Journal of Zhejiang University-SCIENCE B, 2020)

Preparation and Characterization of PVA-Co-PE Drug-Loaded Nanofiber Membrane by Electrospinning Technology - Si Sheng; Xiaoying Yin; Fangmei Chen; Yixin Lv; Lin Zhang; Menghui Cao; Yun Sun (AAPS PharmSciTech, 2020)

The response of warm-season precipitation extremes in China to global warming: an observational perspective from radiosonde measurements - Jianping Guo; Yan Yan; Dandan Chen; Yanmin Lv; Yi Han; Xiaoran Guo; Lin Liu; Yucong Miao; Tianmeng Chen; Ji Nie; Panmao Zhai (Climate Dynamics, 2020)

Effects of carboxymethyl chitosan on the growth and nutrient uptake in Prunus davidiana seedlings - Dandi Xu; Hongyan Li; Lijin Lin; Ming’an Liao; Qunxian Deng; Jin Wang; Xiulan Lv; Honghong Deng; Dong Liang; Hui Xia (Physiology and Molecular Biology of Plants, 2020)

The Cannabinoid Receptor Agonist WIN55,212-2 Ameliorates Hippocampal Neuronal Damage After Chronic Cerebral Hypoperfusion Possibly Through Inhibiting Oxidative Stress and ASK1-p38 Signaling - Da-Peng Wang; Qiao-Li Lv; Qi Lin; Kai Kang; Kai-Yan Jin; Jian Hai (Neurotoxicity Research, 2020)

Remediation of organic arsenic contaminants with heterogeneous Fenton process mediated by SiO2-coated nano zero-valent iron - Yuancai Lv; Siyi Huang; Guofu Huang; Yifan Liu; Guifang Yang; Chunxiang Lin; Gao Xiao; Yonghao Wang; Minghua Liu (Environmental Science and Pollution Research, 2020)

Effects of Chronic Ephedrine Toxicity on Functional Connections, Cell Apoptosis, and CREB-Related Proteins in the Prefrontal Cortex of Rhesus Monkeys - Shouxing Duan; Ye Ma; Lei Xie; Lian Zheng; Jinzhuang Huang; Ruiwei Guo; Zongbo Sun; Yao Xie; Junyao Lv; Zhirong Lin; Shuhua Ma (Neurotoxicity Research, 2020)

Effects of reciprocal hybridization on cadmium accumulation in F1 hybrids of two Solanum photeinocarpum ecotypes - Lijin Lin; Caifang Wu; Jin Wang; Ming’an Liao; Daiyu Yang; Honghong Deng; Xiulan Lv; Hui Xia; Dong Liang; Qunxian Deng (Environmental Science and Pollution Research, 2020)

Comparison of IC-RT-PCR, Dot-ELISA and Indirect-ELISA for the Detection of Sorghum Mosaic Virus in Field-Grown Sugarcane Plants - Hai Chen; Niyaz Ali; Wenzhu Lv; Yanan Shen; Zhen Qing; Yinfu Lin; Baoshan Chen; Ronghui Wen (Sugar Tech, 2020)

Whether China made efforts to decouple economic growth from CO2 emissions?-Production vs consumption perspective - Lin Yang; Yuantao Yang; Haodong Lv; Dong Wang (Environmental Science and Pollution Research, 2020)

An accounting of the external environmental costs of coal in Inner Mongolia using the pollution damage method - Hao-Dong Lv; Jin-Sheng Zhou; Lin Yang; Yi-Ming Li; Lu Liu (Environment, Development and Sustainability, 2020)

Cloning and Expression Analysis of the ScD53 Gene from Sugarcane - Ai-Li Lv; Xu-Juan Li; Chun-Jia Li; Hong-Bo Liu; Qiu-Yan Zi; Xiu-Qin Lin; Xin-Long Liu (Sugar Tech, 2019)

Variation of rill cross-sections with gravel and aggregating soil in the Dry-Hot Valley (SW China) - Nana Wang; Lin Ding; Gangcai Liu; Qingchun Deng; Hui Liu; Jie Wang; Wei Lv; Jun Luo; Ziyin Du; Bin Zhang (Modeling Earth Systems and Environment, 2019)

Effects of mutual grafting on cadmium accumulation characteristics of first post-generations of Bidens pilosa L. and Galinsoga parviflora Cav. - Hongyan Li; Jin Wang; Lijin Lin; Ming’an Liao; Xiulan Lv; Yi Tang; Xun Wang; Hui Xia; Dong Liang; Wei Ren; Wei Jiang (Environmental Science and Pollution Research, 2019)

In silico toxicity evaluation of dioxins using structure–activity relationship (SAR) and two-dimensional quantitative structure–activity relationship (2D-QSAR) - Hong Yang; Zhe Du; Wen-Juan Lv; Xiao-Yun Zhang; Hong-Lin Zhai (Archives of Toxicology, 2019)

Estimation of monthly pan evaporation using support vector machine in Three Gorges Reservoir Area, China - Ji-Long Chen; Hong Yang; Ming-Quan Lv; Zuo-Lin Xiao; Sheng Jun Wu (Theoretical and Applied Climatology, 2019)

Neural Stem Cells Transfected with Leukemia Inhibitory Factor Promote Neuroprotection in a Rat Model of Cerebral Ischemia - Lili Tian; Wenli Zhu; Yuanchu Liu; Ye Gong; Aowei Lv; Zhen Wang; Xiaoli Ding; Shaowu Li; Ying Fu; Yi Lin; Yaping Yan (Neuroscience Bulletin, 2019)

MicroRNA-365 Knockdown Prevents Ischemic Neuronal Injury by Activating Oxidation Resistance 1-Mediated Antioxidant Signals - Jia-Lin Mo; Zhi-Guang Pan; Xiao Chen; Yu Lei; Ling-Ling Lv; Cheng Qian; Feng-Yan Sun (Neuroscience Bulletin, 2019)

Three new Coccomyces species from Shennongjia National Nature Reserve in China - Tu Lv; Wan-Peng Tang; Shu-Rui Cai; Cheng-Lin Hou (Mycological Progress, 2019)

Effects of self-rooted grafting on growth and cadmium accumulation in post-grafting generations of soybean (Glycine max) - Jin Wang; Huan Yao; Lijin Lin; Yi Tang; Dong Liang; Hui Xia; Xiulan Lv; Ming’an Liao; Guochao Sun; Huanxiu Li; Xun Wang; Wei Ren (Environmental Monitoring and Assessment, 2019)

Self-rooted grafting influences the growth and cadmium accumulation characteristics in the post generation of Cosmos sulphureus - Jin Wang; Yumei Tan; Ming’an Liao; Lijin Lin; Yi Tang; Huifen Zhang; Hui Xia; Dong Liang; Qunxian Deng; Xiulan Lv; Cheng Chen; Wei Ren (Environmental Science and Pollution Research, 2019)

Analysis of the elemental spectral characteristics of single elemental capture spectrum log using Monte-Carlo simulation - Chang-Lin Lan; Xu-Wen Zhan; Hong-Liang Wu; Yi Zhang; Tong Liu; Zhou Feng; Tao Lv (Applied Geophysics, 2019)

Thymosin Alpha-1 Inhibits Complete Freund’s Adjuvant-Induced Pain and Production of Microglia-Mediated Pro-inflammatory Cytokines in Spinal Cord - Yunlong Xu; Yanjun Jiang; Lin Wang; Jiahua Huang; Junmao Wen; Hang Lv; Xiaoli Wu; Chaofan Wan; Chuanxin Yu; Wenjie Zhang; Jiaying Zhao; Yinqi Zhou; et al. (Neuroscience Bulletin, 2019)

Akt plays indispensable roles during the first cell lineage differentiation of mouse - Songhua Xu; Lili Pang; Yue Liu; Xiuli Lian; Kaien Mo; Ruimin Lv; Huimin Zhu; Chengyu Lv; Jianmin Lin; Jiandong Sun; Lixuan Xu; Shie Wang (Journal of Molecular Histology, 2019)

Quadruplex PCR detection of three quarantine Phytophthora pathogens of berries - Fang Liao; Guo-Ming Huang; Lin-Hui Zhu; Dajin Lv; Doudou Zhang; Jia-Feng Luo; Guan-Rong Li (European Journal of Plant Pathology, 2019)

Effects of intercropping with floricultural accumulator plants on cadmium accumulation in grapevine - Hongqiang Chen; Lijin Lin; Ming’an Liao; Jin Wang; Yi Tang; Guochao Sun; Dong Liang; Hui Xia; Qunxian Deng; Xun Wang; Xiulan Lv; Wei Ren (Environmental Science and Pollution Research, 2019)

Genetic Diversity and Population Structure of Coffee Germplasm Collections in China Revealed by ISSR Markers - Lin Yan; Collins Ogutu; Lifang Huang; Xiaoyang Wang; Hua Zhou; Yulan Lv; Yuzhou Long; Yunping Dong; Yuepeng Han (Plant Molecular Biology Reporter, 2019)

A Delaunay Triangulation Algorithm Based on Dual-Spatial Data Organization - Niantao Liu; Bingxian Lin; Guonian Lv; A-Xing Zhu; Liangchen Zhou (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2019)

Favus of Scrotum Due to Trichophyton rubrum in Immunocompetent Patients: A Clinical, Mycological and Ultrastructural Study - Ze-Hu Liu; Xiu-Jiao Xia; Yong Zhang; Yan Zhong; Bo Sang; Qiu-Ping Li; Mei Wang; Wen-Wen Lv; Hui-Lin Zhi; Xiang-Dong Wang; Cui-Ping Guan; Hong Shen (Mycopathologia, 2019)

Impact of Orogeny and Environmental Change on Genetic Divergence and Demographic History of Dipus sagitta (Dipodoidea, Dipodinae) since the Pliocene in Inland East Asia - Jilong Cheng; Xue Lv; Lin Xia; Deyan Ge; Qian Zhang; Liang Lu; Qisen Yang (Journal of Mammalian Evolution, 2019)

Effects of intercropping with Bidens species plants on the growth and cadmium accumulation of Ziziphus acidojujuba seedlings - Qian Deng; Qunxian Deng; Yang Wang; Lei Li; Xingyu Long; Si Ren; Yue Fan; Lijin Lin; Hui Xia; Dong Liang; Jin Wang; Huifen Zhang; et al. (Environmental Monitoring and Assessment, 2019)

Gene co-expression network analysis identifies trait-related modules in Arabidopsis thaliana - Wei Liu; Liping Lin; Zhiyuan Zhang; Siqi Liu; Kuan Gao; Yanbin Lv; Huan Tao; Huaqin He (Planta, 2019)

Cutting after grafting affects the growth and cadmium accumulation of Nasturtium officinale - Xingyu Zhang; Fenqin Zhang; Jin Wang; Lijin Lin; Ming’an Liao; Yi Tang; Guochao Sun; Xun Wang; Xiulan Lv; Qunxian Deng; Cheng Chen; Wei Ren (Environmental Science and Pollution Research, 2019)

KLP-PI: a new prognostic index for luminal B HER-2-negative breast cancer - Chuanmeng Pan; Adheesh Bhandari; Yehuan Liu; Erjie Xia; Lizhi Lin; Shixu Lv; Ouchen Wang (Human Cell, 2019)

AMPK agonist AICAR ameliorates portal hypertension and liver cirrhosis via NO pathway in the BDL rat model - Liangshuo Hu; Lin Su; Zhixia Dong; Yunhua Wu; Yi Lv; Jacob George; Jianhua Wang (Journal of Molecular Medicine, 2019)

Characteristics and source apportionment of PM2.5 in Jiaxing, China - Zhipeng Zhao; Sheng Lv; Yihua Zhang; Qianbiao Zhao; Lin Shen; Shi Xu; Jianqiang Yu; Jingwen Hou; Chengyu Jin (Environmental Science and Pollution Research, 2019)

Loop-mediated isothermal amplification (LAMP) detection of Phytophthora hibernalis, P. syringae and P. cambivora - Guan-Rong Li; Guo-Ming Huang; Lin-Hui Zhu; Dajin Lv; Baohong Cao; Fang Liao; Jia-Feng Luo (Journal of Plant Pathology, 2019)

Novel Inhalable Ciprofloxacin Dry Powders for Bronchiectasis Therapy: Mannitol–Silk Fibroin Binary Microparticles with High-Payload and Improved Aerosolized Properties - Chunxia Liu; Ling Lin; Zhengwei Huang; Qiaoli Wu; Junhuang Jiang; Li Lv; Xiaoxia Yu; Guilan Quan; Guocheng Li; Chuanbin Wu (AAPS PharmSciTech, 2019)

Comparative proteomic analysis of Nostoc flagelliforme reveals the difference in adaptive mechanism in response to different ultraviolet-B radiation treatments - Shi-gang Shen; Rong-jun Guo; Rong-rong Yan; Yi-kai Wu; Dong-xue Zhao; Ya-hui Lin; He-xin Lv; Shi-ru Jia; Pei-pei Han (Molecular Biology Reports, 2018)

Classical swine fever virus non-structural protein 4B binds tank-binding kinase 1 - Huifang Lv; Wang Dong; Zhi Cao; Jihui Lin; Yueling Ouyang; Kangkang Guo; Cunfa Li; Yanming Zhang (Journal of Biosciences, 2018)

Responses of lipoxygenase, jasmonic acid, and salicylic acid to temperature and exogenous phytohormone treatments in Gracilariopsis lemaneiformis (Rhodophyta) - Sainan Hou; Lichun Lin; Yan Lv; Nianjun Xu; Xue Sun (Journal of Applied Phycology, 2018)

Occurrence of cucumber mosaic virus subgroup II and its genetic diversity in Sichuan, southwest of China - Chunyan Fei; Zhenpeng Xu; Lijuan Chen; Wenshan Zou; Rui Lv; Honghui Lin; Dehui Xi (Journal of Plant Pathology, 2018)

Cadmium-accumulator straw application alleviates cadmium stress of lettuce (Lactuca sativa) by promoting photosynthetic activity and antioxidative enzyme activities - Yi Tang; Yongdong Xie; Guochao Sun; Huaqiang Tan; Lijin Lin; Huanxiu Li; Ming’an Liao; Zhihui Wang; Xiulan Lv; Dong Liang; Hui Xia; Xun Wang; et al. (Environmental Science and Pollution Research, 2018)

Phylogeographic analysis of porcine reproductive and respiratory syndrome virus 1 in Guangdong province, Southern China - Shao-Lun Zhai; Tao Lin; Xia Zhou; Zhang-Fu Pei; Zu-Zhang Wei; He Zhang; Xiao-Hui Wen; Qin-Ling Chen; Dian-Hong Lv; Wen-Kang Wei (Archives of Virology, 2018)

Associations between maternal exposure to air pollution and birth outcomes: a retrospective cohort study in Taizhou, China - Lin Ye; Yinwen Ji; Wei Lv; Yining Zhu; Chuncheng Lu; Bo Xu; Yankai Xia (Environmental Science and Pollution Research, 2018)

Climate zones determine where substantial increases of maize yields can be attained in Northeast China - Zhijuan Liu; Xiaoguang Yang; Xiaomao Lin; Prasanna Gowda; Shuo Lv; Jing Wang (Climatic Change, 2018)

The AP2/ERF transcription factor CmERF053 of chrysanthemum positively regulates shoot branching, lateral root, and drought tolerance - Jing Nie; Chao Wen; Lin Xi; Suhui Lv; Qingcui Zhao; Yaping Kou; Nan Ma; Liangjun Zhao; Xiaofeng Zhou (Plant Cell Reports, 2018)

MAVS induces a host cell defense to inhibit CSFV infection - Wang Dong; Huifang Lv; Cheng Li; Yaru Liu; Chengbao Wang; Jihui Lin; Yifan Wang; Gui Qian; Kangkang Guo; Yanming Zhang (Archives of Virology, 2018)

Triplex real-time PCR detection of three quarantine Phytophthora pathogens infecting Malus Miller - Fang Liao; Ying Zhang; Lin-Hui Zhu; Baohong Cao; Dajin Lv; Jia-Feng Luo; Guan-Rong Li (Journal of Plant Diseases and Protection, 2018)

Effects of indole-3-butytric acid on lead and zinc accumulations in Pseudostellaria maximowicziana - Zhi Ran; Cheng Chen; Fabo Chen; Ming’an Liao; Lijin Lin; Xiulan Lv; Qunxian Deng; Xun Wang; Jin Wang; Yi Tang; Huaxiong Li (Environmental Monitoring and Assessment, 2018)

Enhanced Tumor Diagnostic and Therapeutic Effect of Mesoporous Silica Nanoparticle-Mediated Pre-targeted Strategy - Gaochao Lv; Ke Li; Ling Qiu; Ying Peng; Xueyu Zhao; Xi Li; Qingzhu Liu; Shanshan Wang; Jianguo Lin (Pharmaceutical Research, 2018)

Time evolution and spatial accumulation of progressive failure for Xinhua slope in the Dagangshan reservoir, Southwest China - Ming-liang Chen; Peng-fei Lv; Shi-lin Zhang; Xing-ze Chen; Jia-wen Zhou (Landslides, 2018)

The different influence of the residual layer on the development of the summer convective boundary layer in two deserts in northwest China - Zhao Lin; Han Bo; Lv Shihua; Wen Lijuan; Meng Xianhong; Li Zhaoguo (Theoretical and Applied Climatology, 2018)

Significance of temperature and water availability for soil phosphorus transformation and microbial community composition as affected by fertilizer sources - Dasheng Sun; Qingfang Bi; Kejie Li; Peibin Dai; Yan Yu; Weiwei Zhou; Ting Lv; Xipeng Liu; Jun Zhu; Qichun Zhang; Chongwei Jin; Lingli Lu; et al. (Biology and Fertility of Soils, 2018)

Radiometric calibration evaluation for RSBs of Suomi-NPP/VIIRS and Aqua/MODIS based on the 2015 Dunhuang Chinese Radiometric Calibration Site in situ measurements - Lin Chen; Peng Zhang; Jiayan Lv; Na Xu; Xiuqing Hu (International Journal of Remote Sensing, 2017)

Adjuvant effects mediated by the carbohydrate recognition domain of Agrocybe aegerita lectin interacting with avian influenza H9N2 viral surface glycosylated proteins - Li-bao Ma; Bao-yang Xu; Min Huang; Lv-hui Sun; Qing Yang; Yi-jie Chen; Ya-lin Yin; Qi-gai He; Hui Sun (Journal of Zhejiang University-SCIENCE B, 2017)

Addition of straw from hyperaccumulator plants to cadmium-contaminated soil increases cadmium uptake by loquat seedlings - Lijin Lin; Ming’an Liao; Xiulan Lv; Dong Liang; Hui Xia; Jin Wang; Xun Wang (Environmental Monitoring and Assessment, 2017)

RIPK1/RIPK3/MLKL-mediated necroptosis contributes to compression-induced rat nucleus pulposus cells death - Songfeng Chen; Xiao Lv; Binwu Hu; Zengwu Shao; Baichuan Wang; Kaige Ma; Hui Lin; Min Cui (Apoptosis, 2017)

Potential Reproductive Advantage of Short-over Long-Winged Adult Males of the Cricket Velarifictorus ornatus - Lv-Quan Zhao; Huai-lin Chai; Dao-Hong Zhu (Evolutionary Biology, 2017)

Characterization of BcMF23a and BcMF23b, two putative pectin methylesterase genes related to pollen development in Brassica campestris ssp. chinensis - Sue Lin; Li Huang; Xiaolin Yu; Xingpeng Xiong; Xiaoyan Yue; Tingting Liu; Ying Liang; Meiling Lv; Jiashu Cao (Molecular Biology Reports, 2017)

Insulin-independent GLUT4 translocation in proliferative vascular smooth muscle cells involves SM22α - Li-Li Zhao; Fan Zhang; Peng Chen; Xiao-Li Xie; Yong-Qing Dou; Yan-Ling Lin; Lei Nie; Pin Lv; Dan-Dan Zhang; Xiao-Kun Li; Sui-Bing Miao; Ya-Juan Yin; et al. (Journal of Molecular Medicine, 2017)

Commercial production of tiger puffer (Takifugu rubripes) in winter using a recirculating aquaculture system - Zhongling Lin; Hua Wang; Chunyan Yu; Fenghe Lv; Hengming Liu; Tao Zhang (Journal of Ocean University of China, 2017)

Nestin Expression Is Associated with Poor Clinicopathological Features and Prognosis in Glioma Patients: an Association Study and Meta-analysis - Donglai Lv; Lin Lu; Zongtao Hu; Zhenle Fei; Meiqin Liu; Lei Wei; Jun Xu (Molecular Neurobiology, 2017)

The complete chloroplast genome sequence of Pinus dabeshanensis - Ren-Yan Duan; Li-Min Yang; Tong Lv; Gan-Lin Wu; Min-Yi Huang (Conservation Genetics Resources, 2016)

Molecular detection and genome characterization of porcine circovirus type 2 in rats captured on commercial swine farms - Shao-Lun Zhai; Sheng-Nan Chen; Wei Liu; Xiao-Peng Li; Su-Fang Deng; Xiao-Hui Wen; Man-Lin Luo; Dian-Hong Lv; Wen-Kang Wei; Rui-Ai Chen (Archives of Virology, 2016)

Rice false smut fungus hijacks the rice nutrients supply by blocking and mimicking the fertilization of rice ovary - Jie‐Hui Song; Wei Wei; Bo Lv; Yang Lin; Wei‐Xiao Yin; You‐Liang Peng; Guido Schnabel; Jun‐Bin Huang; Dao‐Hong Jiang; Chao‐Xi Luo (Environmental Microbiology, 2016)
Summary Rice false smut disease is an increasing threat to rice production in the world. Despite of best efforts, research for the infection of the fungus has yielded equivocal and conflicting results about where and how the infection is initiated and developed. Here we show a stepwise infection pattern and sophisticated regulation during this process. Initial infection occurred on the filaments, which prevented the production of mature pollen thus blocked the pollination. In the following days, the pathogen invaded the stigmas and styles, occasionally the ovaries. Expression analysis indicated that the fungus mimicked a successful fertilization process and enabled the continuous supply of nutrients for fungus to produce false smut balls. The stepwise infection of flower organs and mimicry of ovary fertilization unveiled in this study guided the rice plant into supplying nutrients for false smut ball development and represents a new and unique biological process of host pathogen interactions.

Upregulated TRIM32 correlates with enhanced cell proliferation and poor prognosis in hepatocellular carcinoma - Xiaopeng Cui; Zhipeng Lin; Yuyan Chen; Xiaofei Mao; Wenkai Ni; Jinxia Liu; Huiling Zhou; Xiaohang Shan; Lingling Chen; Jiale Lv; Zhongyi Shen; Chengwei Duan; et al. (Molecular and Cellular Biochemistry, 2016)

Mild Hypothermia Combined with Hydrogen Sulfide Treatment During Resuscitation Reduces Hippocampal Neuron Apoptosis Via NR2A, NR2B, and PI3K-Akt Signaling in a Rat Model of Cerebral Ischemia-Reperfusion Injury - Hai-Bin Dai; Miao-Miao Xu; Jia Lv; Xiang-Jun Ji; Si-Hai Zhu; Ru-Meng Ma; Xiao-Lei Miao; Man-Lin Duan (Molecular Neurobiology, 2016)

Cadmium accumulation characteristics of F1 hybrids by reciprocal hybridizing of Solanum nigrum in two climate–ecology regions - Lijin Lin; Jing He; Xun Wang; Jin Wang; Xiulan Lv; Ming’an Liao; Zhihui Wang; Yi Tang; Dong Liang; Hui Xia; Yunsong Lai (Environmental Science and Pollution Research, 2016)

Health risk assessment of heavy metals in soil-plant system amended with biogas slurry in Taihu basin, China - Bo Bian; Cheng Lin; Lin Lv (Environmental Science and Pollution Research, 2016)

Advanced glycation endproducts in 35 types of seafood products consumed in eastern China - Jing Wang; Zhenxing Li; Ramesh Tushar Pavase; Hong Lin; Long Zou; Jie Wen; Liangtao Lv (Journal of Ocean University of China, 2016)

Complete genome sequence of a coxsackievirus B3 recombinant isolated from an aseptic meningitis outbreak in eastern China - Wenqiang Zhang; Xiaojuan Lin; Ping Jiang; Zexin Tao; Xiaolin Liu; Feng Ji; Tongzhan Wang; Suting Wang; Hui Lv; Aiqiang Xu; Haiyan Wang (Archives of Virology, 2016)

Emergence of reticuloendotheliosis virus in pigeons in Guangdong Province, Southern China - Shao-Lun Zhai; Sheng-Nan Chen; Tao Lin; Xiao-Hui Wen; Wen-Kang Wei; Dian-Hong Lv; Rui-Ai Chen (Archives of Virology, 2016)

Imperatorin inhibits the expression of alpha-hemolysin in Staphylococcus aureus strain BAA-1717 (USA300) - Ping Ouyang; Junjie Chen; Mao Sun; Zhongqiong Yin; Juchun Lin; Hualin Fu; Gang Shu; Changliang He; Cheng Lv; Xuming Deng; Kaiyu Wang; Yi Geng; et al. (Antonie van Leeuwenhoek, 2016)

Multiscale partitioning of small mammal β‐diversity provides novel insights into the Quaternary faunal history of Qinghai–Tibetan Plateau and Hengduan Mountains - Zhixin Wen; Qisen Yang; Qing Quan; Lin Xia; Deyan Ge; Xue Lv (Journal of Biogeography, 2016)
Aim To assess the validity of four hypothesized drivers (Quaternary climate, niche conservatism, contemporary climate, spatial configuration) of small mammal beta diversity in the Qinghai–Tibetan Plateau ( QTP ) and the Hengduan Mountains ( HDM ). Location QTP and HDM of China. Methods We partitioned the beta diversity of small mammals in QTP and HDM into the spatial turnover and nestedness components at the regional (longitudinal/latitudinal zones) and grid (1° × 1°) scales. Regional beta diversity was evaluated by calculating the multiple‐site dissimilarities and the distance‐dissimilarity relationships. We examined the relative effects of geographical distance, environmental difference, habitat diversity, geographical isolation and Quaternary climate stability on the beta diversity patterns. Results The overall beta diversity in all longitudinal/latitudinal zones of both regions was primarily driven by spatial turnover, longitudinal nestedness patterns were almost non‐existent in QTP . Turnover was stronger in the latitudinal direction of QTP and in the longitudinal direction of HDM , which corresponded to the general topography of each region. At the grid scale, higher turnover was primarily concentrated in mountainous areas. Turnover was highly correlated with geographical distance and environmental difference in both regions, and geographical isolation was another strong predictor of turnover in HDM . Habitat diversity independently explained most of the variation in nestedness of HDM . Main conclusions Spatial turnover is the primary cause of the small mammal beta diversity in QTP and HDM . Three non‐exclusive mechanisms including the historic effect of past glaciation, contemporary climate and spatial configuration of the landscape might act in combination to shape the beta diversity patterns in QTP and HDM , particularly the directional patterns. Our results challenge the prevailing view that the current distribution of QTP fauna is primarily explained by westward post‐glacial recolonization, and support the alternative idea that QTP retained considerable refugia and even centres of origin during the Quaternary glaciations.

The effects of abscisic acid (ABA) addition on cadmium accumulation of two ecotypes of Solanum photeinocarpum - Jin Wang; Lijin Lin; Li Luo; Ming’an Liao; Xiulan Lv; Zhihui Wang; Dong Liang; Hui Xia; Xun Wang; Yunsong Lai; Yi Tang (Environmental Monitoring and Assessment, 2016)

Effect of Temperature and pH on the Sorption of Dibutyl Phthalate on Humic Acid - Minling Gao; Xiaolei Gong; Mengting Lv; Wenhua Song; Xiaojun Ma; Yun Qi; Lin Wang (Water, Air, & Soil Pollution, 2016)

Vascular endothelial growth factor-C protects heart from ischemia/reperfusion injury by inhibiting cardiomyocyte apoptosis - Xu-guang Chen; Yan-xia Lv; Dan Zhao; Lei Zhang; Fei Zheng; Jian-Ye Yang; Xiao-lin Li; Lu Wang; Lin-Yun Guo; Ya-mu Pan; Yu-wen Yan; Shi-You Chen; et al. (Molecular and Cellular Biochemistry, 2016)

Effects of grafting on the cadmium accumulation characteristics of the potential Cd-hyperaccumulator Solanum photeinocarpum - Lijin Lin; Daiyu Yang; Xun Wang; Ming’an Liao; Zhihui Wang; Xiulan Lv; Fuyi Tang; Dong Liang; Hui Xia; Yunsong Lai; Yi Tang (Environmental Monitoring and Assessment, 2016)

Erratum to: First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2016)

Complete genome sequence of the first bluetongue virus serotype 7 isolate from China: evidence for entry of African-lineage strains and reassortment between the introduced and native strains - Heng Yang; Minna Lv; Minfei Sun; Liqin Lin; Meilin Kou; Lin Gao; Defang Liao; Heli Xiong; Yuwen He; Huachun Li (Archives of Virology, 2016)

New magnetostratigraphic and pedostratigraphic investigations of loess deposits in north‐east China and their implications for regional environmental change during the Mid‐Pleistocene climatic transition - Lin Zeng; Huayu Lu; Shuangwen Yi; Yongxiang Li; Anqi Lv; Wenchao Zhang; Zhiwei Xu; Haifeng Wu; Han Feng; Mengchun Cui (Journal of Quaternary Science, 2016)
Little is known about the long‐term climatic evolution of north‐eastern (NE) China, because well‐preserved terrestrial paleoenvironmental archives are scarce in this vast region. The extensive loess deposits in the Chifeng region are the thickest and most complete loess–paleosol sequence in NE China, and have significant potential for reconstructing the paleoclimate of the region. Here, we present new high‐resolution magnetostratigraphic results from two loess–paleosol sections in the Chifeng region: the Sanbahuo (SBH) and Toudaojingzi (TDJZ) sections. The results demonstrate that both sections record the Brunhes normal polarity chron and the upper portion of the Matuyama reversed polarity chron. Based on these new results, the base of the TDJZ loess sequence is dated at ca. 1.22 Ma, representing the oldest known loess deposits in NE China. The initiation of loess accumulation in NE China was roughly synchronous with the large expansion of the Eurasian loess belt during the late Early Pleistocene (1.2–0.7 Ma), probably reflecting a widespread intensification of aridity in northern mid‐latitudes. We suggest that global cooling during the Mid‐Pleistocene climatic transition led to increased aridity and more favorable conditions for promoting the availability of silt for entrainment, transport and deposition.

Synthesis and biological evaluation of novel platinum complexes of imidazolyl-containing bisphosphonates as potential anticancer agents - Ling Qiu; Gaochao Lv; Yang Cao; Liping Chen; Hui Yang; Shineng Luo; Meifen Zou; Jianguo Lin (JBIC Journal of Biological Inorganic Chemistry, 2015)

Genome characterization and phylogenetic analysis of a lineage IV peste des petits ruminants virus in southern China - Xiao-Peng Li; Shao-Lun Zhai; Dong-Sheng He; Peng-Ju Guo; Dian-Hong Lv; Xiao-Hui Wen; Man-Lin Luo; Rui-Ai Chen; Wen-Kang Wei (Virus Genes, 2015)

Potential Neurogenesis of Human Adipose-Derived Stem Cells on Electrospun Catalpol-Loaded Composite Nanofibrous Scaffolds - Jian-Hui Guo; Yang Liu; Zheng-Jun Lv; Wen-Juan Wei; Xin Guan; Qing-Lin Guan; Zhi-Qian Leng; Jing-Yuan Zhao; Hui Miao; Jing Liu (Annals of Biomedical Engineering, 2015)

Health risk assessment of metals in food crops and related soils amended with biogas slurry in Taihu Basin: perspective from field experiment - Bo Bian; Hai suo Wu; Lin Lv; Yamin Fan; Haiming Lu (Environmental Science and Pollution Research, 2015)

Correlation analysis of gene polymorphisms and β-lactam allergy - Jing Li; Xin-yue Liu; Lin-jing Li; Chong-ge You; Lei Shi; Shang-di Zhang; Qian Liu; Jun Wang; Ze-jing Liu; Ting-hong Lv (Journal of Zhejiang University-SCIENCE B, 2015)

Physical‐biological coupling of N 2 fixation in the northwestern S outh C hina S ea coastal upwelling during summer - Run Zhang; Min Chen; Qing Yang; Yuanshao Lin; Huabin Mao; Yusheng Qiu; Jinlu Tong; E. Lv; Zhi Yang; Weifeng Yang; Jianping Cao (Limnology and Oceanography, 2015)
Here, we present the first combined results of N 2 fixation rates ( 15 N 2 assay), dissolved iron (dFe, 14 C assay) in the northwestern South China Sea (NWSCS) coastal upwelling region during summer. Surface N 2 fixation rate ranged between 0.1 nmol N L −1 d −1 and 5.6 nmol N L −1 d −1 (average 1.0 nmol N L −1 d −1 , n = 50) under nonbloom conditions. At a Trichodesmium bloom station, N 2 fixation rate was ∼ 3 orders of magnitude higher. Depth‐integrated N 2 fixation rate ranged between 7.5 μmol N m −2 d −1 and 163.1 μmol N m −2 d −1 (average 46.4 μmol N m −2 d −1 ). Our results indicate that N 2 fixation is unlikely limited by Fe availability in the NWSCS continental waters, instead, the coastal upwelling‐induced combined effects of physical and biological processes may have played a decisive role. With the upwelled cold, dFe‐rich, nutrient‐replete waters, nondiazotrophic phytoplankton growth would be preferentially enhanced while N 2 fixation was hindered due to relative deficiency of phosphate caused by massive phytoplankton utilization in the coastal upwelling. By comparison, N 2 fixation was notably elevated along with decreased PP in the offshore waters, probably due to a shift from P‐deficiency to N‐deficiency. Consistently, the contribution of N 2 fixation to PP (0.01–2.52%) also increased toward the open waters. As a significant external N source, summertime N 2 fixation is estimated to contribute a flux of 1.4 Gmol N to this area under nonbloom conditions. This study adds to the knowledge of N 2 fixation in the rarely studied subtropical coastal upwellings, and highlights the necessity of future comprehensive studies in such highly dynamic environments.

P2X7 receptor of rat dorsal root ganglia is involved in the effect of moxibustion on visceral hyperalgesia - Shuangmei Liu; Qingming Shi; Qicheng Zhu; Ting Zou; Guilin Li; An Huang; Bing Wu; Lichao Peng; Miaomiao Song; Qin Wu; Qiuyu Xie; Weijian Lin; et al. (Purinergic Signalling, 2015)

CRISPR/Cas9 Systems: The Next Generation Gene Targeted Editing Tool - Shengchun Guo; Ying Lv; Yuxiang Lin; Kaixuan Lin; Peng Peng; Yangxiu Wu; Jingli Peng; Shaoyun Song; Zhining Li; Qiuyun Liu (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

Risk assessment of heavy metals in air, water, vegetables, grains, and related soils irrigated with biogas slurry in Taihu Basin, China - Bo Bian; Ling Jun Zhou; Lei Li; Lin Lv; Ya Min Fan (Environmental Science and Pollution Research, 2015)

Plastorhodobacter daqingensis gen. nov., sp. nov.: A Non-phototrophic Bacterium Isolated from Daqing Oilfield - Bai-Sheng Xie; Xiang-Lin Lv; Man Cai; Yue-Qin Tang; Ya-Nan Wang; Heng-Lin Cui; Xue-Ying Liu; Yan Tan; Xiao-Lei Wu (Current Microbiology, 2015)

Nd(III)-Induced Rice Mitochondrial Dysfunction Investigated by Spectroscopic and Microscopic Methods - Cai-Fen Xia; Long Lv; Xin-You Chen; Bo-Qiao Fu; Ke-Lin Lei; Cai-Qin Qin; Yi Liu (The Journal of Membrane Biology, 2015)

Altered splenic miRNA expression profile in H1N1 swine influenza - Liangzong Huang; Jun Ma; Yankuo Sun; Yanli Lv; Wen Lin; Mingjie Liu; Changsong Tu; Pei Zhou; Wanjun Gu; Shuo Su; Guihong Zhang (Archives of Virology, 2015)

Marinobacter shengliensis sp. nov., a moderately halophilic bacterium isolated from oil-contaminated saline soil - Yi-Jing Luo; Bai-Sheng Xie; Xiang-Lin Lv; Man Cai; Ya-Nan Wang; Heng-Lin Cui; Hua Cai; Xiao-Lei Wu (Antonie van Leeuwenhoek, 2015)

Detection of spotted fever group Rickettsiae in ticks from Zhejiang Province, China - Jimin Sun; Junfen Lin; Zhenyu Gong; Yue Chang; Xiaodong Ye; Shiping Gu; Weilong Pang; Chengwei Wang; Xiaohua Zheng; Juan Hou; Feng Ling; Xuguang Shi; et al. (Experimental and Applied Acarology, 2015)

Isolation and characterization of microsatellite loci in the dog-faced water snake Cerberus rynchops (Colubridae) - Xiao-Hui Lv; Shu-Zhan Zhao; Xiao-Xiao Zheng; Long-Hui Lin (Conservation Genetics Resources, 2015)

Characteristics of evodiamine-exerted stimulatory effects on rat jejunal contractility - Yong-Jian Xiong; Da-Peng Chen; Jin-Yong Peng; Jing-Yu Wang; Bo-Chao Lv; Fang-Fei Liu; Yuan Lin (Natural Product Research, 2015)

Studies on mitogen-activated protein kinase signaling pathway in the alveolar macrophages of chronic bronchitis rats - Yan Huang; Xiao-Ming Meng; Guo-Lin Jiang; Ya-Ru Yang; Juan Liu; Xiong-Wen Lv; Jun Li (Molecular and Cellular Biochemistry, 2015)

Cloning of a caffeoyl-coenzyme A O-methyltransferase from Camellia sinensis and analysis of its catalytic activity - Yue Zhang; Hai-peng Lv; Cheng-ying Ma; Li Guo; Jun-feng Tan; Qun-hua Peng; Zhi Lin (Journal of Zhejiang University-SCIENCE B, 2015)

Halodurantibacterium flavum gen. nov., sp. nov., a Non-phototrophic Bacterium Isolated from an Oil Production Mixture - Xiang-Lin Lv; Bai-Sheng Xie; Man Cai; Yue-Qin Tang; Ya-Nan Wang; Heng-Lin Cui; Xue-Ying Liu; Yan Tan; Xiao-Lei Wu (Current Microbiology, 2015)

Expression and Localization of Estrogen Receptor in Human Breast Cancer and Its Clinical Significance - Lv Li; Qimin Wang; Xiupeng Lv; Lin Sha; Huamin Qin; Lifen Wang; Linlin Li (Cell Biochemistry and Biophysics, 2015)

USP11 regulates p53 stability by deubiquitinating p53 - Jia-ying Ke; Cong-jie Dai; Wen-lin Wu; Jin-hua Gao; Ai-juan Xia; Guang-ping Liu; Kao-sheng Lv; Chun-lin Wu (Journal of Zhejiang University-SCIENCE B, 2014)

Seohaeicola nanhaiensis sp. nov., A Moderately Halophilic Bacterium Isolated from the Benthic Sediment of South China Sea - Bai-Sheng Xie; Xiang-Lin Lv; Man Cai; Yue-Qin Tang; Yan-Nan Wang; Heng-Lin Cui; Xue-Ying Liu; Yan Tan; Xiao-Lei Wu (Current Microbiology, 2014)

First molecular detection of porcine circovirus type 2 in bovids in China - Shao-Lun Zhai; Rui-Ai Chen; Sheng-Nan Chen; Xiao-Hui Wen; Dian-Hong Lv; Da-Cheng Wu; Jie Yuan; Zhong Huang; Xiu-Rong Zhou; Man-Lin Luo; Dong-Sheng He; Wen-Kang Wei (Virus Genes, 2014)

Genome-wide identification of housekeeping genes in maize - Feng Lin; Lu Jiang; Yuhe Liu; Yuanda Lv; Huixue Dai; Han Zhao (Plant Molecular Biology, 2014)

Expression of the HPV18E2 Gene in Cervical Cancer and Premalignant Lesions and its Clinical Significance - Ling Mou; Bin Wu; Ya Hu; Ying Lan; Feng-Lin Lv (Cell Biochemistry and Biophysics, 2014)

Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) prevents apoptosis induced by hydrogen peroxide in basilar artery smooth muscle cells - Jia-Wei Zeng; Xue-Lin Zeng; Fei-Ya Li; Ming-Ming Ma; Feng Yuan; Jie Liu; Xiao-Fei Lv; Guan-Lei Wang; Yong-Yuan Guan (Apoptosis, 2014)

Effects of ginsenoside Re on rat jejunal contractility - Yongjian Xiong; Dapeng Chen; Bochao Lv; Fangfei Liu; Qiying Yao; Zeyao Tang; Yuan Lin (Journal of Natural Medicines, 2014)

Variants of COL3A1 Are Associated with the Risk of Stroke Recurrence and Prognosis in the Chinese Population: a Prospective Study - Wenfei Lv; Yahui Lin; Weihua Song; Kai Sun; Hui Yu; Yinhui Zhang; Channa Zhang; Liang Li; Miaomiao Suo; Rutai Hui; Jingzhou Chen (Journal of Molecular Neuroscience, 2014)

The roles of autophagy in development and stress responses in Arabidopsis thaliana - Xin Lv; Xiaojun Pu; Gongwei Qin; Tong Zhu; Honghui Lin (Apoptosis, 2014)

Expression and roles of As-NUPR1 protein from Artemia sinica during embryo development and in response to salinity stress - Rui Zhang; Feng Yao; Cheng Cheng; Yifei Chen; Ying Lv; Zengrong Li; Na Zhao; Ting Wang; Wenting Xin; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2014)

Aroma changes of black tea prepared from methyl jasmonate treated tea plants - Jiang Shi; Li Wang; Cheng-ying Ma; Hai-peng Lv; Zong-mao Chen; Zhi Lin (Journal of Zhejiang University-SCIENCE B, 2014)

Cloning and expression patterns of the brine shrimp (Artemia sinica) glycogen phosphorylase (GPase) gene during development and in response to temperature stress - Na Zhao; Ming Hou; Ting Wang; Yifei Chen; Ying Lv; Zengrong Li; Rui Zhang; Wenting Xin; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2014)

Role of the PTEN signaling pathway in autism spectrum disorder - Jing-Wen Lv; Tian-Lin Cheng; Zi-Long Qiu; Wen-Hao Zhou (Neuroscience Bulletin, 2013)

Identification of MHC class I sequences in four species of Macaca of China - Xiang Yan; Aixue Li; Lin Zeng; Yuhua Cao; Jianbin He; Longbao Lv; Lihua Sui; Huahu Ye; Junwen Fan; Xiaoxia Cui; Zhaozeng Sun (Immunogenetics, 2013)

Abnormal baseline brain activity in patients with HBV-related cirrhosis without overt hepatic encephalopathy revealed by resting-state functional MRI - Xiao-Fei Lv; Min Ye; Lu-Jun Han; Xue-Lin Zhang; Pei-Qiang Cai; Gui-Hua Jiang; Ying-Wei Qiu; Shi-Jun Qiu; Yao-Pan Wu; Kai Liu; Zhen-Yin Liu; Pei-Hong Wu; et al. (Metabolic Brain Disease, 2013)

Quantitative analysis of the association between interleukin-10 1082A/G polymorphism and susceptibility to sepsis - Lin Ouyang; You-Di Lv; Can Hou; Guo-Bao Wu; Zhi-Hui He (Molecular Biology Reports, 2013)

High prevalence of torque teno sus virus in China and genetic diversity of the 5’ non-coding region - Shao-Lun Zhai; Jin-Xue Long; Wen-Kang Wei; Qin-Ling Chen; Man-Lin Luo; Dian-Hong Lv; Da-Cheng Wu; Fei Gao; Shi-Shan Yuan; Guang-Zhi Tong; Zu-Zhang Wei (Archives of Virology, 2013)

Overexpression of a GmGBP1 ortholog of soybean enhances the responses to flowering, stem elongation and heat tolerance in transgenic tobaccos - Lin Zhao; Zhixin Wang; Qingyao Lu; Pengpeng Wang; Yongguang Li; Qingxue Lv; Xianping Song; Dongmei Li; Yuejiao Gu; Lixue Liu; Wenbin Li (Plant Molecular Biology, 2013)

Involvement of FGF9/16/20 subfamily in female germ cell development of the Nile tilapia, Oreochromis niloticus - Yun-Lv Sun; Sheng Zeng; Kai Ye; Chao Yang; Ming-Hui Li; Bao-Feng Huang; Li-Na Sun; Lin-Yan Zhou; De-Shou Wang (Fish Physiology and Biochemistry, 2012)

Effects of heavy metals on the expression of a zinc-inducible metallothionein-III gene and antioxidant enzyme activities in Crassostrea gigas - Ming Cong; Huifeng Wu; Xiaoli Liu; Jianmin Zhao; Xuan Wang; Jiasen Lv; Lin Hou (Ecotoxicology, 2012)

Inhibitory effect of Salicornia europaea on the marine alga Skeletonema costatum - Dan Jiang; LingFeng Huang; YongQing Lin; LingLing Nie; SuLian Lv; TingYun Kuang; YinXin Li (Science China Life Sciences, 2012)

Cryotherapy is Associated with Improved Clinical Outcomes of Sorafenib Therapy for Advanced Hepatocellular Carcinoma - Yongping Yang; Yinying Lu; Chunping Wang; Wenlin Bai; Jianhui Qu; Yan Chen; Xiujuan Chang; Linjing An; Lin Zhou; Zhen Zeng; Min Lou; Jiyun Lv (Cell Biochemistry and Biophysics, 2012)

PDGF-induced airway smooth muscle proliferation is associated with Human antigen R activation and could be weakened by AMPK activation - Pengju Zhang; Mingfeng Cao; Yi Liu; Zhimei Lv; Qingrui Yang; Xiaoyan Lin; Huaichen Li; Qiang Wan (Molecular Biology Reports, 2012)

Variation in Genotype and Higher Virulence of a Strain of Sporothrix schenckii Causing Disseminated Cutaneous Sporotrichosis - Zhenying Zhang; Xiaoming Liu; Xuelian Lv; Jingrong Lin (Mycopathologia, 2011)

Expression, purification, and activity assay of peptide deformylase from Escherichia coli and Staphylococcus aureus - Xuchun Che; Jinwei Hu; Lijuan Wang; Zhifeng Zhu; Qiong Xu; Junqiang Lv; Zheng Fu; Yajun Sun; Jia Sun; Gang Lin; Rong Lu; Zhi Yao (Molecular and Cellular Biochemistry, 2011)

Ningdong granule: a complementary and alternative therapy in the treatment of attention deficit/hyperactivity disorder - Ji-Jun Li; Zai-Wang Li; Shu-Zhen Wang; Fang-Hua Qi; Lin Zhao; Hong Lv; An-Yuan Li (Psychopharmacology, 2011)

Role of microRNA-21 and effect on PTEN in Kazakh’s esophageal squamous cell carcinoma - Wen-jing Ma; Guo-dong Lv; Aerziguli Tuersun; Qing Liu; Hui Liu; Shu-tao Zheng; Cong-gai Huang; Jun-guo Feng; Xing Wang; Ren-yong Lin; Ilyar Sheyhidin; Xiao-mei Lu (Molecular Biology Reports, 2011)

Unique evolution characteristics of the envelope protein of EIAVLN40, a virulent strain of equine infectious anemia virus - Xuefeng Wang; Shuai Wang; Yuezhi Lin; Chenggang Jiang; Jian Ma; Liping Zhao; Xiaoling Lv; Fenglong Wang; Rongxian Shen; Jianhua Zhou (Virus Genes, 2011)

Clinical Evaluation of Targeted Arterial Infusion of Verapamil in the Interventional Chemotherapy of Primary Hepatocellular Carcinoma - Jin Huang; Qiaohong Duan; Pingsheng Fan; Chushu Ji; Yuying Lv; Xinmin Lin; Liting Qian; Xiukun Yu (Cell Biochemistry and Biophysics, 2011)

The expression and activation of ERK/MAPK pathway in human esophageal cancer cell line EC9706 - Shu-Tao Zheng; Qi Huo; Aerziguli Tuerxun; Wen-Jing Ma; Guo-Dong Lv; Cong-Gai Huang; Qing Liu; Xing Wang; Ren-Yong Lin; Ilyar Sheyhidin; Xiao-Mei Lu (Molecular Biology Reports, 2011)

Genomic comparison between attenuated Chinese equine infectious anemia virus vaccine strains and their parental virulent strains - Xuefeng Wang; Shuai Wang; Yuezhi Lin; Chenggang Jiang; Jian Ma; Liping Zhao; Xiaoling Lv; Fenglong Wang; Rongxian Shen; Xiangang Kong; Jianhua Zhou (Archives of Virology, 2011)

The pentapeptide PLNPK inhibits systemic lupus erythematosus-associated renal damage - Jun-qiang Lv; Wen Zhang; Song Wang; Lin Zhao; Rui Ma; Jin-wei Hu; Li-juan Wang; Jie Meng; Chun-lei Zhou; Gang Lin; Rong Lu; Zhi Yao (Inflammation Research, 2010)

Knockdown of the prion gene expression by RNA interference in bovine fibroblast cells - Shaohua Wang; Xiaoqing Lv; Kun Zhang; Tonghui Lin; Xiaofang Liu; Jing Yuan; Yunping Dai; Ning Li (Molecular Biology Reports, 2010)

Genomic analysis of an effective lentiviral vaccine-attenuated equine infectious anemia virus vaccine EIAVFDDV13 - Xu Qi; Xuefeng Wang; Shuai Wang; Yuezhi Lin; Chenggang Jiang; Jian Ma; Liping Zhao; Xiaoling Lv; Rongxian Shen; Fenglong Wang; Xiangang Kong; Zhiqiang Su; et al. (Virus Genes, 2010)

High prevalence of a novel porcine bocavirus in weanling piglets with respiratory tract symptoms in China - Shaolun Zhai; Cheng Yue; Zuzhang Wei; Jinxue Long; Duoliang Ran; Tao Lin; Yu Deng; Lv Huang; Lichang Sun; Haihong Zheng; Fei Gao; Hao Zheng; et al. (Archives of Virology, 2010)

Protein phosphatase 1A (PPM1A) is involved in human cytotrophoblast cell invasion and migration - Baohua Zhang; Zhi Zhou; Haiyan Lin; Xiaoyin Lv; Jiejun Fu; Ping Lin; Cheng Zhu; Hongmei Wang (Histochemistry and Cell Biology, 2009)

Analysis of magnetic elements in otoliths of the macula lagena in homing pigeons with inductively coupled plasma mass spectrometry - Ying Zhao; Yi-Na Huang; Lv Shi; Lin Chen (Neuroscience Bulletin, 2009)

Overexpression of Thellungiella halophila H+-PPase (TsVP) in cotton enhances drought stress resistance of plants - Su-Lian Lv; Li-Jun Lian; Pei-Lin Tao; Zhao-Xia Li; Ke-Wei Zhang; Ju-Ren Zhang (Planta, 2009)

Human mesenchymal stem cells-like cells as cellular vehicles for delivery of immunotoxin in vitro - Chang-chen Hu; Yi-quan Ke; Xin-lin Sun; Xiao-dan Jiang; Ru-xiang Xu; Jun Lv; Yu-sheng Wang; Ying-qian Cai; Ling-sha Qin; Yu-xi Zou (Biotechnology Letters, 2009)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

IGFBP7 plays a potential tumor suppressor role against colorectal carcinogenesis with its expression associated with DNA hypomethylation of exon 1 - Wen-jing Ruan; Jie Lin; En-ping Xu; Fang-ying Xu; Yu Ma; Hong Deng; Qiong Huang; Bing-jian Lv; Hu Hu; Jing Cui; Mei-juan Di; Jian-kang Dong; et al. (Journal of Zhejiang University-SCIENCE B, 2006)